Metabolic redirection and capacity expansion in heterotroph-reinforced microalgae-methanotroph systems under high ammonia stress - Yong-Ze Lu; Jia-Sen Yang; Xin-Ya Tan; Yi-Ru Wang; Hong-Yin Sha; Hao-Yu Wang; Shao-Jie Zong; Guang-Can Zhu (Bioresource Technology, 2027)

Chemical constituents from the aerial parts of Clematis terniflora DC - Meng-Ya Chen; Zi-Han Zhu; Xin-Yu Yu; Ya-Ru Wu; Shi-Hui Qian; Zhen-Lin Li (Biochemical Systematics and Ecology, 2027)

Seasonal occurrence and offshore accumulation of phycotoxins in a subtropical semi-enclosed bay: Insights from a year-round survey in Qinzhou Bay, South China Sea - Hui-Xia Geng; Zhuo-Ru Lin; Wen-Jiao Tang; Sara A. Cunha; Zhen-Jun Kang; Xiao-Tian Han; Jin-Xiu Wang; Ren-Cheng Yu (Marine Pollution Bulletin, 2026)

Stratigraphy, sedimentology, and palaeoenvironment of dinosaur-bearing Upper Cretaceous Zhengyang Formation in Zhengyang Basin, Chongqing, Southwest China - Hui Dai; Jun Wang; Liang-Dong Luo; Qian-Ru Wen; Su-Chin Chang; Yu Lin; Ming Xiao; Hai Xing (Palaeoworld, 2026)

Structure and characteristics of quercetin-loaded starch nanoparticles and their surface charges for protein corona formation with gastrointestinal digestive enzymes - Yu-Ru Wu; Zhi-Yuan Yang; Shan-Dan Zhao; Dan-Yang Shen; Ya-Jun Lin; Yi-Bin Zhou; Kang Liu (Food Hydrocolloids, 2026)

Paternal vitamin D deficiency is associated with offspring testicular developmental abnormalities, fibrosis, and altered sperm miRNA profiles - Yu-Ming Chen; Zhi-Hong Tian; Shi-Yuan Li; Juan Dai; Xing-Ru Wang; Guo-Ying Sun; Min Liu; Berthold Hocher; Mei Tian (Molecular Biology Reports, 2026)

Enhancing weed control in imidazolinone-resistant corn and soybean strip intercropping systems through tank mixtures of imidazolinone and residual herbicides - Yi Ru; Xiangxin Zhuang; Lingyang Feng; Hongyou Wan; Jialin Yu (Crop Protection, 2026)

Insulin-like peptide 3 facilitates sheep oocytes in vitro maturation and subsequent early embryo development - Qi Yang; Rui-Feng Zhang; Zhao-Yu Jiang; Dui Sun; Rui-Hao Tang; Xiao-Yi Zhang; Yi-Tong Li; Wen-Ying Li; Ao Liu; Chun-Lan Zhang; Zhi-Wen Jia; Meng-Lei Feng; et al. (Theriogenology, 2026)

Phylogenomics of Tanypodinae (Diptera: Chironomidae) redefines relationships in Procladiini and Tanypodini and supports a new tribe - Xiu-Ru Xiao; Yi-Ni Zhang; Hai-Feng Xu; Zhi-Chao Zhang; Yu-Yi Jiang; Yan-Xin Chen; Chen-Hong Li; Bing-Jiao Sun; Fabio Laurindo da Silva; Xiao-Long Lin (Molecular Phylogenetics and Evolution, 2026)

Origin of fast backward steps and detachment of kinesin motor under backward load - Jie Wang; Xiao-Xuan Shi; Yu-Ru Liu; Peng-Ye Wang; Ping Xie (Journal of Theoretical Biology, 2026)

Polymer-specific oxidative biotransformation of polyethylene and polypropylene microplastics by the stored-grain pest Tribolium castaneum - Sakhawat Shah; Jin-Ru Zhao; Ze-Yu Liu; Yi-Jia Chen; Jie Tang; Karam Khamis Elgizawy; Qiu-Ying Huang; Elvis Genbo Xu; Feng-Lian Yang (Chemical Engineering Journal, 2026)

Apoptotic vesicle-hybridized nanosponges enable dual-phase immunomodulation for targeted periodontitis therapy - Xiao-Ru Xu; Xin-Yan Luo; Lu-Fan Yang; Fei-Ran Wang; Jia-Wei Lu; Bai-Ting Luan; Yuan Yuan; Zi-Qi Zhang; Jin-Yu Liu; Yuan-Yuan Li; Yi-Han Liu; Yu Fu; et al. (Chemical Engineering Journal, 2026)

Metagenomics-guided targeted isolation and mechanistic elucidation of haloalkaliphilic bisphenol A-degrading microorganisms - Sai Yang; Kai-yan Xing; Yue-fei Tao; Jia-yu Wang; Ke-hang Liu; Meng Zhang; Xiang-ru Xu; Lin Zhu; Wei Wei (Bioresource Technology, 2026)

Accumulation, elimination and biotransformation of paralytic shellfish toxins in ark shell Anadara kagoshimensis - Zhuo-Ru Lin; Hui-Xia Geng; Sara A. Cunha; Chang Xu; Ren-Cheng Yu (Marine Pollution Bulletin, 2026)

Integrated transcriptomic and metabolomic analyses reveal the involvement of AtGASA1 and AtGASA4 in salicylic acid pathway-associated immune responses in Arabidopsis - Jian-Bo Song; Ya-Ru Li; Zi-Xin Zhao; Xian-Zhi Zuo; Cai-Feng Wang; Min Huang; Shu-Fan Liu; Yu-Fan Chen; Wen-Qian Song; Lin Wang; Ying-Juan Wang; Xuan Huang (Plant Science, 2026)

Carbon dot-based catalytic materials: From photo/electrocatalysis to nanozyme activity - Pei-De Zhu; Chang Liu; Hui Wang; Rong-Yu Yao; Ling-Rui Sun; Xin-Ru Xu; Jing-Wen Jiang; Ying-Sheng Xu; Kun-Peng Lin; Jia-Xing Wu (Journal of Environmental Chemical Engineering, 2026)

The co-ecotoxicity of microplastics and associated contaminants (PFOA) on soil ecosystems - Si-Yu Liu; Feng Han; Li-Qi Ma; Zheng Li; Chun-Ru Qin; Ikram Yaqine; Yi-kai Wang; Jian Su; Jie Chen (Journal of Environmental Chemical Engineering, 2026)

Lattice carbon-induced electronic regulation of AlCo2O4 spinels for boosting toluene oxidation - Dadao Wang; Xueqin Yang; Mimi Wu; Menglan Xiao; Yanhu Zhang; Mianmian Zhang; Xiuhong Zhu; Guangxin Ru; Yucong Guo; Bo Shi; Xiaolin Yu; Maofa Ge (Journal of Environmental Chemical Engineering, 2026)

Novel electrochemical sensor for histamine: enhancing food safety with polydopamine-modified crystalline NCU-1 zincophosphate material - Asit Kumar Panda; Yu-Chung Chang; Murugan Thiruppathi; Chun-Ru Hsu; Ching-Ping Lu; Yu-Ru Huang; Ja-an Annie Ho; Chih-Min Wang (Food Research International, 2026)

Non-nutritive sweeteners in hand-shaken beverages: Occurrence, consumption patterns, and dietary risk assessment - Yu-Chia Yeh; Wan-Ru Li; Yu-Syuan Luo (Food Research International, 2026)

Amine-functionalized oyster shell waste for hexavalent chromium removal and phosphate recovery - Kamonchanok Huangmee; Liang-Ching Hsu; Guan-Ru Liu; Pei-Chieh Tseng; Heng Yi Teah; Yu-Min Tzou; Nhu Anh Thi Than; Han-Yu Hsueh; Yu-Ting Liu (Bioresource Technology, 2026)

Intracellular imaging and therapeutic application of liver fibrosis via a microRNA-on self-stacking amplification circuit - Xiao-Meng Sun; Yin-Xiang Chen; Lin-Ru Xu; Rui Bai; Li-Zeng Zhu; Gaoxiang Ma; Lian-Wen Qi; Yu Gu; Qun Liu (Analytica Chimica Acta, 2026)

Close-to-nature management alters litterfall production and nutrient return in Chinese fir (Cunninghamia lanceolata) plantations across Southern China - Shu-meng Wei; Xiang-teng Chen; Ru-zhen Jiao; Xiong-qing Zhang; Yu-hong Dong (European Journal of Forest Research, 2026)

Targeting microglial TLR3–NF-κB/MAPK and JAK/STAT Axis: PEITC as a suppressor of poly (I:C)-induced neuroinflammation - Yi-Ching Lan; Yan-Ru Xiao; Yow-Wen Hsieh; Yih-Dih Cheng; Shu-Fen Peng; Fu-Shin Chueh; Hsu-Tung Lee; Yu-Sheng Hsieh; Wei-Cheng Jiang; Wen-Tsong Hsieh; Yu-Cheng Chou (Toxicology and Applied Pharmacology, 2026)

Asymmetric evolution of capturability of atmospheric water (CAW) across global arid and humid regions - Hou-Liang Lu; Hong-Ru Wang; Hui-Min Zuo; Han Zhou; Yu-Fei Jiao; Bill X. Hu (Journal of Hydrology, 2026)

Optimized green extraction of flavonoids from Lycium barbarum leaves using betaine-ethylene glycol NADES: Mechanisms, identification, and bioactivity - Ya-Jie Yuan; Zhen Liu; Yu-Ru Wang; Xin-Yue Zhang; Qian Ma; Cen Xiang; Jun-Wei Yu; Yu-Ou Teng (Food Chemistry, 2026)

A macin family antimicrobial peptide from Atrina pectinata exhibiting dual functions in direct bactericidal activity and hemocyte immune modulation - Yan-ru Chen; Kun-yu Zhao; Shun-xin Hu; Ding-long Yang; Xue-peng Li; Li-zhu Chen; Jian-min Zhao (Fish & Shellfish Immunology, 2026)

Outdoor light at night exposure and hypertension risk in adults: A longitudinal cohort study from the FLORA project - Shuo Zhang; Xiao-Fan Lu; Muhammad Amjad; Lin-Jing Gong; Na Liu; Hong-Xing Zou; Xiao-Yi Liu; Le-Bing Wang; Yuan-Yuan Fan; Yang-Yang Li; Yi-Ran Chen; Wen-Wen Bao; et al. (Environmental Research, 2026)

Heterolytic urea exchange-mediated thermal locking: Architecting 3D printed photo-mechanochromic smart elastomers - Min Yu; Yeting Huang; Dong Wang; Ru Song; Hanzhao Gong; Shuming Zhang; Xiaoyu Han; Yangzheng Li (Chemical Engineering Journal, 2026)

Corrigendum to “Mg-doped CoCr₂O₄ nanoparticles with fast humidity sensing and mixed-controlled pseudocapacitive charge storage” [Chem. Eng. J. 535 (2026) 175200] - K. Manjunatha; Shih-Lung Yu; Yi-En Wu; Ming-Kang Ho; Tsu-En Hsu; Yun-Tai Yu; B. Chethan; Mithun Prakash Ravikumar; Sakar Mohan; Tsung-Te Lin; Yi-Ru Hsu; Meng-Chu Chen; et al. (Chemical Engineering Journal, 2026)

Plasma-engineered chitosan couples red-light bioenergetics to diabetic wound regeneration through programmable microenvironments - Lekshmi Rethi; Hoa Duc Chau; Erlina Febriani; Yan-Ting Chen; Szu-Yu Tung; Pei-Ru Jheng; Yu-Wen Tseng; Rou Li; Min-Lang Tsai; Chun-Chi Chang; Van Khiet Pham; Hieu Trung Nguyen; et al. (Carbohydrate Polymers, 2026)

Quercetin restores oocyte maturation and embryo development in DEHP-exposed mice via mitochondrial protection and apoptosis inhibition - Dui Sun; Qi Yang; Zhi-Hui Gong; Meng-Lei Feng; Zhi-Wen Jia; Bin-Shuo Yang; Zhao-Yu Jiang; Chun-Ru Song; Fang-Rui Xue; Xiao-Jie Zhang; Hao-Yang Zhang; Chun-Lan Zhang; et al. (Chemico-Biological Interactions, 2026)

Kit Ligand enhances in vitro oocyte maturation and early embryonic development in sheep - Qi Yang; Dui Sun; Zhao-Yu Jiang; Rui-Hao Tang; Rui-Feng Zhang; Xiao-Yi Zhang; Wen-Ying Li; Yi-Tong Li; Ao Liu; Chun-Lan Zhang; Zhi-Wen Jia; Meng-Lei Feng; et al. (Animal Reproduction Science, 2026)

Activation-optimized anti-CD3 valency control enables combinatorial discovery of multi-specific nanoantibodies for solid tumor immunotherapy - Long Zhu; Ya-Jing Ma; Jian-Kang Kang; Xiu-Hai Che; Dong-Kun Zhao; Yin-Yi Cai; Yao-Ru Yu; Song Shen; Jun Wang (Science Bulletin, 2026)

Paedocin A: An undescribed iridoid with a C1-C4 ether linkage from Paederia foetida with hepatoprotective effects - Wan-Qi Zhang; Xin-Yue Li; Ming-Hui Sun; Jie Zhou; Guo-Ru Shi; De-Quan Yu; Yan-Fei Liu (Phytochemistry Letters, 2026)

Phytohormonal orchestration of plant phosphate starvation responses - Kai-Kai Lu; Ru-Feng Song; Yu-Pu Fan; Ling-Yu Xu; Bo-Hao Chen; Shu-Xian Li; Meng-Tian Sun; Guo-Mao Liu; Xiao-Li Huang; Lin Li; Xin-Ru Guo; Feng Ren; et al. (Journal of Plant Physiology, 2026)

TRMT10A maintains lipid homeostasis independently of its tRNA m1G9 methyltransferase activity - Huihui Sun; Yu Wang; Shanpeng Liu; Yan Jin; Jianyang Ge; Bowen Zhang; Yongteng Wang; Weifeng Sun; Yun Bai; Yuyong Tao; Yi Lu; Ru-Juan Liu; et al. (Science China Life Sciences, 2026)

From Lab to Farm: A Low‐Cost Naked‐Eye On‐Site Detecting Platform for Cynoglossus semilaevis Parvovirus Based on Magnetic Beads Adsorption and LAMP ‐ HNB - Shu‐Xia Xue; Si‐Yu Yang; Meng‐Han Xu; Xin‐Rui Liu; Ye‐Xuan Liu; Zi‐Tong Li; Yi‐Xuan Li; Jia‐Ru Hu; Li‐Xian Huang; Xin‐Yi Zhang; Chang Lu; Yu‐Ru Liu; et al. (Journal of Fish Diseases, 2026)
Cynoglossus semilaevis parvovirus (CsPV) is an important pathogen that poses a serious threat to the aquaculture industry. In the absence of vaccines and effective therapeutic drugs, early and sensitive detection of the pathogen is the key measure to prevent and control the outbreaks and epidemics of viral diseases. Currently, the existing detection methods for CsPV are expensive and rely on specialized operations, limiting the application of on‐site detection. There is an urgent need for a low‐cost, user‐friendly detecting platform to prevent fish viral diseases. In this study, we confirmed skin mucus as a target tissue for non‐lethal sampling, established a simple proteinase K digestion, 2% CTAB lysis and silica‐hydroxylated magnetic beads adsorption method for extracting viral genomic DNA from skin mucus and developed a visual one‐pot loop‐mediated isothermal amplification (LAMP) detection method with a sensitivity of 4.69 × 10 1 copies/μL. Validation of the detection platform using clinical samples showed 97% sensitivity and 100% specificity. The cost of reagents for per sample was reduced from 16.6 CNY to 6.2 CNY. The low‐cost naked‐eye on‐site detection platform provides technical support for resource‐limited aquaculture farms to prevent and control emerging viral diseases in Chinese tongue sole.

Microplastics Inhibit Microbial Abundance and Enzyme Activities in Pb/Cd Co-contaminated Soil: The Alleviating Role of Biochar - Si-Yu Liu; Feng Han; Li-Qi Ma; Zheng Li; Chun-Ru Qin; Ikram Yaqine (Journal of Soil Science and Plant Nutrition, 2026)

Precision droplet deposition control in helicopter spraying: a novel valve-switch timing method accounting for headwind effects - Shuping Fang; Yu Ru; Ningning Wang; Xiaojun Jin; Chunxia Jiang; Yangyang Liu; Chao Zhang (Computers and Electronics in Agriculture, 2026)

Deep carbon cycling in continental subduction zones - Sheng-Ao Liu; Wan-Yu Sun; Yuan-Ru Qu; Hong-Li Yang (Lithos, 2026)

Elucidating the role of ammonia doping in modulating combustion dynamics in ethane fuel-rich jet flames - Bipro Gain; Muhammad Bilal; Yun-Fan Wang; Ahmed E. Mansy; Muhammad Yousuf; Kai-Ru Jin; Du Wang; Boyang Su; Aqsa Liaqat; Mohammed Khalil; Zhi-Min Wang; Qingli Li; et al. (Fuel, 2026)

Numerical and experimental study on the soot formation in methane multi-jet flames under microgravity - Wen-Jiao Wang; Kai-Ru Jin; Zhi-Hao Zheng; Hong-Qing Shi; Du Wang; Ling-Nan Wu; Ya-Wen Liu; Longfei Li; Jiayu Sun; Yu Cheng Liu; Zhen-Yu Tian (Fuel, 2026)

Green and efficient extraction of polyphenols from Lycium barbarum leaves using a betaine-based natural deep eutectic solvent: Process optimization, mechanistic elucidation, and bioactivity evaluation - Ya-Jie Yuan; Zhen Liu; Yu-Ru Wang; Jing-Yi Wang; Qian Ma; Cen Xiang; Jun-Wei Yu; Yu-Ou Teng (Food Chemistry, 2026)

Bioactive PVA/SDES propolis extracts composite films for extending oyster shelf life: Structure, functionality, and preservation performance - Tian Du; Lin-Kun Sun; Pei-Ru Zhou; Yu-Cang Zhang; Yan-Zhen Zheng (Food Packaging and Shelf Life, 2026)

A regional classification framework integrating AI and causal inference revealing the drivers of lake eutrophication in China - Yong Xu; Ru-Long Ma; Yu-Xi Feng; Bin Zou; Shen-Xin Li; Wen-Ting Huang; Shang-Chen Zhou; Wen-Qiang Peng (Water Research, 2026)

Wavelength-tunable light regulates binding affinity of histone deacetylase inhibitors via azobenzene Photoswitches - Yifan Ru; Sifan Guo; Yu He; Xiujuan Huang; Zhenguo Zhang; Lei Shi; Xiaoguang Shao; Zhong Li; Wen Fu; Xusheng Shao (Pesticide Biochemistry and Physiology, 2026)

Synchronized lignocellulosic pyrolysis for activator-free carbon foams: Role of selective hemicellulose removal - Jia-Cheng Ye; Xiao-Ru Meng; Bo Xia; Ting-Yu Bi; Wei Chen; Lu-jiang Xu; Shuai Gao; Zhen Fang (Journal of Environmental Chemical Engineering, 2026)

Superoxide dismutase/peroxidase-like MoS2 quantum dots enhance ammonia synthesis by Klebsiella pasteurii - Meng-Xin Zhao; Si-Ru Chen; Shan-Shan Hu; Ting-Ting Liu; Jia-Le Teng; Ya-Wen Yu; Jia-Long Zhang; Xue-Ru Zhou; Qun-Feng Ye; Su-Fang Qin; Le-Xing You (Journal of Environmental Chemical Engineering, 2026)

Interventional mechanisms of antioxidants on flavor profile modification in the fermented egg white powder system - Ru-yi Zhang; Zhi-shuo Zhang; Yan-jun Yang; Wei-jian Zhang; Jun-hua Li; Yu-jie Su; Lu-ping Gu; Cui-hua Chang (Food Chemistry, 2026)

From air to adipose: Investigating PM2.5-bound chlorinated paraffins and overweight/obesity in Chinese children and adolescents - Qi Yang; Hai-Xin Tu; Yu He; Ya-Qin Zhang; Muhammad Amjad; Jing-Fu Lai; Jing-Wen Huang; Yun-Ting Zhang; Wan-Ting He; Li-Xia Liang; Wen-Wen Bao; Yang Zhou; et al. (Environmental Research, 2026)

Enhancing camptothecin biosynthesis in Camptotheca acuminata through CrLAMT transfer from Catharanthus roseus - Ru Huang; Wen-Hui Ma; Bing-Run Yang; Fang Yu; Ping Kou (Biotechnology Letters, 2026)

Investigation on Ionospheric TEC disturbances During the Geomagnetic Storms Resulted from ICME Events - Chao Niu; Xiang-yu Li; Xiao-niu Zeng; Hong-ru Li; Ji-hao Liu; Ai-min Du (Applied Geophysics, 2026)

Predation, Climate and Species Traits Interact to Shape Global Patterns of Avian Nest Architecture - Stephanie Y. Chia; Yu Tsai‐Chen; Yi‐Ru Cheng; Mao‐Ning Tuanmu; William F. Fagan (Global Ecology and Biogeography, 2026)
Aim Bird nest structures are critical for reproductive success and vary widely across species. However, the ecological and evolutionary drivers behind enclosed nests (domes and cavities) remain unclear, with previous studies yielding conflicting results. Leveraging recently available comprehensive nest trait data, we aim to clarify whether enclosed nests primarily function as protection from predation or for regulation of microclimate. Location Global. Time Period Contemporary (environmental data from 1981 to 2010). Major Taxa Studied Birds (Aves). Methods Using phylogenetic logistic regression models for 7427 bird species, we examined whether the observed relationships between nest structure and potential environmental drivers and species traits were consistent with the predictions of the two functional hypotheses. To explore potential variations in the function, we built separate models for domes and cavities, as well as for passerines and non‐passerines. Results Predation risk increases the likelihood of dome use, especially in passerines, where a stronger increase is among the species that are more susceptible to nest predation such as ground‐nesting, non‐cooperative and larger clutch size species. Climatic effects are more pronounced in cavity nesters, with aridity promoting cavity use among passerines, and both cold and hot temperatures increasing cavity use among small non‐passerine species. Main Conclusions Different types of enclosed nests correspond to distinct environmental challenges, with dome nests primarily associated with predation pressure and cavities with adverse climatic conditions. These findings contribute to resolving long‐standing debates about the functional significance of enclosed nests and offer insights into the evolution of avian nest structures.

Multiprotein-based nanomedicines with dual CD44/CD133 targeting and GSH-responsive drug release for improving cancer chemotherapy - Lu-Yi Yu; Pei-Wei Shueng; Yu-Hsin Wang; Yu-Wei Yen; Kuan-Wei Chen; Chieh-Ru Li; Hsin-Cheng Chiu; Yu-Wen Lin; Chun-Liang Lo (Drug Delivery and Translational Research, 2026)
Albumin, a highly biocompatible protein, has been utilized in the construction of anti-cancer drugs for the treatment of various cancers. However, albumin-based nanomedicines still face several clinical challenges, including low stability in the bloodstream, non-specific targeting ability, and lack of controlled release capability. To address these limitations, we developed a multiprotein-based nanomedicine for targeted chemotherapy of non-small cell lung cancer (NSCLC). This nanomedicine was assembled using a heart-shaped albumin and two Y-shaped anti-CD44 and anti-CD133 antibodies. To enhance stability and improve therapeutic efficacy, the multiproteins were crosslinked using disulfide bond linkers and loaded with paclitaxel and ceramide. This resulted in nanomedicines that exhibited responsiveness to glutathione (GSH) and demonstrated inhibition of tumor cancer cells and cancer stem cells (CSCs). Our experimental results indicated that the inclusion of anti-CD44 and anti-CD133 antibodies enhanced the targeting capability of nanomedicines towards cancer cells and CSCs in an in vitro study and the accumulation in both normoxic regions and hypoxic niches in in vivo tumor xenografts. The multiprotein-based nanomedicines also demonstrated GSH-dependent drug release behavior, induced apoptosis in cancer cells and CSCs, inhibited cell migration, and effectively suppressed NSCLC tumor growth. Overall, our findings presented a novel nanostructure created from differently shaped proteins for application in drug delivery. This multiprotein-based nanomedicines showed promising potential in addressing the limitations of albumin-based nanomedicines and may offer improved therapeutic outcomes for cancer treatment. Graphical Abstract

Synergistic inhibition of advanced glycation end products and enhancement of flavor by the combination of oligomeric proanthocyanidins and glycated yeast proteins - Jing-jing Fu; Bo-wen Ru; Qi-cheng Zhang; Yu-jun Wu; Hai-yang Feng; Lian-ping Zheng; Yue-wen Chen (Food Research International, 2026)

Green manure co-application boosts arid agroecosystem sustainability: Mixed sowing of feed rape and hairy vetch modulates N input and enzymes for optimized wheat production - Ru Yu; Jie Zhou; Fangdi Chang; Jiashen Song; Jing Wang; Xiaobin Li; Hua Zhang; Jufeng Cao; Xiaohong Li; Hanjiang Liu; Hongyuan Zhang; Yuyi Li (Field Crops Research, 2026)

Molecular epidemiology reveals co-circulation of five Anaplasma species with zoonotic potential in sheep and goats from Henan province, China - Jia-Run Yang; Wei-Hao Tan; Jie-Yue Liang; Jing-Rong Li; Yu-Ru Cao; Wan-Yu Li; Jian-Wei Shao (Comparative Immunology, Microbiology and Infectious Diseases, 2026)

Mg-doped CoCr2O4 nanoparticles with fast humidity sensing and mixed-controlled pseudocapacitive charge storage - K. Manjunatha; Shih-Lung Yu; Yi-En Wu; Ming-Kang Ho; Tsu-En Hsu; Yun-Tai Yu; B. Chethan; Mithun Prakash Ravikumar; Sakar Mohan; Tsung-Te Lin; Yi-Ru Hsu; Meng-Chu Chen; et al. (Chemical Engineering Journal, 2026)

A novel dual-function biosensor based on polarity reversal of MFC for bioelectricity generation and detecting trimethylamine-N-oxide - Sheng-chao Gao; Yu-xuan Wang; Yong-dong Li; Ru-meng Zhang; Ya-nan Zhang; Jin-song Dong; Hong-xia Ni; Yi Chen; Xi-hui Shen; Ying Liu (Chemical Engineering Journal, 2026)

AtGASA1 positively regulates Arabidopsis response to salt stress by suppressing accumulation of reactive oxygen species - Jian-Bo Song; Hao-En He; Cai-Feng Wang; Xian-Zhi Zuo; Zi-Xin Zhao; Ya-Ru Li; Yu-Fan Chen; Shu-Fan Liu; Han-Wen Guo; Xuan Huang (Plant Cell Reports, 2026)

Metabolic-Epigenetic-Immune axis in Ischemic Stroke: Lactate-derived Lactylation as a Key Regulator - Xin-Yu Dong; Xin-Ru Pan; Xiao-Shuang Feng; Jia-Xin Xie; Xiao-Yi Xiong (Metabolic Brain Disease, 2026)

The unique biogenesis pathway of extracellular vesicles in Hirudo nipponia salivary gland cells - Ya-Li Zhu; Meng-Xiang Jia; Ru-Yu Qu; Qian Li; Xia Qiu; Wen-Chen Zhao; Yuan-Yuan Luo (Tissue and Cell, 2026)

Multi-system geochronometer constraints on thermo-tectonic evolution of the Qiangtang Terrane, central Tibetan Plateau: Comment - Xiao-Long Song; Ru-Ye Tian; Kang-Yu Li (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Chlorine-resistant high-entropy spinel oxide catalyst for efficient and durable seawater anion exchange membrane water electrolysis - Thi Xuyen Nguyen; Ting-You Shih; Ngoc Thanh Thuy Tran; Thanh Tuan Nguyen; Yi-Chuan Chu; Bo-Han Lai; Chun-Kuo Peng; Yu-Ru Lin; Yan-Gu Lin; Kao-Shu Chuang; Jeng-Kuei Chang; Thi Y Phung Nguyen; et al. (Chemical Engineering Journal, 2026)

Overexpression of PtrPYL11 enhance drought tolerance in Populus: evidence from genome-wide identification and comparative transcriptome profiling - Shuang-Lian Deng; Shu-Ying Wei; Rui-Quan Wang; Yuan Zhang; Hao Li; Xing-Yu Liu; Xin-Ran Yu; Guan-Ru Ren; Ting Wang; Fang He (Plant Cell Reports, 2026)

Protist‐Bacteria Trophic Interactions Contribute to Higher Community Stability in Subsoils Than Topsoils - Suo Liu; Jingyi Ru; Sihang Deng; Jiesi Lei; Zhencheng Ye; Yu Tang; Changchun Zhai; Shiqiang Wan; Yunfeng Yang (Global Change Biology, 2026)
Climate change is reshaping ecosystem components and functions across soil profiles. In this study, we examined the effects of altered precipitation and nighttime warming on soil microbial communities in both topsoils (0–20 cm in depth) and subsoils (20–50 cm in depth) in a long‐term field experiment in Inner Mongolia, China. Unexpectedly, moisture, belowground net primary production, and NO 3 − content in subsoils were all affected more by climate changes than topsoils. Moreover, using multiple resistance metrics, including α‐diversity, β‐diversity, microbial network complexity, and network robustness, we found that both bacterial and protistan communities in subsoils exhibited greater resistance to climate change than those in topsoils, while fungal communities showed no consistent pattern. Enhanced bacterial resistance in subsoils was associated with lower 16S rRNA gene operon ( rrn ) copy number, reduced GC content, lower genome and cell size, and other oligotrophic traits, collectively supporting adaptation to nutrient‐poor and stressful environments. Protistan resistance in subsoils tracked bacterial resistance and was reinforced by stronger trophic interactions and functional traits such as protective shells, greater motility, and reduced cell size, reflecting a bottom‐up control, as soil protists are primarily phagotrophs shaped by bacterial prey supply. Abundant bacteria enhanced resistance through oligotrophic adaptations and positive intra‐community interactions, while abundant protists reduced resistance, potentially due to the dominance of negative intra‐community interactions. Partial least squares analyses revealed that microbial community resistance modulated soil heterotrophic respiration (R h ), connecting community resistance to carbon cycling. Together, these findings demonstrate that the often‐overlooked resistance of subsoil microbiomes could buffer ecosystem functions under future climate conditions, suggesting that traits (e.g., rrn copy number) and trophic interactions can outweigh diversity for community stability.

Triterpenoids from Ganoderma angustisporum and their α -glucosidase inhibitory activities - Fan-Ru Xu; Le Zhou; Yu-Cheng Dai; Hai-Sheng Yuan; Yu-Xi Wang (Natural Product Research, 2026)

Prioritizing key determinants of hematite photocatalysis through structure – Property contour mapping and statistical correlation analysis - TsingHai Wang; Ching-Lung Chen; Wei-Fan Kuan; Wei-Tong Li; Ching-Yao Ke; Tzu-Han Lin; Chung-Yu Guan; Huei-Ru Fuh (Process Safety and Environmental Protection, 2026)

Overexpression of SlPMEI3 in tomato increased the viscosity of ketchup and juice - Chunyu Liu; Yonghui Zhu; John B. Golding; Penta Pristijono; Yue Guan; Youjian Yu; Yong He; Yongxin Li; Zhujun Zhu; Lei Ru (Plant Science, 2026)

Cyclopentanoid monoterpene glycosides from the aerial parts of Paederia foetida L - Wan-Qi Zhang; Xin-Yue Li; Ming-Hui Sun; Jie Zhou; Guo-Ru Shi; De-Quan Yu; Yan-Fei Liu (Phytochemistry, 2026)

Exploratory analysis of epigenetic dynamics and small extracellular vesicles in Penaeus vannamei hemocytes under inactivated Vibrio parahaemolyticus priming - Yu-Ru Lin; Guan-Lin Lai; Yu-Hsuan Sun; Ta-Jeng Yang; Ting-Yu Huang; Huu-The Nguyen; Muhammad Ar Rozzaaq Nugraha; Novi Rosmala Dewi; Yeh-Fang Hu; Fan-Hua Nan (Journal of Invertebrate Pathology, 2026)

Preparation of indicator cards for freshness detection of rice with four different processing degrees during storage based on olfactory visualization technology - Wan-ru Liu; Yang Yang; Yue Xu; Bing Wang; Guang Zhang; Xin-yu Xu; Yuan-yuan Wang; Chun-min Ma; Na Zhang (Food Chemistry, 2026)

GaAs/GaN-based self-powered catalytic systems driven by tribovoltaic effect enable efficient degradation of azo dyes - Meng-Nan Liu; Yan-Xin Wu; Yu-Tong Sun; Xu Li; Ru Li; Jun Zhang; Yun-Ze Long (Chemical Engineering Journal, 2026)

Synergistic activation of the bioenergetics-apoptosis axis via flavonoids-loaded cascade-targeted biomimetic nanoplatform to overcome cancer metabolic plasticity - Xue Zheng; Yunfan Shao; Xue Gao; Yu Hao; Yanhui Shi; Ru Xie; Miaoqing Zhao (Chemical Engineering Journal, 2026)

Tracking the dynamic changes in vegetation belts in China: spatiotemporal insights into climate and human influences - Yong Xu; Yun-Gui Lu; Qiang-Yu Dai; Wen-Ting Huang; Shang-Chen Zhou; Ru-Long Ma; Wen-Qiang Peng; Yu-Xi Feng (Regional Environmental Change, 2026)

Bridging Aquaculture and Human Medicine: A Comprehensive Review of Zebrafish Models for Chronic Kidney Disease - Feng‐Yi Guo; Hao‐Yu Yang; Lan‐Chen Zhang; Xiang‐Ru Liu; Pan‐Pan Jia; De‐Sheng Pei (Reviews in Aquaculture, 2026)
Chronic kidney disease (CKD) poses a significant global health burden, necessitating robust animal models for mechanistic studies and drug discovery. Zebrafish offers unique advantages as a powerful models in kidney disease, including high‐throughput compatibility, optical transparency, and significant genetic and nephron homology with both humans and farmed teleosts. However, challenges, such as the species' potent regenerative capacity and a lack of standardized diagnostic thresholds, hinder their broad application. This review systematically summarizes four principal induction strategies: environmental stress, nephrotoxic chemical exposure, CRISPR/Cas‐based gene editing, and transgenesis. We further outline a validation pipeline that integrates functional assays, morphometrics, and histopathology, while advocating for cross‐laboratory harmonization. Additionally, we compare risk factors for CKD and CKD of unknown etiology (CKDu), emphasizing environmental contributors. Collectively, we propose zebrafish as a reproducible platform for aquaculture applications, specifically for nephropathy early‐warning systems and functional feed assessment, and for human therapeutic research. These standardized models hold great promise for high‐throughput drug screening and elucidating disease mechanisms, facilitating the translation of findings to both aquaculture and clinical medicine.

Real-time visualization of Nocardia seriolae proliferation and macrophage migration in the Northern snakehead (Channa argus) - Jian Teng; Jian-Ru Liu; Yi-Xiang Zhai; Sheng-Liang Cao; Zhen-Shu Si; Qing-Teng Ren; Xiang-Shan Ji; Mei-Hua Lu; Yu-Bao Li; Yan Zhao (Aquaculture, 2026)

Short-, medium-, and long-chain chlorinated paraffins in sediments from the Pearl River Delta, China: Occurrence, sources, and risks - Fei-Xiang Xie; Yu-Fang Huang; Yong-Hong Zhang; Ya-Hui Xue; Run-Lin Chen; Xiao-Mei Huang; Hong-De Shi; Jia-Hui Huang; Hui-Ru Li (Science of The Total Environment, 2026)

Recyclable Na-Mn-O nanocomposite for dual-modal photothermal/ROS antibacterial therapy against multidrug-resistant bacteria in pathogen-laden wastewater - Zhi-ru Tao; Shu-xian Hou; Yi-mei Wang; Xue-chao Shi; Xin-xin Liu; Jun Ge; Yu-han Ji; Ya-qi Cheng; Zi-yi Leng; Xin-yv Cao; Rong-rong Li; Jin-nan Xuan; et al. (Journal of Water Process Engineering, 2026)

Synergistic one-step pyrolysis of waste coffee grounds and orange peels: A green route to hierarchical porous carbon for high-performance supercapacitors - Yu-Cheng Chang; Shao-Ru Chang (Journal of Environmental Chemical Engineering, 2026)

Lactic acid modulates empty-cup aroma persistence in Baijiu via molecular interaction mechanisms: a case study of strong-aroma and soy-sauce-aroma Baijiu - Qing-Ru Liu; Shun-Hua Zhang; Xiao-Juan Zhang; Zheng-Juan Zhu; Ru-Yi Li; Song-Tao Wang; Jin-Song Shi; Su-Yi Zhang; Cai-Hong Shen; Guan-Yu Fang; Qing-Qing Liu; Yong-Jun Yuan; et al. (Food Chemistry, 2026)

Research on the impact of resident behavior on energy consumption during the heating period of ultra-low energy buildings - Ru-Xi Ding; Jia-Ze Dai; Ying-Nan Zhang; Xiao-Ping Wu; Cong-Han Yu; Zhenfa Fan (Energy and Buildings, 2026)

Energy-saving and fire/water-resistant recyclable aerogel coatings for thermal-insulating polyurethane foam - Cong-Mei Lin; Xue-Lian Chen; Fu-Rong Zeng; Li-Xiao Hao; Yu-Shi Wen; Bing-Ru Zhang; Bo-Wen Liu; Lin Zhang; Hai-Bo Zhao (Chemical Engineering Journal, 2026)

Construction of lignin crosslinked nanocellulose 3D-printed solar evaporators for efficient seawater desalination via hydroxyl-yne click chemistry - Juan Yu; Xinyi Zhu; Ru Guo; Bowen Li; Liqin Jiang; Zhiguo Wang; Yimin Fan (Carbohydrate Polymers, 2026)

Two new clerodane diterpenoids and their anti-inflammatory activity from Callicarpa integerrima - Muhammad Aurang Zeb; Xiao-Ying Ruan; Xing-Jie Zhang; Yu-Tong Xing; Meng-Ru Wang; Yuan-Lin Kong; Xiao-Li Li; Kai Jiang; Wei-Lie Xiao (Natural Product Research, 2026)

The protective effects of alkaloids from Stephania tetrandra S. Moore on H9C2 cardiomyocytes - Yan-nan Ji; Ran Zhou; Zhi-hui Zhang; Xing-ru Gao; Si-qian Yang; Pu-yu Yang; Zi-shan Chen; Jun-li Sha; Jing-yu He; Yue-feng Zhang; Tie-jun Zhang; Yu-cheng Gu; et al. (Natural Product Research, 2026)

Disease outbreaks substantially enhance greenhouse gas emissions from Asian seabass (Lates calcarifer) aquaculture pond - Han-Yang Yeh; Chien-Wei Tu; Yi-Jung Chen; Wen-Ping Cheng; Pei-Yu Shih; Chia-Chia Yu; Wei-Sheng Zhang; Wei-En Hung; Yu-Ru Lin; Zhen Hao Liao; Wen-Chen Chou; Hsiao-Chun Tseng; et al. (Marine Pollution Bulletin, 2026)

Lanthanum-quaternized chitosan-modified zeolite for long-lasting operation of constructed wetland: A bifunctional strategy for simultaneous phosphorus removal and microbial clogging mitigation - Ling Wang; Jian-Guo Zhang; Hong-Yin Sha; Yi-Ru Wang; Hao-Yu Wang; Guang-Can Zhu; Yong-Ze Lu (Water Research, 2026)

Autophagy, ROS, and their interplay in plant adaptive responses - Chi Zhang; Song-Qi Li; Pengwei Jing; Run-Xin Wu; Yu-Qing Ma; Ji-Xiao Wu; Ru-Feng Song; Wen-Cheng Liu (Journal of Plant Physiology, 2026)

Long-term ozone exposure and attention-deficit/hyperactivity disorder symptoms in school-aged children: Findings from a large multi-city study in China - Zhao-Huan Gui; Wan-Ting He; Yun-Ting Zhang; Joachim Heinrich; Michael S. Bloom; Shao Lin; Bin Jalaludin; Mohammed Zeeshan; Lidia Morawska; Tian-Yu Zhao; Shyamali Dharmage; Luke Knibbs; et al. (Journal of Hazardous Materials, 2026)

Reducing the healthcare carbon footprint through fully self-service artificial intelligence-powered screening: A comparative simulation study utilizing data from Shanghai City and Lixin Town, China - Yingyan Ma; Xiyuan Shi; Lina Lu; Yi Xu; Juzhao Zhang; Tao Yu; Yajun Peng; Enren Ke; Senlin Lin; Ru Guo; Haidong Zou (Journal of Cleaner Production, 2026)

Straw interlayer burial improved soil humic fractions via pore-microbe mediated life strategy hierarchy regulating pore structure and bacterial characteristic in saline soils - Hongyuan Zhang; Jiashen Song; Jie Zhou; Fangdi Chang; Ru Yu; Wenhao Feng; Haoruo Li; Jing Wang; Xiaobin Li; Yuyi Li (Journal of Environmental Management, 2026)

Longitudinal monitoring of global prevalence, genomic characterization and transmission routes of Salmonella Derby strains from food, humans and the environment - Min-Ge Wang; Dong-Xiao Ru; Ying-Xin Ruan; Ying Chu; Peng-Yu Zhang; Sheng Chen; Ruan-Yang Sun (Food Research International, 2026)

Sustainable extraction and bioconversion of tea stems using NADES: Dual benefits in polyphenolic recovery and carbohydrates enzymatic hydrolysis - Lin-Kun Sun; Pei-Ru Zhou; Tian Du; Yu-Cang Zhang; Yan-Zhen Zheng (Food Chemistry, 2026)

Built-in electric field and surface adsorption enhanced gas detection of muti-interface MXene/TiO2/Bi2MoO6 integrated heterostructure - Yan Liang; Peipei Yan; Xiaojian Zhao; Chunbo Ru; Lu Tang; Yu Jiang; Yong Yang (Chemical Engineering Journal, 2026)

Dual-dynamic polyimide and its thermally conductive adhesive featuring high glass transition temperature, recyclability, and strong adhesion - Fang Li; Ping Yu; Bin Wu; Ming Cao; Ru Xia; Jiasheng Qian (Chemical Engineering Journal, 2026)

Configurational entropy–induced lattice distortion in high-entropy Prussian blue analogues derived transition metal phosphide accelerates electrocatalytic hydrogen evolution in alkaline media - Yu-Ru Liu; Mia Rinawati; Ping-Chen Shi; Sofiannisa Aulia; Wuttichai Tanmathusorachai; Hsin-Chih Huang; Wei-Nien Su; Ling-Yu Chang; Wei-Hsiang Huang; Min-Hsin Yeh (Chemical Engineering Journal, 2026)

A proposed framework based on traffic volume and the design of a bottom-up methodology to estimate the CO emission of on-road vehicles - Shan-Yi Shen; Ru-Yun Chang; Yun-Wei Liao; Wei-Chun Chou; Yu-Hao Lin; Ping-Yu Liu (Atmospheric Pollution Research, 2026)

Microglial Activation Mediates Drp1-Dependent Mitochondrial Fission and Neuronal Apoptosis in a Lipopolysaccharide-Induced Model of Cognitive Dysfunction - Meng-Jie Chen; Jia-Qi Ning; Jia-Xi Liu; Jian-Sheng Luo; Ru-Yu Yan; Yu-Xuan Yang; Xiang Li; Ling-Ling Ding (Molecular Neurobiology, 2026)

Fluorescent aptasensor based on magnetic bead–assisted displacement reaction for monitoring vancomycin in plasma - Cheng-Shiuan Hsieh; Hsu-Yun Tsai; Ting-Chien Tsai; Yang-Chun Wang; Yi-Tung Cheng; Jing-Ru Liou; Meng-Yu Liu; Yen-Ling Chen; Chien-Chin Chen (Analytica Chimica Acta, 2026)

7,8-Dihydroxyflavone attenuates cisplatin-induced cardiomyocyte apoptosis and mitochondrial dysfunction via the p53/Nrf2 pathway - Zhen Tian; Ting-ting Tan; Yu-wei Hu; Jia-tong Yao; Xiao-ting Kang; Jin-yu Zhou; Dong-xu Jia; Qing-liu Li; Ru-jin Liang; Li-mei Zhao; Hua Zhu; Jing Zhao; et al. (Toxicology and Applied Pharmacology, 2025)

Assessing the atmospheric deposition of inorganic nitrogen and phosphorus over the Yellow Sea - Limin Yu; Ru Li; Chong Zhang; Hao Sun; Zhe Zhang; Pengfei Zhao; Pengji Zhang; Fan Yang (Regional Studies in Marine Science, 2025)

Pathogenic and beneficial microbial communities determine the shelf life of stored 'Fengtangli' plums - Yu-Ru Wang; Tomislav Cernava; Shi-Xian Zeng; Hong Chen; Feng-Quan Liu; Zheng-Qing Fu; Tao Zhou; Yong Wang; Jia Liu (Postharvest Biology and Technology, 2025)

Fluoride species conversion-enhanced selective extraction: A green and safe strategy for fluorine recovery in wet-process phosphoric acid production - Long Yao; Guixuan Shan; Abrar Laiba; Yu Zhao; Yujiao Zhang; Ru’an Chi; Bingwen Long; Wei Li; Jinli Zhang (Journal of Environmental Chemical Engineering, 2025)

Soot characterization of n-dodecane combustion in multi-jet premixed flames: A multi-scale analysis - Xiao-Hong Gui; Jiao-Jiao Wu; Wen-Jun Zhou; Ling-Nan Wu; Kai-Ru Jin; Wen-Jiao Wang; Zhen-Yu Tian (Fuel, 2025)

Interactive effect of various fatty acids and the Maillard reaction of sesame meal enzymatic hydrolysates on aroma generation - Qing-qing Ruan; Bei-bei Hu; Kai-yue Su; Jun-ru Li; Wen-ting Yin; Zi-qi Han; Yu-xin Liu; Xiao-shuang Cai (Food Research International, 2025)

Electrostatic spray drying enhances transferrin hydrophilicity for improved rosmarinic acid binding: Insights into biological activity and molecular mechanism - Ru-yi Zhang; Zhi-shuo Zhang; Ting-ting Tang; Jun-hua Li; Yu-jie Su; Lu-ping Gu; Yan-jun Yang; Cui-hua Chang (Food Chemistry, 2025)

Fermented Broussonetia papyrifera leaves on growth performance, immune responses, and resistance to Vibrio of shrimp - Guan-Lin Lai; Yu-Ru Lin; Ta-Jeng Yang; Yu-Ting Chu; Fan-Hua Nan; Yeh-Fang Hu (Fish & Shellfish Immunology, 2025)

Effects of feed supplementation with fermented Broussonetia papyrifera leaves on non-specific immune responses, resistance to Vibrio parahaemolyticus, growth, intestinal histology, and microbiota of white shrimp (Penaeus vannamei) - Guan-Lin Lai; Yu-Ru Lin; Ta-Jeng Yang; Yu-Ting Chu; Fan-Hua Nan; Yeh-Fang Hu (Fish & Shellfish Immunology, 2025)

Antibiotics, antibiotic resistance genes, and environmental drivers: Assessment of resistance pollution along the Yangtze River Basin - Chengcheng Bu; Chong Chen; Weiwei Zhang; Ru Zhang; Jinpeng Yu; Yu Hua; Haoyu Zeng; Yuchen Han; Ruolan Jia; Qihui Zhao; Yuefei Ruan; Limin Ma (Environmental Pollution, 2025)

Selective energy transfer via chromium clusters for high-performance blue-excitable shortwave infrared phosphors - Shih-En Chen; Kuan-Chun Chen; Chuan-Fang Tsao; Yu-Chieh Huang; Agata Lazarowska; Mikołaj Kamiński; Natalia Majewska; Tadeusz Leśniewski; Grzegorz Leniec; Ewa Mijowska; Ding-Hwa Cherng; Ting-Wei Yeh; et al. (Chemical Engineering Journal, 2025)

Designing light-guiding carriers in microalgal-bacterial systems: From optimization to integration and development perspectives - Cong-Cong Tang; Jin-Qiao Liu; Yong-Qi Cheng; Ya-Ru Hu; Zhang-Wei He; Wen-Qiong Wang; Zhi-Hua Li; Xiaochang C. Wang; Yu Tian (Chemical Engineering Journal, 2025)

Exploring the potential of radar vegetation indices for soil parameters retrieval: a case study of remote sensing soil salinity mapping - Aihepa Aihaiti; Ilyas Nurmemet; Yu Qin; Bilali Aizezi; Yang Xiang; Meimei Zhang; Yixin Zhang; Ru Feng (CATENA, 2025)

Computational-assisted protein engineering to develop thermostable and highly active catalase for industrial and biocatalytic applications - Shuai Xu; Ya-min Chen; Xiang-yu Meng; Ru Pan; Ao-xuan Yan; Zhi-min Li; Zong-lin Li (Bioresource Technology, 2025)

A new norlignan and other compounds from Artemisia frigida Willd - Xin-Ya Dong; Ru-Ya Li; Hong-Xia Tang; Ya-Jie Li; Jun Chen; Jin-Guo Luo; Na Yu; Xiang-Wei Xu; Xu-Dong Zhou (Biochemical Systematics and Ecology, 2025)

Correction: Combining network Pharmacology and metabonomics to explore the mechanism of baicalin inhibiting PRRSV replication - Qin Luo; Yu-xuan Huang; Hai-rui Li; Chang-hong Qiao; Zhen-wen He; Xiang-yu Chen; Xiao-hu Wang; Gang Wang; Meng-meng Zhao; Ru-jian Cai (Veterinary Research Communications, 2025)

Combining network pharmacology and metabonomics to explore the mechanism of baicalin inhibiting PRRSV replication - Qin Luo; Yu-xuan Huang; Hai-rui Li; Chang-hong Qiao; Zhen-wen He; Xiang-yu Chen; Xiao-hu Wang; Gang Wang; Meng-meng Zhao; Ru-jian Cai (Veterinary Research Communications, 2025)

GZR101, a Novel Premixed Insulin for the Treatment of Diabetes Mellitus - Wei Chen; Cheng Cui; Wancai Xing; Yining Zhang; Anshun He; Yue Wang; Yan Huang; Nannan Zhai; Qimin Shi; Fangkai Xue; Yongchun Wang; Jun Zhang; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Impact of vancomycin and Clostridioides difficile on the secretome and pathogenicity of Clostridium innocuum - Yi-Ywan M. Chen; Kun-Yi Chien; Hui-Ru Shieh; Cai-Jie Luo; Yu-Xun Chang; Chuan Chiang-Ni; Chih-Ho Lai; Cheng-Hsun Chiu (Medical Microbiology and Immunology, 2025)

Transcriptome analysis reveals no obvious unintended effects in the spleen of CRISPR/Cas9-mediated CD163 and pAPN double-knockout pigs - Zhi-Guo Liu; Nan Wang; Wan-Jie Wang; Lei Huang; Shun-Shun Chi; Yu-Xin Nie; Mao-Sha Yuan; Ya-Ru Sun; Yu-Lian Mu; Kui Li (Functional & Integrative Genomics, 2025)

High Quality, Granular, Timely, Trustworthy and Efficient Vertebrate Species Distribution Data Across a 30,000 km 2 Protected Area Complex - Yinqiu Ji; Alex Diana; Xueyou Li; Eleni Matechou; Jim E. Griffin; Shuwei Liu; Mingjie Luo; Chunying Wu; Ru Bai; Chenyang Yao; Tingting Yin; Feng Dong; et al. (Ecology Letters, 2025)
The routine generation of species distribution data at scale remains a challenge. We used aquatic environmental DNA metabarcoding to sample vertebrate species across the 30,000 km 2 Gaoligongshan region along the China–Myanmar border. In just 56 calendar days (33 researcher‐field‐days + 69 researcher‐lab‐days), we detected 389 vertebrate species, of which 35 are Red‐Listed. We introduce the ‘eDNA‐aware’ OccPlus occupancy model, which accounts for false‐negative and false‐positive error in the field and lab. OccPlus leverages the taxonomic breadth of eDNA datasets by using ordination to estimate species occupancies. We recover known biogeographic patterns and find that native terrestrial and fish species have higher occupancies inside protected areas while domesticated species and non‐native fishes have higher occupancies outside them. Our study demonstrates how eDNA metabarcoding can obtain high‐quality, granular, timely, trustworthy and efficient species distribution data to facilitate nature conservation and restoration.

Metagenome-assembled genomes reveal Pseudogracilibacillus amylolyticus sp. nov., a functional uncultured microorganism in high-temperature Daqu - Ai-Ping Lv; Ying-Han; Bao-Zhu Fang; Guo-Zheng Wang; Man-Chun Liu; Bing-Ru Bian; Zhuo-Huan Zheng; Kai Li; Bing-Yu Li; Jian-Yu Jiao; Lan Liu; Lei Dong; et al. (Systematic and Applied Microbiology, 2025)

A nonlocal strain gradient higher-order beam theory and its application to wave propagation in radially graded nanotubes - Wei-Li Ma; Peng-Yu Wang; Hui-Ru Cui; Xian-Fang Li (Ocean Engineering, 2025)

Timing of closure of the South Tianshan Ocean: Evidence from a stitching pluton in the Western Tianshan, NW China - Zhi-Hao Jiang; Ru-Xiong Lei; Shi-Bao Wu; Matthew J. Brzozowski; Mingyi Xia; Yuanjun Yu; Chang-Zhi Wu (Journal of Asian Earth Sciences, 2025)

AO168=O at environmentally relevant concentrations induces reproductive toxicity by causing germline apoptosis and cell cycle arrest in Caenorhabditis elegans - Yuxing Wang; Luyao Gu; Simin Li; Ru Liu; Tong Meng; Yue Yu; Rong Ye; Houhu Zhang; Rong Zhou; Yuanqing Bu (Environmental Research, 2025)

A Li-ion permeable poly(phenylene ether-ether-sulfone) interphase to address interfacial instability and structural degradation of Ni-rich NCM cathodes in poly(ethylene oxide)-based all-solid-state Li-ion batteries - Cheng-Hung Liao; Yu-Ting Weng; Senthil-Kumar Parthasarathi; Hsi Chen; Shu-Jui Chang; Guan-Yi Liu; Tsung-Yu Yu; Chih-Wen Pao; Ting-Shan Chan; Wei-Tsung Chuang; Chun-Chieh Wang; Ru-Jong Jeng; et al. (Chemical Engineering Journal, 2025)

Inspired by traditional printing pastes: Green eco-design of phytic acid-modified starch and durable flame-retardant cellulose-based fabrics - Wan-Meng Song; Bao-Hong Wang; Ru-Yu Fan; Yun Liu; Yu-Zhong Wang (Chemical Engineering Journal, 2025)

Foam dust suppressant based on synergistic coordination between oxidized starch-gelatin Schiff base reaction and multiple crosslinking - Xinyue Zhang; Ru Wang; Haiming Yu; Jiayin Wang; Haochun Ma (Carbohydrate Polymers, 2025)

Temporal variability of greenhouse gas fluxes in monoculture of tilapia in ponds - Yi–Jung Chen; Han–Yang Yeh; Chien-Wei Tu; Yu-Ru Lin; Zhen Hao Liao; Wen-Chen Chou; Hsiao-Chun Tseng; Ruei-Feng Shiu; Tzu-Ning Teng; Meng–Chou Lee; Fan–Hua Nan (Aquaculture International, 2025)

Chemical constituents isolated from leaves of seashore plant Aglaia rimosa - Jing-Ru Weng; Jui-Hsin Su; Ping-Jyun Sung; Wei-Yu Lin; Zhen-Hong Han; You-Ying Chen; Chun-Lin Chen (Phytochemistry Letters, 2025)

Effects of curcumin on jejunal morphology and intestinal integrity of broiler under heat stress - Ding-Ding Zhang; Meng-Ru Xue; Yu-Ting Liu; Hong-Jie Cui; Ding-Ping Bai (Journal of Thermal Biology, 2025)

LSPR-enhanced hydrogen evolution via Au-UiO-67-NH2/ZnIn2S4/MoS2 hybrid nanostructures - Jing Ru; Kang Li; Guofeng Sun; Maoxia Chen; Yu Hu; Zhiguo Wen; Dongyu Wu; Xuan Yi; Zhenbin Chen; Bin Wang (Journal of Environmental Chemical Engineering, 2025)

Nano architectonics via in situ growth of MIL-101(Fe) on modified sugarcane bagasse for selective capture of glyphosate from aqueous solution - Ru-yi Zhou; Ming-hua Liu; Yun Xiao; Yu Qin; Bo Zuo; Muhammad Akhtar Abbas; Jun-xia Yu; Xiao-di Li; Yue-fei Zhang; Ru-an Chi (Journal of Environmental Chemical Engineering, 2025)

Sequential fermentation with Kluyveromyces marxianus and yogurt starter cultures produces stirred fermented milk with reduced lactose and enhanced natural flavor - Yu-Ting Feng; Yan-Ru Zhou; Chang-Cheng Li; Shu-Jun Guo; Zhen-Peng Gao; Chun-Feng Guo (Innovative Food Science & Emerging Technologies, 2025)

Structural characterization, interaction mechanism and thermal stability of dual-fibrous complexes formed by rice glutelin fibrils and cellulose nanocrystals - Yi-Xuan Jiang; Ya-Ru Wang; Qin Yang; Xiao-Hong Yu; Han-Qing Chen (Food Chemistry, 2025)

The threat of microplastics to human kidney health: Mechanisms of nephrotoxicity and future research directions - Ru-Yu Tan; Qin-Ying She; Yun-Ci Ma; Ming-Hong Liu; Li-Juan Li; Li-Li Huang; Yi-Wen Zhong; Hui-Xin Bi (Environmental Research, 2025)

Polycyclic aromatic hydrocarbon aggravates high-fat diet-induced metabolic dysfunction-associated steatotic liver disease through disturbing hepatocyte sphingolipid metabolism - Hui-Ru Kuo; Yu-Fen Chung; Li-Ting Wang; Chih-Wen Wang; Shih-Hsien Hsu; Li-Chen Chen; Ming-Hong Lin; Shau-Ku Huang; Kwei-Yan Liu (Environmental Pollution, 2025)

Genetic burden and multidimensional predictors in prenatal diagnosis of fetal congenital diaphragmatic hernia - Ruibin Huang; Fang Fu; Shanshan Mei; Liyuan Liu; Wei Zhong; Jin Han; Qiuxia Yu; Hang Zhou; Chunling Ma; Li Zhen; Min Pan; Qiong Deng; et al. (Human Genetics, 2025)

Subsurface organic ameliorant is beneficial in reducing inorganic carbon loss and improving carbon sequestration in saline soils - Ru Yu; Jiashen Song; Jie Zhou; Fangdi Chang; Xiaobin Li; Jing Wang; Haoruo Li; Xia Zhang; Hua Zhang; Yuexin Zhang; Hongyuan Zhang; Yuyi Li (Applied Soil Ecology, 2025)

A selenium nanozyme: Light/mercury dual-enhanced oxidase mimicry for simultaneous ultra-sensitive detection and efficient removal of mercury ions, and superior photocatalytic bacterial disinfection - Yu Shi; Dong-hui Li; Chi Zhang; Zheng-ren Wang; Yi-ran Wang; Ru-kang Chen; Yen-ho Chu; Yu-gang Shi; Rammile Ettelaie; Qing Gu (Water Research, 2025)

Green manure roots return drives saline-alkali soil organic carbon accumulation via microbial necromass formation - Fangdi Chang; Hongyuan Zhang; Peiyi Zhao; Na Zhao; Jiashen Song; Ru Yu; Jing Wang; Xiquan Wang; Dongxun Han; Xiaodong Liu; Jie Zhou; Yuyi Li (Soil and Tillage Research, 2025)

Integrating machine learning and metabolomics to uncover new biomarkers for predicting pesticide exposure among patients with kidney function decline - Junne-Ming Sung; Yu-Chi Hung; Wan-Ru Wang; Chiau-Jun Chu; Yen-Ping Lin; Kuan-Hung Liu; Trias Mahmudiono; Hsiu-Ling Chen (Science of The Total Environment, 2025)

Molecular characterization and optical properties of methanol-soluble brown carbon chromophores in a metropolitan area of northeastern Asia - Yu-Chieh Ting; Yi-Ru Ko; Yueh-Ling Hung; Cheng-Hua Ma; Cheng-Chih Hsu; Yu-Hsiang Cheng (Science of The Total Environment, 2025)

First experiment using post-accelerated unstable ion beams at BRIF: angular distribution of the 21 , 22 Na elastic scattering from doubly magic 40 Ca - Wei Nan; Bing Guo; Cheng-Jian Lin; Dan-Yang Pang; Lei Yang; Dong-Xi Wang; Guo Yang; Yang-Ping Shen; Bing Tang; Qi-Wen Fan; Yi-Wen Bao; Lei Cao; et al. (Science Bulletin, 2025)

Arabidopsis HSFA1b functions as a heat sensor inhibiting OST1-mediated stomatal closure through its adenylate-cyclase activity - Yu Zhang; Ru-Feng Song; Xiao-Yu Hu; Hui Zhou; Wei Wang; Junli Zhang; Xin Zhang; Liu-Mei Li; Su-Ting Wang; Yuwei Song; Fuyou Xiang; Jingjing Xing; et al. (Molecular Plant, 2025)

Integrating morphology, ecology, and genomics: Unraveling the population genetic and evolution within the Rosa graciliflora complex - Jia Miao; Liang-Ying Li; Zhen-Long Liang; Yu Feng; Cheng Zhang; Shi-Qi Li; Heng-Ning Deng; Jian Ru; Zhong-Yu Tang; Xin-Fen Gao (Molecular Phylogenetics and Evolution, 2025)

Genomic analysis of Pseudoalteromonas sp. SD03 reveals its potential in chitin hydrolysis - Yu-Xuan Jiang; Wen-Yue Xu; Hui Liu; Si-Qi Lin; Sha-Sha Liu; Xi-Ying Zhang; Yan-Ru Dang (Marine Genomics, 2025)

Cross-view geo-localization with panoramic street-view and VHR satellite imagery in decentrality settings - Panwang Xia; Lei Yu; Yi Wan; Qiong Wu; Peiqi Chen; Liheng Zhong; Yongxiang Yao; Dong Wei; Xinyi Liu; Lixiang Ru; Yingying Zhang; Jiangwei Lao; et al. (ISPRS Journal of Photogrammetry and Remote Sensing, 2025)

Insight into the effect of ammonia doping on the methane jet flame - Bipro Gain; Muhammad Bilal; Yun-Fan Wang; Samuel Daniel; Wang Du; Ahmed E. Mansy; Kai-Ru Jin; Zhen-Yu Tian (Fuel, 2025)

Comparison of hydroxylated flavonoids and their interaction with protein-based carriers - Zhi-Yuan Yang; Shan-Dan Zhao; Yu-Ru Wu; Qian Zhou; Wei Wang; Yi-Bin Zhou; Kang Liu (Food Chemistry, 2025)

Integration of human sensory evaluation, intelligent E-tongue/E-nose systems, microbiomics, and metabolomics to comprehensively analyze flavor characteristics and dietary improvement mechanisms of processed Buddha's hand fruit - Zi-Xuan Ding; Yue-Hua Chen; Jia-Nuo Zhang; Wen-Yu Wang; Xin-Ru Zhang; Rui-Bo Sun; Hui Zhang; Ming Xie; Hui-Peng Song (Food Bioscience, 2025)

Multispectral analysis and molecular docking simulation of the inhibition mechanism of dietary anthocyanins on acetylcholinesterase - Nuo Wang; Min Zhao; Yue Li; Hao-Yu Xue; Xu Si; Chi Shu; Ying Zhou; Bao-Ru Yang; Sergey S. Makarov; Anton I. Chudetsky; Liang Wang; Ying He; et al. (Food Bioscience, 2025)

Electrocatalytic synergistic degradation of tetracycline by low-energy-consumption Mn0.22-NiS nanosheet electrodes: Interface mechanism and toxicity analysis - Fan-Hao Hu; Qun-Feng Ye; Si-Ru Chen; Ya-Wen Yu; Hao Chen; Su-Fang Qin; Le-Xing You; Xiao-Chun Tian; Feng Zhao (Chemical Engineering Journal, 2025)

Hafnium metal-organic frameworks coupling with DNAzyme-driven bipedal DNA walkers as dual-mode aptasensing platform for sensitive detection of ochratoxin A - Zhuangzhuang Ru; Jingui Chen; Luyang Lv; Ning Gao; Xiang Ren; Yu Du; Lei Yang; Qin Wei (Chemical Engineering Journal, 2025)

Overcoming the bottleneck in one-electron reduction of CO2 with mechanical energy-driven triboelectric plasma-enabled catalysis - Qinglong Ru; Bao Zhang; Sumin Li; Jiao Wang; Wei Jiang; Nannan Liu; Hui Hu; Yongcui Yang; Taifeng Liu; Qianhong Gao; Yifei Zhu; Yu Jia; et al. (Chemical Engineering Journal, 2025)

Endothelial Cell Integrin α6 Regulates Vascular Remodeling Through the PI3K/Akt-eNOS-VEGFA Axis After Stroke - Bing-Qiao Wang; Yang-Ying Duan; Mao Chen; Yu-Fan Ma; Ru Chen; Cheng Huang; Fei Gao; Rui Xu; Chun-Mei Duan (Neuroscience Bulletin, 2025)

Architectural features and antioxidative biofunctionality of a novel pectin from Angelica keiskei Koidz - Si-Ru Chen; Yu-Ru Zhu; Li-Ting He; Hong-Liang Sun; Jing Huang; Yan-Zi Yang; Hua-Jun Zhao; Bo Yang; Meng-Xia Yan (Natural Product Research, 2025)

Orchard variable rate spraying method and experimental study based on multidimensional prescription maps - Chenming Hu; Yu Ru; Shuping Fang; Zifan Rong; Hongping Zhou; Xianghai Yan; Mengnan Liu (Computers and Electronics in Agriculture, 2025)

Avian reovirus induces autophagy-mediated cargo of progeny viruses to extracellular vesicles and enhancement of virus release - Chao-Yu Hsu; Wei-Ru Huang; I.-Hsun Chiang; Jyun-Yi Li; Muhammad Munir; Hung-Jen Liu (Veterinary Microbiology, 2025)

Oncolytic avian reovirus regulates the TLR3-IRF3-IFN-γ-JAK-STAT1 and TLR3-NF-κB-IFN-γ-JAK-STAT1 pathways inducing autophagy in murine melanoma cells - Chao-Yu Hsu; Zi-Yang Lo; Yi-Ying Wu; Wei-Ru Huang; Tz-Chuen Ju; Kuo-Pin Chuang; Lon-Fye Lye; Muhammad Munir; Hung-Jen Liu (Veterinary Microbiology, 2025)

Subgenual anterior cingulate cortex functional connectivity abnormalities in depression: insights from brain imaging big data and precision-guided personalized intervention via transcranial magnetic stimulation - Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Zi-Han Wang; Hui-Xian Li; Yi-Fan Liao; Daniel M. Blumberger; Francisco Xavier Castellanos; Eduardo A. Garza-Villarreal; Li-Ping Cao; Guan-Mao Chen; et al. (Science Bulletin, 2025)

Improved antifouling and regeneration capability of polyaniline-modified halloysite nanotube/MXene composite membranes - Jing-Yi Feng; Wen-Hao Geng; Ru-Yu Chang; Yu-Han Wang; Yue-Xin Wang; Ze-Long Bao; Wen-Yi Sun; Lu-Yao Tian; Di Zhang; Hong-Zhang Geng (Journal of Water Process Engineering, 2025)

Spatial distribution, phase partitioning, and ecological risk assessment of typical pesticides in Yangtze River Basin - Chengcheng Bu; Chong Chen; Xitong Fu; Weiwei Zhang; Ru Zhang; Yu Hua; Ruolan Jia; Yuefei Ruan; Kenneth Mei Yee Leung; Limin Ma (Journal of Hazardous Materials, 2025)

Thermophilic degradation of sulfamethazine by Geobacillus sp. S-07: pathway and mechanism - Ting Pan; Yan-Yan Zhou; Xu Huang; Jian-Xin Xu; Xiao-Yu Guo; Jian-Qiang Su; Hu Li; Xiao-Ru Yang (Environmental Research, 2025)

Integrative transcriptome and metabolome analyses provide insights into rice defence against Chilo suppressalis oviposition - Chen Shen; Haibo Bao; Zhengping Yu; Xiaoyan Cang; Ru Zhang; Junxian Song; Guanghua Luo; Jichao Fang (Plant Molecular Biology, 2025)

Combined genome and transcriptome provides insight into the genetic evolution of an edible halophyte Suaeda salsa adaptation to high salinity - Bing Cui; Ranran Liu; Qiong Yu; Jianrong Guo; Xihua Du; Zixin Chen; Chenyang Li; Tong Wang; Ru Liu; Rui He; Congcong Song; Yue Liu; et al. (Molecular Ecology, 2025)
Suaeda salsa L. is a typical halophyte with high value as a vegetable. Here, we report a 447.98 Mb, chromosomal‐level genome of S. salsa , assembled into nine pseudomolecules (contig N50 = 1.36 Mb) and annotated with 27,927 annotated protein‐coding genes. Most of the assembled S. salsa genome, 58.03%, consists of transposable elements. Some gene families including HKT1 , NHX , SOS and CASP related to salt resistance were significantly amplified. We also observed expansion of genes encoding protein that bind the trace elements Zn, Fe, Cu and Mn, and genes related to flavonoid and α‐linolenic acid metabolism. Many expanded genes were significantly up‐regulated under salinity, which might have contributed to the acquisition of salt tolerance in S. salsa . Transcriptomic data showed that high salinity markedly up‐regulated salt‐resistance related genes, compared to low salinity. Abundant metabolic pathways of secondary metabolites including flavonoid, unsaturated fatty acids and selenocompound were enriched, which indicates that the species is a nutrient‐rich vegetable. Particularly worth mentioning is that there was no significant difference in the numbers of cis ‐elements in the promoters of salt‐related and randomly selected genes in S. salsa when compared with Arabidopsis thaliana , which may affirm that plant salt tolerance is a quantitative rather than a qualitative trait in terms of promoter evolution. Our findings provide deep insight into the adaptation of halophytes to salinity from a genetic evolution perspective.

Spatiotemporal distribution and priority assessment of steroids in the estuarine environment: Implications for environmental risk management - Ru Xu; Nian-Nian Wu; Shan Liu; Hui Chen; Qin-Wei Hao; Yong-Xia Hu; Bing Hong; Shen Yu; Xiang-Rong Xu (Marine Pollution Bulletin, 2025)

Antiviral prenylated C6–C3 derivatives containing a methylenedioxyl group from the roots of Illicium brevistylum - Jing-Yu Zhang; Qian-Ru Wang; Hui-Lin Yang; Rong-Mei Gao; Mi Li; Jia Yang; Yu-Huan Li; Li Li; Shuang-Gang Ma (Phytochemistry, 2025)

Identification of major fungal diseases in sorghum and screening of broad-spectrum resistance germplasms in Southwest China - Zhi-Fan Yu; Yam Bahadur Kami; Jing-Yang Xia; Xin-Ya Chang; Jin-Yang Li; Jun-Ru Han; Jun Lin; Yuan-Tao Sun; Li-Cheng Wang; Xian-Lin Ni; Wen-Ming Wang; Ji-Wei Zhang (Physiological and Molecular Plant Pathology, 2025)

Explore the synergistic effects of Lactobacillus plantarum fermentation and tea polyphenols on the deodorization of egg white powder from the perspective of protein site competition - Ru-yi Zhang; Yan-jun Yang; Wei-jian Zhang; Jun-hua Li; Yu-jie Su; Lu-ping Gu; Cui-hua Chang (Food Chemistry, 2025)

The role of quorum sensing effector ComA in regulating biofilm formation and surfactin production in Bacillus subtilis ASAG 010 - Ru Jia; Yu Wang; Huachao Wang; Xiao Ji; Faizan Ahmed Sadiq; Xu Wang; Guohua Zhang (Food Bioscience, 2025)

Schiff base crosslinking based dialdehyde-chitosan/gelatin/tea polyphenol electrospun nanofibrous membranes with excellent antibacterial and antioxidant activity for food packaging - Yu Ma; Ru Tian; Yudong Song; Mengxiao Liu; Jie Li; Zhichun Bi; Hui Huang; Yongxin Li (Food Packaging and Shelf Life, 2025)

Unveiling a new hemocyte subpopulation in white shrimp (Penaeus vannamei) and the characterization of immune response in hemocyte subpopulation - Novi Rosmala Dewi; Ari Widodo; Muhammad Ar Rozzaaq Nugraha; Min-Da Yang; Ta-Jeng Yang; Yu-Ru Lin; Yeh-Fang Hu (Fish & Shellfish Immunology, 2025)

The effects of the 2D aligned fibers on the fracture properties of steel fiber reinforced cementitious composite slab: Simulation and experimental validation - Kelai Yu; Yu Hu; Ru Mu; Peng Xing; Nan Zhao; Longbang Qing (Engineering Structures, 2025)

Unraveling the crucial role of Al distribution in ordered mesoporous silica for ultra-stable CO2 adsorption - Xu Li; Xiangyu Li; Ru Feng; Miaomiao Tan; Yu Feng; Mengmeng Wu; Weiren Bao; Liping Chang; Jiancheng Wang (Chemical Engineering Journal, 2025)

Multi-scale characteristics and statistically associated factors of ozone pollution in Hangzhou based on machine learning - Yu-ting He; Tao Ding; Ru Yi; Yuan-yuan Wang; Yi Fu; Cheng-kai Tu; Hong-yan Fang; Jin-ye Li; Ming Zhang (Atmospheric Pollution Research, 2025)

Gelatin based preservation technologies on the quality of food: a comprehensive review - Qingfang Ying; Shengnan Zhan; Haixia Yu; Jihua Li; Ru Jia; Huamao Wei; Eugeni Roura; Xinle Tan; Zhaohui Qiao; Tao Huang (Critical Reviews in Food Science and Nutrition, 2025)

Delineate the unknown aquifer geometry and boundary condition using hydraulic tomography - Mpendulo Mangaliso Mtsetfwa; Zaiyong Zhang; Chengcheng Gong; Hong-Ru Lin; Jet-Chau Wen; Yu-Li Wang (Journal of Hydrology, 2025)

How does digital industry agglomeration drive carbon peaking and carbon neutrality in China? The role of digital technology innovation - Ru-Yu Xu; Ke-Liang Wang (Journal of Cleaner Production, 2025)

Co-encapsulation and stability evaluation of myricetin and epicatechin in the oxidized starch-coated edible dock protein hydrogels - Si-Qi Li; Zhi-Yuan Yang; Ming Yang; Wei Wang; Yu-Ru Wu; Yi-Bin Zhou; Kang Liu (Food Hydrocolloids, 2025)

Overcrowded steric engineering of through-space interactions for anti-quenching multi-resonance TADF materials - Ru-Jia Wang; Fan Zheng; Jie Hu; Yu-Lan Wu; Xiao-Long Liu; Jia-Xiong Chen; Longjiang Xing; Qiao-Er Wu; Yanping Huo; Wen-Cheng Chen (Chemical Engineering Journal, 2025)

Efficient catalyst-free CO2 reduction by CO2— radical anions at gas–liquid interface under ambient conditions - Nannan Liu; Qinglong Ru; Wei Jiang; Hui Hu; Yongcui Yang; Kailan Ma; Zuliang Du; Yu Jia; Xiaojing Yang; Bao Zhang; Gang Cheng (Chemical Engineering Journal, 2025)

Chemical constituents from the aerial parts of Clematis peterae - Pan-Pan Yu; Meng-Ya Chen; Ya-Ru Wu; Yong-Qi Guo; Ying-Zhen Tang; Zi-Han Zhu; Yang-Yang Ma; Shi-Hui Qian; Nan Yao; Zhen-Lin Li (Biochemical Systematics and Ecology, 2025)

Effects of combined exposure to polyethylene and oxidized polycyclic aromatic hydrocarbons on growth, development, and neurobehavior in Zebrafish - Yu Liu; Yujun Ning; Yi Jiang; Yiquan Ou; Xiaobing Chen; Chiting Zhong; Ru Wang; Zhibo Zhang; Kongfan Wang; Dingxin Long; Weichao Zhao (Aquatic Toxicology, 2025)

Mitigating low-temperature frost damage in Taiwan high-altitude tea cultivation: physiological insight and protective strategies - Po-Heng Chen; Ru-Hong Lin; Chui-Feng Chiu; Yu-Sheng Lin (Planta, 2025)

Study on the mechanical genesis mechanism and reservoir-controlled pattern of strike-slip fault pressure-ridge structures in the Shunbei Area, Tarim Basin - Zhixing Ru; Xinjing Yu; Yingtao Li; Huabiao Qiu; Shuang Liu (Carbonates and Evaporites, 2025)

Using unmanned aerial vehicle monitoring for the landslide and dammed lake: a case study of the Xiuluan area in Taiwan - Che-Hsin Liu; Jui-Yi Ho; Horn-Ru Liao; Shih-Chiang Lee; Naoki Sakai; Chen-Yu Chen; Chih-Hsin Chang (Bulletin of Engineering Geology and the Environment, 2025)

A tongue resistance training program improves strength, endurance, and swallowing in frail older adults with mild cognitive impairment: a double-blind randomized controlled trial - Shu-Hua Kao; Ruey Chen; Pi-Yu Su; Kondwani Joseph Banda; Chien-Mei Sung; Chia-Hui Wang; Kai-Jo Chiang; Melati Fajarini; Kuei-Ru Chou (GeroScience, 2025)

Analysis of Wind–Wave Relationship in Taiwan Waters - Kai-Ho Cheng; Chih-Hsun Chang; Yi-Chung Yang; Yu-Hao Tseng; Chung-Ru Ho; Tai-Wen Hsu; Dong-Jiing Doong (Journal of Marine Science and Engineering, 2025)
The relationship between wind and waves has been extensively studied over time. However, understanding the local wind and wave relationship remains crucial for advancing renewable energy development and optimizing ocean management strategies. This study used wind and wave data collected by the ten weather buoys in the waters surrounding Taiwan to analyze regional sea states. The relationship between wind speed and significant wave height (SWH) was examined using regression analysis. Additionally, machine learning techniques were employed to assess the relative importance of features contributing to SWH growth. The regression analysis revealed that SWH in the waters surrounding Taiwan was not fully developed, with notable discrepancies observed between the waters east and west of Taiwan. According to the power law formula describing the relationship between wind speed and SWH, the eastern waters exhibited a larger prefactor coupled with a smaller scaling exponent, while the western waters manifested a converse parametric configuration. Through an evaluation of four machine learning algorithms, it was determined that wind speed is the most influential factor driving these regional differences, especially in the waters west of Taiwan. Beyond wind speed, air pressure or temperature emerged as the secondary feature factor governing wind–wave interactions in the waters east of Taiwan.

Poly (sodium acrylate-acrylamide) hydrogels for enrichment and purification of microalgal biomass in an open system: performance optimization and mechanistic analysis - Cong-Cong Tang; Yong-Qi Cheng; Sheng-Long Chen; Ya-Ru Hu; Zhang-Wei He; Zhi-Hua Li; Yu Tian; Xiaochang C. Wang (Journal of Environmental Management, 2025)

Collagenases from hepatopancreas and muscle of Litopenaeus vannamei: Purification, characterization and comparison of their behaviors in collagen degradation - Xu-Chen Xiao; Jia-Yin Huang; Yu-Lei Chen; Kai-Yuan Cao; Ru-Qing Yang; Duan-Quan Lin; Shu-Jun Hong; Yu-Ting Yang; Min-Jie Cao (Food Chemistry, 2025)

Effects of proteolysis pretreatment on the formation, structural changes and emulsifying properties of rice glutelin amyloid-like fibrils - Yi-Xuan Jiang; Ya-Ru Wang; Qin Yang; Xiao-Hong Yu; Han-Qing Chen (Food Chemistry, 2025)

Electrospun nanofiber membranes based on dialdehyde pullulan polysaccharide and schiff base crosslinked lysozyme for antibacterial packaging of blueberries - Yu Ma; Ru Tian; Yudong Song; Chenghui Yin; Hui Huang; Yongxin Li (Food Bioscience, 2025)

Development of a shear strengthening conductive hydrogel for impact protection and distress signal emission - Juan Tan; Xi Li; Chuan Ru Zheng; Anna Tan; Xiu Chen Li; Hai Liang Ni; Wen Hao Yu; Yue Feng Bai; Ping Hu; Hong Mei Chen (Chemical Engineering Journal, 2025)

Targeted restoration of endothelial hypoxic response prevents angiogenic bone loss against liver fibrosis - Nan Zhang; Sheng-Feng Bai; Jia-Ning Liu; Xin Huang; Lu Liu; Yu-Ru Gao; Si-Qi Ying; Chen-Xi Zheng; Hao-Kun Xu; Ji Chen; Xiao Lei; Yu-Bo-Han Zhang; et al. (Chemical Engineering Journal, 2025)

Synthesis of hollow HC-Ni0.96S@MXene/C nanobox as advanced anode for lithium-ion and sodium-ion battery - Song-Yi Liao; Jing Chen; Dao-Ren Deng; Cai-Yun Wu; Selina X. Yao; Yi Wang; Yu-Ming Ru; Xiao-Yan Li; Xu-Gang Shu; Yong-Gang Min (Chemical Engineering Journal, 2025)

Synergistic modulation of electronic structure in high entropy perovskite oxide for enhanced bifuntional oxygen evolution/reduction reactions and its mechanistic insights via in-situ analyses and density functional theory calculation - Thi Xuyen Nguyen; Chih-Heng Lee; Jun-Hong Sun; Chun-Kuo Peng; Wen-Hui Chu; Hamed Pourzolfaghar; Yu-Ru Lin; Muhammad Ghufron; Yuan-Yao Li; Yu-Hao Chang; Yan-Gu Lin; Hsin-Yi Tiffany Chen; et al. (Chemical Engineering Journal, 2025)

Corrigendum: Deciphering the influence of dietary synbiotics in white shrimp gut and its effects in regulating immune signaling pathways - Sofia Priyadarsani Das; Zaenal Abidin; Huai-Ting Huang; Yu-Ru Lin; Chih-Yang Huang; Yu-Sheng Wu; Yeh-Fang Hu; Fan-Hua Nan (Frontiers in Marine Science, 2025)

First report of Stagonosporopsis pogostemonis causing the fruit rot disease of Capsicum annuum L. in China - Mengting Zou; Banlop Leelahasilp; Ming-Rong Chen; Yu-Ru Wang; Yong Wang (Crop Protection, 2025)

First report of Botryosphaeria wangensis, Colletotrichum nymphaeae, Diaporthe eres, and Geotrichum candidum causing postharvest fruit rot of plums (Prunus salicina) in China - Yu-Ru Wang; Bo-Ying Huang; Hafiz Muhammad Usman; Khadija Javed; Fatimah Al-Otibi; Kevin D. Hyde; Yong Wang (Crop Protection, 2025)

Preparation and epitope identification of a novel monoclonal antibody against 3A protein of Senecavirus A - Xiang-hui Ling; Biao Zhang; Hao-jie Ren; Ming-yang Li; Shun-da Liu; Meng-ru Luo; Ke-wei Guo; Shi-chong Han; Wen-rui He; Gai-ping Zhang; Yu-hang Zhang; Bo Wan (Veterinary Microbiology, 2025)

Repeated measurements of urinary bisphenol A and its analogues in relation to sperm DNA damage - Yang-Juan Li; A-Xue Liu; Jia-Yue Zeng; Yu Miao; Min Zhang; Xiao-Ying Liu; Wu Yang; Ru-Cheng Li; Jin-Qin Zhu; Chang-Jiang Liu; Qiang Zeng (Journal of Hazardous Materials, 2025)

Metallization-mediated charge transfer in cocrystals for efficient photocatalytic decontamination of mustard-gas simulant - Li Zhang; Xiao-Lin Liu; Chen Sun; Yu-Ting Luo; Qiang Shi; Ru-Ping Liang; Jian-Ding Qiu (Journal of Environmental Chemical Engineering, 2025)

Construction and application of antimicrobial ultrafiltration membranes based on electro-stimulated hollow mesoporous carbon spheres and carbon nanotubes - Ru-Yu Chang; Wen-Hao Geng; Li-Chao Jing; Jing-Yi Feng; Yue-Xin Wang; Peng-Fei Qian; Ze-Long Bao; Wenyi Wang; Di Zhang; Hong-Zhang Geng (Journal of Environmental Chemical Engineering, 2025)

Granitoid genesis and related rare metal mineralization of the Shihuiyao Rb–Ta–Nb deposit in the Southern Great Xing’an Range, NE China - Shi-Heng Bai; Yu Huang; Zhi-Jie Feng; Matthew J. Brzozowski; Yao-Hui Jiang; Ru-Xiong Lei; Chang-Zhi Wu (Gondwana Research, 2025)

Metal-organic coordinated self-assembled nanomedicine for enhanced cuproptosis-mediated chemo-photo-chemodynamic synergistic therapy of non-small cell lung cancer - Ru-Gui Liu; Rui-Rui Zhao; Zi-Wei Yu; Feng-Juan Liu; Chun-Zhao Liu; Xiao Wu (Chemical Engineering Journal, 2025)

Protective role of Tongxinluo in mitigating myocardial fibrosis in mice with acute myocardial infarction via neuregulin-1 upregulation and Inhibition of endothelium-interstitial transition - Zhen Li; Yu-jie Yin; Ya-ru Wei; Yi Liu; Ning-xin Han; Xiao-qi Wang; Yuan-jie Hao; Ya-fen Wang; Yun-long Hou; Zhen-hua Jia (Journal of Molecular Histology, 2025)

Leveraging Deep Learning to Extract Raindrop Size Gamma Distribution Parameters from Wind Profile Radar Data - Yu Huang; Zhiqun Hu; Lin Li; Ru Zhou; Xu Lu; Mengyu Huang (Journal of Meteorological Research, 2025)

Associations between lifestyle factors, physiological conditions, and epigenetic age acceleration in an Asian population - Yu-Ru Wu; Wan-Yu Lin (Biogerontology, 2025)
Epigenetic clocks use DNA methylation (DNAm) levels to predict an individual’s biological age. However, relationships between lifestyle/biomarkers and epigenetic age acceleration (EAA) in Asian populations remain unknown. We here explored associations between lifestyle factors, physiological conditions, and epigenetic markers, including HannumEAA, IEAA, PhenoEAA, GrimEAA, DunedinPACE, DNAm-based smoking pack-years (DNAmPACKYRS), and DNAm plasminogen activator inhibitor 1 level (DNAmPAI1). A total of 2474 Taiwan Biobank (TWB) individuals aged between 30 and 70 provided physical health examinations, lifestyle questionnaire surveys, and blood and urine samples. Partial correlation analysis (while adjusting for chronological age, smoking, and drinking status) demonstrated that 29 factors were significantly correlated with at least one epigenetic marker (Pearson’s correlation coefficient | r |> 0.15). Subsequently, by exploring the model with the smallest Akaike information criterion (AIC), we identified the best model for each epigenetic marker. As a DNAm-based marker demonstrated to predict healthspan and lifespan with greater accuracy, GrimEAA was also found to be better explained by lifestyle factors and physiological conditions. Totally 15 factors explained 44.7% variability in GrimEAA, including sex, body mass index (BMI), waist-hip ratio (WHR), smoking, hemoglobin A1c (HbA1c), high-density lipoprotein cholesterol (HDL-C), creatinine, uric acid, gamma-glutamyl transferase (GGT), hemoglobin, and five cell-type proportions. In summary, smoking, elevated HbA1c, BMI, WHR, GGT, and uric acid were associated with more than one kind of EAA. At the same time, higher HDL-C and hemoglobin were related to epigenetic age deceleration (EAD). These findings offer valuable insights into biological aging.

Exploring the multifaceted roles of histone deacetylase inhibitor vorinostat in the cell growth, mycelial morphology, pigments, and citrinin biosynthesis of Monascus purpureus - Run-Ya Li; Chen-Yu Zhang; Shaoxiang Xiao; Xin-Yi Liu; Ru-Xue Li; Jing Li; Hao Li; Jun Liu (Archives of Microbiology, 2025)

Characterization of the gut microbiota in drug abuse: prediction, prevention, and personalized medicine to benefit affected populations - Xin Wang; Ya-Jie Yu; Cai Liao; Xiao-Ru Liu; Rui Yu; Yun Wang (EPMA Journal, 2025)

Unveiling the role of aeration tanks in the emission and enrichment of airborne antibiotic resistance genes in a wastewater treatment plant - Jui-Hung Yen; Jun-Fa Yeh; Chih-Yu Chan; Hsin-Hsin Tung; Kai-Hsien Chi; Hsin-Chang Chen; Wan-Ru Chen; Charles C.-K. Chou; Ta-Chih Hsiao (Water Research, 2025)

Urinary biomarkers of drinking water disinfection byproducts in relation to blood-based liver function parameters among reproductive-aged Chinese women - Ping-Ping Gui; Yan-Ling Deng; Min Zhang; Yu Miao; Peng-Hui Liu; Jia-Yue Zeng; Yang Wu; Cheng-Ru Li; Xiao-Ying Liu; Yang-Juan Li; Jin-Qin Zhu; A-Xue Liu; et al. (Science of The Total Environment, 2025)

The Arabidopsis heterotrimeric G protein α subunit binds to and inhibits the inward rectifying potassium channel KAT1 - Jiang-Fan Guo; Hui Zhou; Zhuo-Ran Hu; Ya-Lan Yang; Wen-Bin Wang; Yan-Ru Zhang; Xue Li; Nuerkaimaier Mulati; Ying-Xin Li; Lu Wu; Yu Long; Jun-Min He (Plant Science, 2025)

The association between anthropogenic heat and parent-report symptoms of childhood attention deficit hyperactivity disorder in China: A novel perspective reflecting climate change - Tao Yu; Yue Wen; Pei-Pei Dong; Ming-Kun Sun; Samantha E. Qian; Mario Schootman; Michael G. Vaughn; Shu-Li Xu; He-Hai Huang; Feng-Wen Shan; Shi-Fu Zhu; Jing-Yao Wang; et al. (International Journal of Hygiene and Environmental Health, 2025)

Microbiological, physicochemical, textural, and rheological properties of fermented soymilk produced with Enterococcus faecium and Lactiplantibacillus plantarum - Chang-Cheng Li; Shu-Jun Guo; Yu-Ting Feng; Yan-Ru Zhou; Yue Li; Zhen-Peng Gao; Chun-Feng Guo (Food Chemistry, 2025)

Two new phenolic glycosides from the rhizomes of Paris yunnanensis - Yu-Rui Xie; Shan-Shan Ling; Yan-Xi Li; Mei-Ru Wang; Hai-Yang Liu (Phytochemistry Letters, 2025)

Microplastic pollution in stony coral skeletons and tissues: A case study of accumulation and interrelationship in South Penghu Marine National Park, Taiwan Strait - Chih-Feng Chen; Yun-Ru Ju; Ming-Huang Wang; Yee Cheng Lim; Chiu-Wen Chen; Yu-Rong Cheng; Cheng-Di Dong (Journal of Hazardous Materials, 2025)

Effect of vacuum frying on the structure and bioactivity of proanthocyanidins in Chinese quince (Chaenomeles sinensis Koehne) fruit - Yu Lou; Xu Fang; Zi-Cheng Yang; Jia-Lin Fei; Yu-Ru Feng; Zhao Qin; Hua-Min Liu; Yu-Xiang Ma; Xue-De Wang (Food Chemistry, 2025)

Exploration of the impact of different drying methods on the quality of Gastrodia elata: A study based on drying kinetics and multidimensional quality evaluation - Ming-xuan Li; Bin Wang; Yu Li; Xin-ru Nie; Jing Mao; Qiang Guo; Nuo Xu; Rao Fu; Zhi-jun Guo; Xiao-li Zhao; Zhen-hua Bian; Tu-lin Lu; et al. (Food Chemistry, 2025)

Differentiation revelation of wine quality induced by maceration technology under the mediation of environmental factors and microbial community - Manman Gao; Shuo Yu; Jianing Bai; Ru Chen; Yunjie Li; Liping Du; Lijuan Ma; Huiling Zhang; Xiaoju Tian (Food Bioscience, 2025)

Fast simulation strategy for capacitively-coupled plasmas based on fluid model - Jing-Ze Li; Ming-Liang Zhao; Yu-Ru Zhang; Fei Gao; You-Nian Wang (Computer Physics Communications, 2025)

Astragalus polysaccharide/carboxymethyl chitosan/sodium alginate based electroconductive hydrogels for diabetic wound healing and muscle function assessment - Letian Tang; Shuyang Xie; Danyang Wang; Yiying Wei; Xiaopu Ji; Yicheng Wang; Nana Zhao; Zonglei Mou; Baoping Li; Wan Ru Sun; Ping Yu Wang; Nicola Paccione Basmadji; et al. (Carbohydrate Polymers, 2025)

Tetrachlorantraniliprole induces neurodevelopmental toxicity through oxidative stress-mediated apoptosis and dysregulation of Wnt signaling pathway - Ru Guo; Youjuan Wu; Tingting Yu; Chen Guo; Zijia Yin; Guannan Zhao; Meifeng Li; Huiling Mao; Chengyu Hu; Xiaowen Xu (Aquatic Toxicology, 2025)

Rapid and visual detection of the strawberries pathogenic fungi Fusarium oxysporum and Colletotrichum siamense by one-pot LAMP-CRISPR/Cas12b - Ya-Ru Tian; Dong-Lan Tang; Tian-Qi Wang; Jia-Yue Chen; Yan-Fang Dong; Xin-Yu Ying; Dan Zhang; Wen-Jing Wang; Zhi-Dan Luo (Journal of Plant Diseases and Protection, 2025)

Self-driven electrochemical system for struvite and energy recovery from digested wastewater: Device optimization strategy and long-term operation - Yi-fan Niu; Ting-ting Dong; Zhi-guo Zhao; Meng-Yu Liu; Ru Wang; Lin-jiang Yuan (Journal of Environmental Management, 2025)

Cation W-doping motivated novel layered K0.45Rb0.05Mn0.85−xWxMg0.15O2 cathode for boosting potassium/sodium-ion storage - Yucong Chen; Xiaobo Chen; Jia Li; Hongjie Chen; Yixuan Su; Weitao Chen; Chengrun Yu; Francis Chi-Chun Ling; Qiang Ru (Chemical Engineering Journal, 2025)

Amorphous Solid Dispersions of Glycyrrhetinic Acid: Using Soluplus, PVP, and PVPVA as the Polymer Matrix to Enhance Solubility, Bioavailability, and Stability - Meng-yu Zhao; Xian-bao Shi; Jin-hua Chang; Ru-xing Wang; Jian-yu Zhou; Pei Liu (AAPS PharmSciTech, 2024)

Heavy metal emissions from on-road vehicles in Xia-Zhang-Quan metropolitan area in southeastern China from 2015 to 2060: impact of vehicle electrification - Zhe-Nan Wen; Qi-Yu Miao; Jiang-Ru Chen; Shui-Ping Wu; Li-Xiong He; Bing-Qi Jiang; Yi-Jing Liu; Zhi Huang (Environmental Science and Pollution Research, 2024)

Environmental contamination and risks of organic UV filters: Source, discharge, analytical methods and implications for ecological and human health - Yue-hong Sun; Heng-Yu Wu; Feng-Qi Xie; Jia-Ru Ma; Qin-Lin Tang; Yan-Fen Chen; Hao Li; You-Sheng Liu; Guang-Guo Ying (Science of The Total Environment, 2024)

Effects of temperature, relative humidity and soil organic carbon content on soil-air partitioning coefficients of volatile PFAS - Weiwei Zhang; Limin Ma; Songsong Chen; Chong Chen; Chengcheng Bu; Jinpeng Yu; Ru Zhang; Yongzhi Wang; Haoyu Zeng; Yuchen Han (Science of The Total Environment, 2024)

Outdoor light at night is a modifiable environmental factor for metabolic syndrome: The 33 Communities Chinese Health Study (33CCHS) - Li-Wen Hu; Yan-Chen Gong; Hong-Xing Zou; Le-Bing Wang; Yanan Sun; Alejandro Godinez; Han-Yu Yang; Si-Han Wu; Shuo Zhang; Wen-Zhong Huang; Zhao-Huan Gui; Li-Zi Lin; et al. (Science of The Total Environment, 2024)

Discovery of a polyurethane-degrading enzyme from the gut bacterium of plastic-eating mealworms - Jiakang Ru; Xuan Chen; Xuena Dong; Lin Hu; Jianli Zhang; Yu Yang (Journal of Hazardous Materials, 2024)

Bacterial necromass as the main source of organic matter in saline soils - Jiashen Song; Hongyuan Zhang; Bahar Razavi; Fangdi Chang; Ru Yu; Xia Zhang; Jing Wang; Jie Zhou; Yuyi Li; Yakov Kuzyakov (Journal of Environmental Management, 2024)

Developing novel microwave-assisted induction heating (MAIH) technology for heating in-packaged ready-to-eat chicken breast products - Chiu-Chu Hwang; Yu-Ru Huang; Cheng-Da Hsieh; Yi-Chen Lee (Innovative Food Science & Emerging Technologies, 2024)

The impact of the addition of vitamin C, NaCl, clove oil on the muscle of live blunt-snout bream during transportation - Yu Chen; Ramy M. Khoder; Jun Mei; Hong Yang; Qilin Huang; Juan You; Tao Yin; Ru Liu (Food Bioscience, 2024)

The formation of protein coronas and its effect on the quercetin-edible dock protein nanoparticles - Yu-Ru Wu; Qian Zhou; Jing Li; Wei Wang; Yi-Bin Zhou; Kang Liu (Food Hydrocolloids, 2024)

The soil-air interfacial migration process of volatile PFAS at the contaminated sites: Evidence from stable carbon isotopes with CSIA - Zhang Weiwei; Chen Songsong; Wang Yongzhi; Zhang Ru; Bu Chengcheng; Yu Jinpeng; Ma Limin (Environmental Pollution, 2024)

Mechanistic insights into the efficient activation of peracetic acid by mackinawite (FeS) for diclofenac degradation under near-neutral conditions: Multiple identification and contribution of non-radicals - Yao-Feng Gao; Yan-Ping Duan; Yu-Ru Chen; Yuan-Hua Jia; Yao-Jen Tu; Chao-Meng Dai (Chemical Engineering Journal, 2024)

A novel heat recovery VRF system: Principle and cooling performance analysis - Shurong Liu; Tianchan Yu; Baolong Wang; Hongmei Lyu; Ru Gao; Wenxing Shi (Building and Environment, 2024)

CircRNA hsa_circ_0003528/miR-215 is considered a potential target for predictive prognosis and therapy for triple-negative breast cancer - Ru Chang; Haizhen Yu; Shizhen Li; Jianzhen Pan (Molecular Biology Reports, 2024)

PRDX1 Interfering Peptide Disrupts Amino Acids 70–90 of PRDX1 to Inhibit the TLR4/NF-κB Signaling Pathway and Attenuate Neuroinflammation and Ischemic Brain Injury - Xiang-Yu Ma; Cheng-yu Qi; Xing-yi Xu; Hui Li; Chang-Dong Liu; Xiang-Ru Wen; Yan-Yan Fu; Yan Liu; Jia Liang; Cheng-Yu Huang; Dan-Dan Li; Yan Li; et al. (Molecular Neurobiology, 2024)

Targeting PADI2 as a potential therapeutic strategy against metastasis in oral cancer via suppressing EMT-mediated migration and invasion and CCL3/5-induced angiogenesis - Shih-Kai Hung; Chih-Chia Yu; Hon-Yi Lin; Wen-Yen Chiou; Moon-Sing Lee; Ru-Inn Lin; Ming-Chi Lu (Clinical & Experimental Metastasis, 2024)

MiR-3571 modulates traumatic brain injury by regulating the PI3K/AKT signaling pathway via Fbxo31 - Yang Zhang; Zongying He; Qiongfang Hu; Huali Liu; Rongai Wen; Na Ru; Jinghua Yu; Shaokun Lv; Rui Tao (Cell Biochemistry and Biophysics, 2024)

Clarifying the impacts of climatic coupling on plastic-mulching potato production in the loess plateau of China - Zhihao He; Kaiyuan Gong; Mengyu Qu; Xiaoya Ru; Shang Chen; Tengcong Jiang; Jing Zhang; Hao Feng; Qiang Yu; Liang He; Jianqiang He (Agricultural Systems, 2024)

The different impacts of functional network centrality and connectivity on the complexity of brain signals in healthy control and first-episode drug-naïve patients with major depressive disorder - Shanling Ji; Wei An; Jing Zhang; Cong Zhou; Chao-Gan Yan; Xiao Chen; Li-Ping Cao; Wei Chen; Yu-Qi Cheng; Yi-Ru Fang; Qi-Yong Gong; Wen-Bin Guo; et al. (Brain Imaging and Behavior, 2024)

Functional characterization of a novel Chlamydomonas reinhardtii hydrolase involved in biotransformation of chloramphenicol - Xin Qi; Jing-Yu Qin; Shaoguo Ru; Jiu-Qiang Xiong (Water Research, 2024)

An embryonic intra-oceanic subduction in the Bangong−Nujiang Meso-Tethys: insights from Late Jurassic Nd Hf isotopic decoupling adakitic granodiorites in the Dongco ophiolite of central Tibet - Xin-Miao Wang; Chen Ji; Kai-Jun Zhang; Ru-Ye Tian; Kang-Yu Li (Lithos, 2024)

Physicochemical properties, structural characteristics and protein digestibility of pea protein-wheat gluten composited meat analogues prepared via high-moisture extrusion - Yu-Ru Zhao; Ning Peng; Ying-Qiu Li; Yan Liang; Zhi-Wei Guo; Cai-Yue Wang; Zi-Yue Wang; Chenying Wang; Xidong Ren (Food Hydrocolloids, 2024)

Long-term exposure to ozone and sleep disorders in children: A multicity study in China - Zhao-Huan Gui; Joachim Heinrich; Lidia Morawska; Tian-Yu Zhao; Steve Hung-Lam Yim; Xiang-Qian Lao; Meng Gao; Duo-Hong Chen; Hui-Min Ma; Li-Zi Lin; Ru-Qing Liu; Guang-Hui Dong (Environmental Research, 2024)

Cadmium causes cerebral mitochondrial dysfunction through regulating mitochondrial HSF1 - Chen-Xi Li; Milton Talukder; Ya-Ru Xu; Shi-Yong Zhu; Yu-Xiang Wang; Jin-Long Li (Environmental Pollution, 2024)

The impact of digital technology innovation on green total-factor energy efficiency in China: Does economic development matter? - Ru-Yu Xu; Ke-Liang Wang; Zhuang Miao (Energy Policy, 2024)

Genomic estimated selection criteria and parental contributions in parent selection increase genetic gain of maternal haploid inducers in maize - Yu-Ru Chen; Ursula K. Frei; Thomas Lübberstedt (Theoretical and Applied Genetics, 2024)

Trichoderma harzianum promoting chrysanthemum cutting rooting and reshaping microbial communities in endophytic and rhizosphere environments - Ya-Jie Wu; Murad Muhammad; Yu Jiao; Xiu Chen; Hai-Long Wang; Chun-Mei Lu; Xiao-Ming Wang; Guo-Xing Zhu; Kai-Qing Liu; Yue Zhang; Zi-Chao Liu; Zhi-Xing Chen; et al. (Applied Soil Ecology, 2024)

Dually-amplified electrochemical aptasensor based on the self-linking AuPt nanoflowers for ultrasensitive determination of hemagglutinin - Qing-Cai Yu; Yan Wang; Yao Liu; Chan-Ru Xiong; Xing Chen (Analytica Chimica Acta, 2024)

Efficacy of swallowing rehabilitative therapies for adults with dysphagia: a network meta-analysis of randomized controlled trials - Chi-Li Lee; Kondwani Joseph Banda; Yu-Hao Chu; Doresses Liu; Chiu-Kuei Lee; Chien-Mei Sung; Hidayat Arifin; Kuei-Ru Chou (GeroScience, 2024)

Most appropriate nozzle of six-rotor UAV for prescribed spraying liquid in tea plantation under effects of downwash flow structure in hover - Nai-Hong Hu; Wen-Xuan Zhou; Lin Zhu; Yan-Cheng Li; Xin-Yu Xie; Ru-Yan Hou; Cheng-Long Yin (Crop Protection, 2024)

Corrigendum to “CLAUDIN7 modulates trophectoderm barrier function to maintain blastocyst development in pigs” [Theriogenology 158 (2020) 346–357 10.1016/j.theriogenology.2020.09.038] - Di Gao; Tengteng Xu; Xin Qi; Wei Ning; Shang Ren; Zhenyuan Ru; Kaiyuan Ji; Yangyang Ma; Tong Yu; Yunsheng Li; Zubing Cao; Yunhai Zhang (Theriogenology, 2024)

Long-term ambient ozone exposure and childhood asthma, rhinitis, eczema, and conjunctivitis: A multi-city study in China - Zhao-Huan Gui; Zhan-Yu Guo; Yang Zhou; Shyamali Dharmage; Lidia Morawska; Joachim Heinrich; Zhang-Kai Cheng; Hui Gan; Zhi-Wei Lin; Dong-Ying Zhang; Jing-Wen Huang; Li-Zi Lin; et al. (Journal of Hazardous Materials, 2024)

The construction of yeast β-glucan coated-edible dock protein nanomicelles for the encapsulation and sustained release of apigenin - Qian Zhou; Xiao-Jie Wang; Yu-Ru Wu; Weinan Zhang; Jing Li; Wei Wang; Ying-Nan Liu; Zhen-Yu Yu; Ming-Ming Zheng; Yi-Bin Zhou; Kang Liu (Journal of Food Engineering, 2024)

Technology-driven carbon-neutral pathway analysis for Urban Wastewater Treatment Plants - Haoran Wu; Chen Cai; Lian Yu; Zhenxing Shang; Yumeng Zhang; Xiaojing Ni; Ru Guo; Jia Liu; Kaiming Peng; Xiangfeng Huang; Limin Zhang; Zhaochang Huang; et al. (Journal of Cleaner Production, 2024)

Plantago asiatica seed as a protective agent for mitigating metals toxicity on Penaeus vannamei - Zhen-Hao Liao; Yeh-Fang Hu; Wen-Shao Wu; Huu-The Nguyen; Sofia Priyadarsani Das; Huai-Ting Huang; Yu-Ru Lin; Po-Tsang Lee; Fan-Hua Nan (Fish & Shellfish Immunology, 2024)

A bifunctional thiobenzamide additive for improvement of cathode kinetics and anode stability in lithium-sulfur batteries - Junpeng Rao; Tong Yu; Youshuang Zhou; Ru Xiao; Yaozu Wang; Zhuoyan Qu; Dean Shi; Zhenhua Sun; Feng Li (Chemical Engineering Journal, 2024)

Promoting symbiotic relationship between microalgae and bacteria in wastewater treatment processes: Technic comparison, microbial analysis, and future perspectives - Cong-Cong Tang; Ya-Ru Hu; Zhang-Wei He; Zhi-Hua Li; Yu Tian; Xiaochang C. Wang (Chemical Engineering Journal, 2024)

Lowering Schottky barrier in MoC-based cocatalyst via heteroatoms tunning for enhanced photocatalytic hydrogen evolution - Ru-zhou Miao; Yu-long Bao; Guang Yang; Ying-jie Sun; Xiao-jing Wang; Jun Zhao; Hui-ying Mu; Fa-tang Li (Chemical Engineering Journal, 2024)

The cooperative p-n heterojunction and Schottky junction in Au-decorated hierarchical CuS@SnS2 hollow cubes for boosted charge transport and CO2 photoreduction - Yuejia Yin; Yajie Chen; Xinyan Yu; Qiuyu Zhang; Yaxin Ru; Guohui Tian (Chemical Engineering Journal, 2024)

Combined effects of nitrogen limitation and overexpression of malic enzyme gene on lipid accumulation in Dunaliella parva - Shi-Yu Liang; Li-Hua Li; Meng-Xiang Ling; Lei Mo; Li-Mei Huang; Ling-Ru Ruan; Chang-Hua Shang (Bioresource Technology, 2024)

Chemical constituents from Ficus tikoua and chemotaxonomic significance - Han-Lei Wang; Jing Lu; Xue-Lin Chen; Ru Li; Kun Zhang; Yu-Ling Guo; Xia Zhao; Yu-Mei Zhang (Biochemical Systematics and Ecology, 2024)

Ingenane-type diterpenoids inhibit non-small cell lung cancer cells by regulating SRC/PI3K/Akt pathway - Xin-Ye Wang; Yu-Jue Wang; Zi-Lin Hou; Bo-Wen Guo; Ru-Qi Wang; Qingbo Liu; Guo-Dong Yao; Shao-Jiang Song (Natural Product Research, 2024)

Silencing of the Phytoene Desaturase (PDS) gene through virus infection using Tobacco Rattle Virus in Physalis grisea - Hai-Meng Zhang; Ru-Xin Wang; Yi-Ting Liu; Peng-Wei Jing; Qiao-Fang Shi; Yi-He Yu (Plant Cell, Tissue and Organ Culture (PCTOC), 2024)

Genesis of Pb–Zn-Ag-Sb mineralization in the Tethys Himalaya, China: Early magmatic-hydrothermal Pb–Zn(-Ag) mineralization overprinted by Sb-rich fluids - Xiang Sun; Ru-Yue Li; Hao-Yu Sun; Paul H. Olin; M. Santosh; Bin Fu; Jun Deng (Mineralium Deposita, 2024)

The irregular developmental duration mainly caused by the broad-complex in Chilo suppressalis - Zhi-Ling Zhang; Qing-Yu Xu; Ru Zhang; Chen Shen; Hai-Bo Bao; Guang-Hua Luo; Ji-Chao Fang (Pesticide Biochemistry and Physiology, 2024)

Water–Rock reactions in the acid leaching of Uranium: Hydrochemical characteristics and reaction mechanisms - Bing Wang; Yue Luo; Xun Li; Ya–zhou Liu; Chang–rui Xu; Yu–xiu Zheng; Yan–hong Zhang; Yi–ru Zhou (Journal of Hydrology, 2024)

The effectiveness of gliding arc discharge plasma in sterilizing artificial seawater contaminated with Vibrio parahaemolyticus - Meng-Ru Du; Yu-yi Guo; Han-ze Wei; Yu-pan Zhu; Rong-rong Liu; Ruo-nan Ma; Fu-kun Shi; Jin-song Guo; Jie Zhuang (Journal of Hazardous Materials, 2024)

Association between outdoor light at night exposure and executive function in Chinese children - Han-Yu Yang; Si-Han Wu; Shuo Zhang; Hong-Xing Zou; Le-Bing Wang; Li-Zi Lin; Zhao-Huan Gui; Xiao-Wen Zeng; Bo-Yi Yang; Ru-Qing Liu; Guang-Hui Dong; Li-Wen Hu (Environmental Research, 2024)

Non-covalent interactions-advanced selective trapping of flexible nitrilotriacetamide towards radioactive pertechnetate - Ding Xie; Juan Wang; Yu-Chang Hou; Yuan-Ru Guo; Songdong Ding; Qing-Jiang Pan (Chemical Engineering Journal, 2024)

Development and efficacy evaluation of nanoliposomes targeting CAFs-LCSCs communication for hepatocellular carcinoma treatment - Liang Kong; Yang Yu; Ru Yang; Rui-bo Guo; Lu Zhang; Jia-hua Wang; Yang Liu; Juan Zang; Chen Yang; Hui-yue Yang; Rui-jun Ju; Xue-tao Li (Chemical Engineering Journal, 2024)

Direct evidence from STXM analysis of enhanced oxygen storage capacity in ceria through the addition of Cu and Mg: Correlation of HT-WGS reaction performance - Ru-Ri Lee; Dong-Hyun Kim; Kyung-Won Jeon; I-Jeong Jeon; Chang-Hyeon Kim; Alexander S. Ditter; David A. Shapiro; Matthew A. Marcus; Hendrik Ohldag; Karen C. Bustillo; Young sang Yu; Won-Jun Jang; et al. (Chemical Engineering Journal, 2024)

Biofunctionalized hydrogel composed of genipin-crosslinked gelatin/hyaluronic acid incorporated with lyophilized platelet-rich fibrin for segmental bone defect repair - Er-Yuan Chuang; Yi-Cheng Lin; Yu-Min Huang; Chih-Hwa Chen; Yi-Yen Yeh; Lekha Rethi; Yu-Jen Chou; Pei-Ru Jheng; Jen-Ming Lai; Chang-Jung Chiang; Chin-Chean Wong (Carbohydrate Polymers, 2024)

Performance evaluation of vegetation concrete with carbonaceous mudstone aggregates in slope protection under wet-dry conditions - Ling Zeng; Jin-Tao Luo; Zi-Ru Yang; Hui-Cong Yu; Wei Wen; Qian-Feng Gao; Hong-Ri Zhang (Bulletin of Engineering Geology and the Environment, 2024)

Glucoconjugated monoterpene indole alkaloids with xanthine oxidase inhibitory activity from Ophiorrhiza japonica - Bao-Bao Shi; Fan Xu; Guang-Ru Zhang; Yu He; Qing Liu; Meng-Lin Feng; Zheng-Hui Li; Ji-Kai Liu (Phytochemistry, 2024)

Ecological restoration largely alleviates livestock grazing pressure in a montane grassland - Xiao-lian Qi; Hao-jie Xu; Ru-yu Teng; Tian Chen; Xu-dong Wang (Journal of Cleaner Production, 2024)

LECT2 mediates antibacterial immune response induced by Nocardia seriolae infection in the northern snakehead - Jian Teng; Yan Zhao; Yu Bao Li; Liang Yi Xue; Yi Xiang Zhai; Jian Ru Liu; Hui Wang; Xiang Shan Ji (Fish & Shellfish Immunology, 2024)

Effects of Taiwanese indigenous cinnamon (Cinnamomum osmophloeum) leaf hot-water extract on nonspecific immune responses, resistance against Vibrio parahaemolyticus, nonviable cells, and haemocyte subpopulations in white shrimp (Penaeus vannamei) - Muhammad Ar Rozzaaq Nugraha; Yu-Ru Lin; Novi Rosmala Dewi; Huai-Ting Huang; Fan-Hua Nan; Yeh-Fang Hu (Fish & Shellfish Immunology, 2024)

Enhancing open-circuit voltage and suppression of energy loss in ternary organic photovoltaics utilizing carbazole/bicarbazole-based guest donors - Chun-Yu Lin; Bing-Huang Jiang; Pei-Jui Weng; Yu Hsuan Lin; Yu-Wei Su; Hui-Shan Shih; Zhong-En Shi; Yan-Ru Lin; Jijitha Vailassery; Shih-Sheng Sun; Chih-Ping Chen; Yuan Jay Chang (Chemical Engineering Journal, 2024)

Molecular insights into the interactions of theaflavin and epicatechin with different lipid bilayer membranes by molecular dynamics simulation - Rong-zu Nie; Huo-min Luo; Jing-yu Chen; Li-heng Sun; Zi-bo Wang; Zhen-ping Zhang; Ya-ru Bao (Chemistry and Physics of Lipids, 2024)

TNFAIP1 promotes macrophage lipid accumulation and accelerates the development of atherosclerosis through the LEENE/FoxO1/ABCA1 pathway - Can Xu; Jun Meng; Xiao-Hua Yu; Ru-Jing Wang; Mei-Ling Li; Shan-Hui Yin; Gang Wang (Journal of Physiology and Biochemistry, 2024)

Development of the near-infrared fluorescence probe for detection of ONOO− and its application in vitro and vivo - Ya-Jing Shang; Yuan-Yuan Li; Jia-Ling Hu; Yi-Ru Wang; Sheng-Tao Li; Xing-Hu Wu; Ai-Hong Zhang; Yu-Wei Tan; Ting Liang; Xiao-Bo Zhu; Yan-Fei Kang (Analytica Chimica Acta, 2024)

Author Correction: Multiscale nest-site selection and breeding biology: infrared camera monitoring of the great crested grebe Podiceps cristatus in a plateau freshwater lake in southwestern China - Zu K. Luo; Xian H. Shao; Yu B. Liu; Ru B. Wang (Ornithology Research, 2024)

C-Phycocyanin improves the quality of goat oocytes after in vitro maturation and vitrification - Xing-Yue Wang; Yang Gao; Hao-Ran Liu; Teng Wang; Meng-Lei Feng; Fang-Rui Xue; Kang Ding; Qi Yang; Zhao-Yu Jiang; Dui Sun; Chun-Ru Song; Xiao-Jie Zhang; et al. (Theriogenology, 2024)

Distinct response patterns of soil micro-eukaryotic communities to early-season and late-season precipitation in a semiarid grassland - Yanyan Yu; Jingyi Ru; Binghai Lei; Shijie Han; Shiqiang Wan; Junqiang Zheng (Soil Biology and Biochemistry, 2024)

Comprehensive analysis of metal(loid)s and associated metal(loid) resistance genes in atmospheric particulate matter - Xiu-Peng Liang; He-Jing Wang; Jie-Ru Zheng; Xiao-Ru Wang; Dao-Ming Lin; Ya-Qing Wu; Rui-Lian Yu; Gong-Ren Hu; Yu Yan (Science of The Total Environment, 2024)

A versatile food packaging film fabricated by gallic acid/octanoic acid grafted chitosan: Preparation, characterization, high-efficient cells capture and photodynamic eradication of bacteria and biofilms - Ke Zhang; Lai Jiang; Ru-Kang Chen; Yu Shi; Yu-Gang Shi; Yue-Wen Chen; Rammile Ettelaie; Ping Li (Food Hydrocolloids, 2024)

Whole exome sequencing analyses reveal novel genes in telomere length and their biomedical implications - Wei-Shi Liu; Bang-Sheng Wu; Liu Yang; Shi-Dong Chen; Ya-Ru Zhang; Yue-Ting Deng; Xin-Rui Wu; Xiao-Yu He; Jing Yang; Jian-Feng Feng; Wei Cheng; Yu-Ming Xu; et al. (GeroScience, 2024)

Multiscale nest-site selection and breeding biology: infrared camera monitoring of the great crested grebe Podiceps cristatus in a plateau freshwater lake in southwestern China - Zu K. Luo; Xian H. Shao; Yu B. Liu; Ru B. Wang (Ornithology Research, 2024)

Path tracking control for brake-steering tracked vehicles based on an improved pure pursuit algorithm - Chenming Hu; Yu Ru; Xianzhe Li; Shuping Fang; Hongping Zhou; Xianghai Yan; Mengnan Liu; Rong Xie (Biosystems Engineering, 2024)

Urinary haloacetic acid concentrations and thyroid function among women: Results from the TREE study - Yang Wu; Yan-Ling Deng; Min Zhang; Yu Miao; Fei-Peng Cui; Jia-Yue Zeng; Xiao-Ying Liu; Cheng-Ru Li; A-Xue Liu; Jin-Qin Zhu; Yang-Juan Li; Chong Liu; et al. (Science of The Total Environment, 2024)

Unraveling the effect of combined heat and high-pressure homogenization treatment on the improvement of chickpea protein solubility from the perspectives of colloidal state change and structural characteristic modification - Yu Wang; Jing-jing Yuan; Ya-ru Zhang; Xing Chen; Jia-le Wang; Bo Chen; Ke Li; Yan-hong Bai (Food Chemistry, 2024)

A macromolecular Gleditsia Saponin induces apoptosis of leukemia cells through Fas-mediated death receptor pathway and mitochondrial pathway - Wen-jie Ding; Yao Huo; Zhen-tong Li; Yan-ru Liu; Ke-yao Dai; Chao Liu; Hai-yu Ji; An-jun Liu (Food Bioscience, 2024)

Enteral nutrition in the management of acute pancreatitis: Modulates gut microbiome and alleviates inflammation - Fang-Yuan Yang; Yi-Jing Cai; Xiao-Ying Niu; Shun-Fu Wang; Yu-Qi Wang; Sabola Eluby Esmie; Rui-Cong Chen; Sheng-Jie Dai; Hong-Ru Kong; Hong-Wei Sun; Ke-Qing Shi (Food Bioscience, 2024)

Differences among Lactiplantibacillus plantarum strains isolated from different fermented foods in their potential cholesterol-lowering properties - Shu-Jun Guo; Chang-Cheng Li; Yu-Ting Feng; Yan-Ru Zhou; Bin Liu; Zhen-Peng Gao; Chun-Feng Guo (Food Bioscience, 2024)

Inorganic carbon accumulation in saline soils via modification effects of organic amendments on dissolved ions and enzymes activities - Jiashen Song; Hongyuan Zhang; Kazem Zamanian; Fangdi Chang; Ru Yu; Jing Wang; Jie Zhou; Yuyi Li (CATENA, 2024)

Delayed Chronic Acidic Postconditioning Improves Poststroke Motor Functional Recovery and Brain Tissue Repair by Activating Proton-Sensing TDAG8 - Yan-Ying Fan; Yu Li; Xiao-Ying Tian; Ying-Jing Wang; Jing Huo; Bao-Lu Guo; Ru Chen; Cai-Hong Yang; Yan Li; Hui-Feng Zhang; Bao-Long Niu; Ming-Sheng Zhang (Translational Stroke Research, 2024)

Di- and tri-methylation of histone H3K36 play distinct roles in DNA double-strand break repair - Runfa Chen; Meng-Jie Zhao; Yu-Min Li; Ao-Hui Liu; Ru-Xin Wang; Yu-Chao Mei; Xuefeng Chen; Hai-Ning Du (Science China Life Sciences, 2024)

Regulatory effect of Yinchenhao decoction on bile acid metabolism to improve the inflammatory microenvironment of hepatocellular carcinoma in mice - Jian Shi; Lin Zhu; Bang-Yi Tang; Wan-Qing Yang; Sheng-Yan Xi; Chen-Long Zhang; Peng-Fei Li; Yu-Jie Wang; Kai-Hang Guo; Jing-Ru Huang; Chen-Rui Huang; Zhou-Xin Yu; et al. (Journal of Natural Medicines, 2024)

Application of a water-energy-carbon coupling index to evaluate the long-term operational stability of the anaerobic-anoxic-oxic-membrane bioreactor (A2/O-MBR) process under the influence of rainstorms - Lian Yu; Kaiming Peng; Yizhen Huang; Feng Chen; Shoubin Chen; Yulong Xia; Xiangfeng Huang; Xiaojing Ni; Ru Guo; Chen Cai; Jia Liu (Water Research, 2024)

Pivotal role of intracellular oxidation by HOCl in simultaneously removing antibiotic resistance genes and enhancing dewaterability during conditioning of sewage sludge using Fe2+/Ca(ClO)2 - Xinxin Wang; Yu Lu; Yiwen Yan; Ru Wang; Yuhang Wang; Hua Li; Lixiang Zhou; Guanyu Zheng; Yifeng Zhang (Water Research, 2024)

BDNF mimetics recover palmitic acid-induced injury in cardiomyocytes by ameliorating Akt-dependent mitochondrial impairments - Man-Ru Zhang; Bang-Yun Zuo; Yu-Chen Song; Dan-Dan Guo; Qing-Liu Li; Jin-Xiu Lyu; Hua Zhu; Jing Zhao; Peng-Zhou Hang (Toxicology and Applied Pharmacology, 2024)

Green manure removal with reduced nitrogen improves saline-alkali soil organic carbon storage in a wheat-green manure cropping system - Fangdi Chang; Hongyuan Zhang; Na Zhao; Peiyi Zhao; Jiashen Song; Ru Yu; Zhengrong Kan; Xiquan Wang; Jing Wang; Hanjiang Liu; Dongxun Han; Xinya Wen; et al. (Science of The Total Environment, 2024)

Potential roles of hydroxybenzoate paralytic shellfish toxins in modulating toxin biokinetics in scallops - Zhuo-Ru Lin; Hui-Xia Geng; Ren-Cheng Yu (Journal of Hazardous Materials, 2024)

Direct and indirect monitoring methods for nitrous oxide emissions in full-scale wastewater treatment plants: A critical review - Zhenxin Shang; Chen Cai; Yanli Guo; Xiangfeng Huang; Kaiming Peng; Ru Guo; Zhongqing Wei; Chenyuan Wu; Shunjian Cheng; Youxiang Liao; Chih-Yu Hung; Jia Liu (Journal of Environmental Management, 2024)

A clean label O/W pickering emulsion stabilized by pectin-containing lignocellulosic nanofibrils isolated from apple pomace - Chi Zhang; Tian Gong; Shan Qiang; Xiao Yu Wang; Xiao Ru Wang; Shuai Zhang; Yong Hong Meng (Food Hydrocolloids, 2024)

Uptake, translocation, and metabolism of organophosphate esters (OPEs) in plants and health perspective for human: A review - Zhi-Lang Lao; Dan Wu; Hui-Ru Li; Yu-Fei Feng; Long-Wei Zhang; Xue-Yi Jiang; Yi-Shan Liu; Dong-Wei Wu; Jun-Jie Hu (Environmental Research, 2024)

Role of phosphate in microalgal-bacterial symbiosis system treating wastewater containing heavy metals - Cong-Cong Tang; Ya-Ru Hu; Min Zhang; Sheng-Long Chen; Zhang-Wei He; Zhi-Hua Li; Yu Tian; Xiaochang C. Wang (Environmental Pollution, 2024)

Efficient removal of size-fractionated antibiotic resistance genes (ARGs) in WWTPs secondary effluent by vacuum ultraviolet (VUV) activated potassium peroxymonosulfate (PMS) - Xiao-Yan Fan; Shi-Long Xu; Xing Li; Zhi-Wei Zhou; Yu-Xi Gao; Jun-Ru Zhao; Zhong-Xing Zhang (Chemical Engineering Journal, 2024)

Differentiation of closely-related species within Acinetobacter baumannii-calcoaceticus complex via Raman spectroscopy: a comparative machine learning analysis - Xue-Song Xiong; Lin-Fei Yao; Yan-Fei Luo; Quan Yuan; Yu-Ting Si; Jie Chen; Xin-Ru Wen; Jia-Wei Tang; Su-Ling Liu; Liang Wang (World Journal of Microbiology and Biotechnology, 2024)

Fine mapping of major QTL qshgd1 for spontaneous haploid genome doubling in maize (Zea mays L.) - Tyler L. Foster; Monika Kloiber-Maitz; Laurine Gilles; Ursula K. Frei; Sarah Pfeffer; Yu-Ru Chen; Somak Dutta; Arun S. Seetharam; Matthew B. Hufford; Thomas Lübberstedt (Theoretical and Applied Genetics, 2024)

Vital residues-orientated rational design of butenolide inhibitors targeting Of ChtI - Qing Han; Yun-Jiang Zi; Tian-Yu Feng; Nan Wu; Ren-Xuan Zou; Jing-Yu Zhang; Ru-Lei Zhang; Qing Yang; Hong-Xia Duan (Medicinal Chemistry Research, 2024)

CircRNA: a rising therapeutic strategy for lung injury induced by pulmonary toxicants - Cai Liao; Zhen-Wei He; Rui Yu; Ya-Jie Yu; Xiao-Ru Liu; De-Lei Kong; Yun Wang (Archives of Toxicology, 2024)

Prediction of cytochrome P450-mediated bioactivation using machine learning models and in vitro validation - Xin-Man Hu; Yan-Yao Hou; Xin-Ru Teng; Yong Liu; Yu Li; Wei Li; Yan Li; Chun-Zhi Ai (Archives of Toxicology, 2024)

Experiments and CFD simulation of downwash airflow and fog distribution discharged from a single-rotor UAV fitted with a pulse-jet thermal fogging machine - Jian Zhang; Qing Chen; Jian Liu; Yan Wang; Hongping Zhou; Fengbo Yang; Yu Ru (Biosystems Engineering, 2024)

Opportunist ant species dominate metropolitan microhabitats: Evidence from the eastern margin of the Qinghai-Tibetan plateau - Ru-Yi Yin; Xin-Yu Luo; Xiang-Qin Huang; Zi-Xuan Zhao; Chris Newman; Yi Luo; Zhao-Min Zhou (Soil Biology and Biochemistry, 2024)

Sources-attributed contributions to health risks associated with PM2.5-bound polycyclic aromatic hydrocarbons during the warm and cold seasons in an urban area of Eastern Asia - Yu-Chieh Ting; Yu-Xuan Zou; Shih-Yu Pan; Yi-Ru Ko; Zih-Jhe Ciou; Chuan-Hsiu Huang (Science of The Total Environment, 2024)

Di (2-ethylhexyl) phthalate induced lipophagy-related renal ferroptosis in quail (Coturnix japonica) - Yu Zhu; Xiang-Yu Ma; Ling-Ge Cui; Ya-Ru Xu; Chen-Xi Li; Milton Talukder; Xue-Nan Li; Jin-Long Li (Science of The Total Environment, 2024)

On the origin of selectivity in extracting and separating lanthanide ions by alkyl-nitrilotriacetamide - Yu-Chang Hou; Juan Wang; Yuan-Ru Guo; Song-Dong Ding; Qing-Jiang Pan (Chemical Engineering Journal, 2024)

Effect of Regional Brain Activity Following Repeat Transcranial Magnetic Stimulation in SCA3: A Secondary Analysis of a Randomized Clinical Trial - Xia Liu; Lin Zhang; Hao-Lin Xu; Xia-Hua Liu; Arif Sikandar; Meng-Cheng Li; Xiao-Yue Xia; Zi-Qiang Huang; Na-Ping Chen; Yu-Qing Tu; Jian-Ping Hu; Shi-Rui Gan; et al. (The Cerebellum, 2024)

Risk factors for short-term prognosis of end-stage liver disease complicated by invasive pulmonary aspergillosis - Weiyan Yu; Ying Xiao; Yue Luo; Yangyang Hu; Ru Ji; Wei Wang; Zhinian Wu; Zeqiang Qi; Tingyu Guo; Yadong Wang; Caiyan Zhao (European Journal of Clinical Microbiology & Infectious Diseases, 2024)

Three new diterpenoids isolated from Euphorbia nematocypha Hand.-Mazz and their anti-fungal activity - Rong-Shuai Li; Zhi-Chang Xu; Ding-Mei Qin; Jia-Bi Huang; Meng-Ru Wang; Xue-Rong Zhao; Quan-Yu Yang; Wei-Lie Xiao; Rui-Rui Wang; Xiao-Li Li (Natural Product Research, 2024)

Experimental study of the influence factors of the droplet size of rotary nozzles during manned helicopter spraying operations - Yu Ru; Shuping Fang; Jiangkun Xue; Chenming Hu; Jie Zhou (Crop Protection, 2024)

Subsurface organic amendment of a saline soil increases ecosystem multifunctionality and sunflower yield - Jiashen Song; Hongyuan Zhang; Fangdi Chang; Ru Yu; Jing Wang; Aiping Chen; Yang Xu; Yu Liu; Jie Zhou; Yuyi Li (Science of The Total Environment, 2024)

Migration of phosphorus in pig manure during pyrolysis process and slow-release mechanism of biochar in hydroponic application - Ru-Qing Jiang; Guang-Wei Yu; Lin-Hui Yu; Yu Wang; Chang-Jiang Li; Zhen-Jiao Xing; Xi-Mei Xue; Yin Wang; Cheng Yu (Science of The Total Environment, 2024)

Tyrosine hydroxylase plays crucial roles in larval cuticle formation and larval-pupal tanning in the rice stem borer, Chilo suppressalis - Qing-Yu Xu; Zhi-Ling Zhang; Ru Zhang; Ary A. Hoffman; Ji-Chao Fang; Guang-Hua Luo (Pesticide Biochemistry and Physiology, 2024)

Efficient capture of iodine in steam and water media by hydrogen bond-driven charge transfer complexes - Li Zhang; Yu-Ting Luo; Jia-Qi Fan; Sai-Jin Xiao; Qiong-Qing Zheng; Xiao-Lin Liu; Quan-Gen Tan; Chen Sun; Qiang Shi; Ru-Ping Liang; Jian-Ding Qiu (Journal of Hazardous Materials, 2024)

Comprehensive evaluation of antibiotics pollution the Yangtze River basin, China: Emission, multimedia fate and risk assessment - Yu-Ru Chen; Yan-Ping Duan; Zhi-Bo Zhang; Yao-Feng Gao; Chao-Meng Dai; Yao-Jen Tu; Jun Gao (Journal of Hazardous Materials, 2024)

Preparation and characterization of pea protein isolate-egg white protein composite gels - Yu-Ru Zhao; Ning Peng; Chenying Wang; Ying-Qiu Li; Yan Liang; Zhi-Wei Guo; Ao-Yue Sun; Xidong Ren (Food Hydrocolloids, 2024)

Exposures to drinking water disinfection byproducts and kidney function in Chinese women - Cheng-Ru Li; Yan-Ling Deng; Yu Miao; Min Zhang; Jia-Yue Zeng; Xiao-Ying Liu; Yang Wu; Yang-Juan Li; A-Xue Liu; Jin-Qin Zhu; Chong Liu; Qiang Zeng (Environmental Research, 2024)

Effect of high corn straw loads on short-chain fatty acid production in semi-continuous rumen reactor - Jinsong Liang; Panyue Zhang; Le Chen; Jianning Chang; Ru Zhang; Guangming Zhang; Yu Tian (Bioresource Technology, 2024)

Integrated transcriptome and metabolome analysis revealed that HaMYB1 modulates anthocyanin accumulation to deepen sunflower flower color - Siqi Ma; Hanlin Zhou; Tingting Ren; Er-ru Yu; Bin Feng; Juying Wang; Chengsheng Zhang; Chao Zhou; Yiqiang Li (Plant Cell Reports, 2024)
Key message HanMYB1 was found to play positive roles in the modulation of anthocyanins metabolism based on the integrative analysis of different color cultivars and the related molecular genetic analyses. Abstract As a high value ornamental and edible crop with various colors, sunflowers ( Helianthus annuus L.) provide an ideal system to understand the formation of flower color. Anthocyanins are major pigments in higher plants, which is associated with development of flower colors and ability of oxidation resistance. Here, we performed an integrative analysis of the transcriptome and flavonoid metabolome in five sunflower cultivars with different flower colors. According to differentially expressed genes and differentially accumulated flavonoids, these cultivars could be grouped into yellow and red. The results showed that more anthocyanins were accumulated in the red group flowers, especially the chrysanthemin. Some anthocyanins biosynthesis-related genes like UFGT (UDP-glycose flavonoid glycosyltransferase) also expressed more in the red group flowers. A MYB transcriptional factor, HanMYB1, was found to play vital positive roles in the modulation of anthocyanins metabolism by the integrative analysis. Overexpressed HanMYB1 in tobacco could deepen the flower color, increase the accumulation of anthocyanins and directly active the express of UFGT genes. Our findings indicated that the MYB transcriptional factors provide new insight into the dynamic regulation of the anthocyanin biosynthesis in facilitating sunflower color formation and anthocyanin accumulation.

Inflammation and Brain Structure in Alzheimer’s Disease and Other Neurodegenerative Disorders: a Mendelian Randomization Study - Wei-Shi Liu; Ya-Ru Zhang; Yi-Jun Ge; Hui-Fu Wang; Wei Cheng; Jin-Tai Yu (Molecular Neurobiology, 2024)

Desynchronization of neural networks induced by transcranial magneto-acoustical stimulation: a modeling study - Zhenfang Ma; Yuhui Yang; Jianyang Xu; Yi Ru; Yu Yin (Neurophysiology, 2024)

Biological upcycling of nickel and sulfate as electrocatalyst from electroplating wastewater - Xian-Zhong Fu; Yu-Ru Yang; Tian Liu; Zhi-Yan Guo; Chen-Xuan Li; Hai-Yang Li; Kang-Ping Cui; Wen-Wei Li (Water Research, 2024)

Adaptive shifts in plant traits associated with nitrogen removal driven by phytoremediation strategies in subtropical river restoration - Yu Xin; Lin Liu; Xiao-Ru Yang; Le-Yang Yang; Shan-Bin Guang; Yu-Ming Zheng; Quan-Bao Zhao (Water Research, 2024)

Response of rumen microorganisms to pH during anaerobic hydrolysis and acidogenesis of lignocellulose biomass - Jinsong Liang; Panyue Zhang; Ru Zhang; Jianning Chang; Le Chen; Gongting Wang; Yu Tian; Guangming Zhang (Waste Management, 2024)

Long-term exposure to the mixture of phthalates induced male reproductive toxicity in rats and the alleviative effects of quercetin - Li-Lan Liu; Jun-Zhe Yue; Zhen-Yu Lu; Ru-Ya Deng; Can-Can Li; Ye-Na Yu; Wen-Jin Zhou; Min Lin; Hai-Tao Gao; Jiaming Liu; Ling-Zi Xia (Toxicology and Applied Pharmacology, 2024)

Urinary biomarkers of drinking-water disinfection byproducts in relation to diminished ovarian reserve risk: A case-control study from the TREE cohort - Xiao-Ying Liu; Min Zhang; Xiao-Li Gu; Yan-Ling Deng; Chong Liu; Yu Miao; Yang Wu; Cheng-Ru Li; Jia-Yue Zeng; Yang-Juan Li; A-Xue Liu; Jin-Qin Zhu; et al. (Science of The Total Environment, 2024)

Influence of labor migration on rural household food waste in China: Application of propensity score matching (PSM) - Guohui Shen; Xin Ru; Kunzhen Wang; Ziqi Li; Mingxue Yu; Lu Chen; Juan Han; Yanzhi Guo (Journal of Environmental Management, 2024)

Mixed sowing of Feed rape and Vicia villosa can substitute nitrogen fertilizer to improve soil multifunctionality in the Hetao irrigation District - Ru Yu; Hongyuan Zhang; Fangdi Chang; Jiashen Song; Jing Wang; Xiquan Wang; Zhengrong Kan; Na Zhao; Xiaohong Li; Jun Ma; Yuyi Li (CATENA, 2024)

Mechanism of enhanced microalgal biomass and lipid accumulation through symbiosis between a highly succinic acid-producing strain of Escherichia coli SUC and Aurantiochytrium sp. SW1 - Mei-Yu Zhang; Xin-Ru Xu; Ru-Ping Zhao; Chao Huang; Yuan-Da Song; Zi-Tong Zhao; Yu-Bin Zhao; Xiao-Jie Ren; Xin-He Zhao (Bioresource Technology, 2024)

The application of nanopore targeted sequencing for pathogen diagnosis in bronchoalveolar lavage fluid of patients with pneumonia: a prospective multicenter study - Qinqing Lin; Yake Yao; Xi Li; Shanshan Zhang; Huimin Guo; Xiaolong Ma; Wenyu Chen; Chuhui Ru; Limin Wang; Bin Wang; Qiang Ma; Junfei Zhu; et al. (Infectious Diseases, 2024)

ABA functions in low phosphate-induced anthocyanin accumulation through the transcription factor ABI5 in Arabidopsis - Ru-Feng Song; Xiao-Yu Hu; Wen-Cheng Liu; Hong-Mei Yuan (Plant Cell Reports, 2024)

TAT-W61 peptide attenuates neuronal injury through blocking the binding of S100b to the V-domain of Rage during ischemic stroke - Jia Liang; Hui Li; Chang‑Dong Liu; Xiao‑Yan Zhou; Yan‑Yan Fu; Xiang-Yu Ma; Dan Liu; Yu-Ling Chen; Qian Feng; Zhen Zhang; Xiang-Ru Wen; Guang Zhu; et al. (Journal of Molecular Medicine, 2024)

Prenatal exposures to phthalates and bisphenols in relation to oxidative stress: single pollutant and mixtures analyses - Jia-Yue Zeng; Min Zhang; Xu-Hui Chen; Chong Liu; Yan-Ling Deng; Pan-Pan Chen; Yu Miao; Fei-Peng Cui; Tian Shi; Ting-Ting Lu; Xiao-Ying Liu; Yang Wu; et al. (Environmental Science and Pollution Research, 2024)

Deciphering the influence of dietary synbiotics in white shrimp gut and its effects in regulating immune signaling pathways - Sofia Priyadarsani Das; Zaenal Abidin; Huai-Ting Huang; Yu-Ru Lin; Chih-Yang Huang; Yu-Sheng Wu; Yeh-Fang Hu; Fan-Hua Nan (Frontiers in Marine Science, 2024)
The health of the host is significantly influenced by the gut microbiota. Penaeus vannamei (white shrimp) is one of the most profitable aquaculture species globally. Synbiotics are typically used as a beneficial diet supplement for raising aquaculture species’ growth capacities and enhancing immunity against pathogenicity. However, the effects of synbiotics on the white shrimp intestinal microbiota remain poorly understood. In the present study, we targeted the V3–V4 region of 16S rRNA genes to analyze the effects of synbiotics on white shrimp gut microbiota. Dietary synbiotics, having Lactobacillus acidophilus , and Moringa oleifera leaf extract were added to the white shrimps’ feed in various proportions in the present study. In total, 490 operational taxonomic units yielding 23 phyla, 41 classes, 94 orders, 151 families, and 250 genera of microorganisms were obtained. The diet containing L. acidophilus at 1 × 10 7 CFU/g and M. oleifera at 2.5 g/kg led to an increase in the relative abundance of beneficial microorganisms through a significant decrease in the α diversity. Moreover, it upregulated several physiological pathways such as carbohydrate metabolism, signal transduction, lipid metabolism, nucleotide metabolism, amino acid metabolism, and environmental adaptation, which led to the upregulation of the AMPK, MAPK, P13K-Akt, lysosome, peroxisome, and ferroptosis signaling pathways; this enhanced growth and immunity in white shrimp. Whether a single species or a combination of different microorganisms improves growth and immunity remains unclear till now. Nevertheless, our results will facilitate further in-depth investigation into beneficial microbial communities for upliftment of white shrimp aquaculture.

Effects of Different Intensities and Wavelengths of Light on the Growth of Juvenile Tridacna noae - Rod Ping-Tsan Lee; Yu-Ru Lin; Chih-Yang Huang; Fan-Hua Nan (Molluscan Research, 2024)

Accelerated removal of naproxen in the iron-based peracetic acid activation system by chloride ions: Enhancement of reactive oxidative species via the formation of iron-chloride complexes - Si-Ying Yu; Yang Shi; Chuan-Shu He; Yu-Dan Dong; Si Sun; Ru-Yan Ning; Zhao-Kun Xiong; Peng Zhou; Heng Zhang; Bo Lai (Journal of Hazardous Materials, 2024)

Associations between urinary biomarkers of exposure to disinfection byproducts and semen parameters: A repeated measures analysis - Min Zhang; Xiao-Ying Liu; Yan-Ling Deng; Chong Liu; Jia-Yue Zeng; Yu Miao; Yang Wu; Cheng-Ru Li; Yang-Juan Li; A-Xue Liu; Jin-Qin Zhu; Qiang Zeng (Journal of Hazardous Materials, 2024)

Expression of polyphenol oxidase of Litopenaeus vannamei and its characterization - Qian Hong; Yu-Lei Chen; Duanquan Lin; Ru-Qing Yang; Kai-Yuan Cao; Ling-Jing Zhang; Yi-Ming Liu; Le-Chang Sun; Min-Jie Cao (Food Chemistry, 2024)

Study and application of coupling relationship between water-salt-resistivity-soil structure in saline soils in arid and semi-arid areas of northwest China - Yang Liu; Feng-jie Li; Hong-li Liu; Yu-ru Hou; Nusrat Nazir (Environmental Research, 2024)

Urban green, blue spaces and their joint effect are associated with lower risk of emotional and behavior problem in children and adolescents, a large population-based study in Guangzhou, China - Jing-hong Liang; Ru-yu Yang; Mei-ling Liu; Ying-qi Pu; Wen-wen Bao; Yu Zhao; Li-xin Hu; Yu-shan Zhang; Shan Huang; Nan Jiang; Xue-ya Pu; Shao-yi Huang; et al. (Environmental Research, 2024)

Uptake mechanism, translocation, and transformation of organophosphate esters in water hyacinth (Eichhornia crassipes): A hydroponic study - Zhi-Lang Lao; Dan Wu; Hui-Ru Li; Yi-Shan Liu; Long-Wei Zhang; Yu-Fei Feng; Xue-Yi Jiang; Dong-Wei Wu; Jun-Jie Hu; Guang-Guo Ying (Environmental Pollution, 2024)

Fully space-confined donor-acceptor interaction for highly efficient thermally activated delayed fluorescence emitters - Wen-Cheng Chen; Ming-Hui Zheng; Yu-Lan Wu; Ru-Jia Wang; Jia-Ming Jin; Si-Wei Chen; Bo Liu; Jia-Xiong Chen; Yanping Huo; Shaomin Ji (Chemical Engineering Journal, 2024)

High-strength ionic hydrogel constructed by metal-free physical crosslinking strategy for enhanced uranium extraction from seawater - Yuan-Hao Wang; Yu-Qin Xiang; Qian Huang; Xiao-Lan Yang; Shuang-Long Wang; Yue-Ru Zhou; Song Qin; Ling-Qiong Gou; Guo-Hong Tao; Ling He (Chemical Engineering Journal, 2024)

Technological diversity in the tropical-subtropical zone of Southwest China during the terminal Pleistocene: excavations at Fodongdi Cave - Fa-Xiang Huan; Shi-Xia Yang; Feng Gao; Xin-Ying Zhou; Jian-Ping Yue; Yu-Xiu Zhang; Jin-Xu Wu; Qi-Jun Ruan; Kai-Wei Qiu; Jing-wen Xu; Nai-Ru Lin; Yi-Ren Wang; et al. (Archaeological and Anthropological Sciences, 2024)

A novel hydrangea-like magnetic composite Fe3O4@MnO2@ZIF-67 for efficient selective adsorption of Pd(II) from metallurgical wastewater - Xue Jiang; Yu Zhou; Haiou Chen; Ru Zhang; Junhui Yu; Shixiong Wang; Fengzhi Jiang; Huiping Bai; Xiangjun Yang (Chemosphere, 2023)

Burying straw interlayers decreases CO2 emissions in deep saline soil - Jiashen Song; Hongyuan Zhang; Leanne Peixoto; Fangdi Chang; Ru Yu; Xiquan Wang; Jing Wang; Jufeng Cao; Jie Zhou; Amit Kumar; Yuyi Li (Sustainable Production and Consumption, 2023)

Corrigendum to “Silica nanoparticles promote oxLDL-induced macrophage lipid accumulation and apoptosis via endoplasmic reticulum stress signaling” [Sci. Total Environ., 631-632 (2018): 570-579] - Caixia Guo; Ru Ma; Xiaoying Liu; Tian Chen; Yang Li; Yang Yu; Junchao Duan; Xianqing Zhou; Yanbo Li; Zhiwei Sun (Science of The Total Environment, 2023)

Magmatic–hydrothermal evolution of the Koktokay No. 3 pegmatite, Altai, northwestern China: Constraints from in situ boron isotope and chemical compositions of tourmaline - Rong Yin; Xiao-Long Huang; Ru-Cheng Wang; Gang-Jian Wei; Yi-Gang Xu; Yu Wang; Xiao-Ming Sun; Le Zhang; Xiao-Ping Xia (Lithos, 2023)

A crosslinked waterborne poly(vinyl acetate) for greenhouse gas fixation with improved elastomeric properties, shape-memory ability, and recyclability - Yen-Chuan Chen; Ying-Chi Huang; Yi-Hua Huang; Ying-Feng Lin; Ho-Ching Huang; Ru-Jong Jeng; Yu-Wei Cheng; Chien-Hsin Wu (Journal of Environmental Chemical Engineering, 2023)

Application of lipid and polymeric-based nanoparticles for treatment of inner ear infections via XGBoost - Jie Zhang; Ru Chen; Shuainan Chen; Die Yu; Dalia H. Elkamchouchi; Mohammed S. Alqahtani; Hamid Assilzadeh; Zhongguan Huang; Yideng Huang (Environmental Research, 2023)

Humic acid plus manure increases the soil carbon pool by inhibiting salinity and alleviating the microbial resource limitation in saline soils - Jiashen Song; Hongyuan Zhang; Fangdi Chang; Ru Yu; Xiangqian Zhang; Xiquan Wang; Weini Wang; Junmei Liu; Jie Zhou; Yuyi Li (CATENA, 2023)

Applying sheet iron to enhance the treatment efficiency of digested effluent with continuous flow and the corresponding mechanism - Cong Ding; Li-bin Chen; Li-ping Yu; Ru Wang; Lin-jiang Yuan; Lan Wang; Liang-wei Deng (Chemosphere, 2023)

Microplastics in coral reef sediments underestimated? They may hide in biominerals - Chih-Feng Chen; Yun-Ru Ju; Chiu-Wen Chen; Frank Paolo Jay B. Albarico; Yee Cheng Lim; Chongtai Ke; Yu-Rong Cheng; Cheng-Di Dong (Science of The Total Environment, 2023)

Mineralogy, petrology and P-T conditions of the spodumene pegmatites and surrounding meta-sediments in Lhozhag, eastern Himalaya - Jia-Min Wang; Kang-Shi Hou; Lei Yang; Xiao-Chi Liu; Ru-Cheng Wang; Guang-Ming Li; Jian-Gang Fu; Fang-Yang Hu; Yu-Lu Tian; Fu-Yuan Wu (Lithos, 2023)

Climate co-benefits of VOC control policies in China based on a cross-scale approach - Wen-Wen Zhang; Basil Sharp; Yu Gu; Shi-Chun Xu; Jianyun Nie; Ru-Yin Long; Mei-Fen Wu (Journal of Environmental Management, 2023)

Dual N-modification enables high-performance Solid-State Li metal batteries with Li5.5PS4.5Cl1.5 - Chaochao Wei; Ru Wang; Zhongkai Wu; Qiyue Luo; Ziling Jiang; Liang Ming; Long Zhang; Hongcheng Lu; Guangshe Li; Liping Li; Chuang Yu; Shijie Cheng (Chemical Engineering Journal, 2023)

Mechanical energy-driven triboelectric plasma catalytic CO2 reduction over oxygen-vacancy-introduced In2O3 nanoparticles - Xiaochen Xiang; Jiao Wang; Qinglong Ru; Sumin Li; Ke Zhao; Yifei Zhu; Zhenpan Chen; Liangliang Liu; Guangqin Gu; Yu Jia; Bao Zhang; Gang Cheng; et al. (Chemical Engineering Journal, 2023)

Multipath charge transfer in Cu-BTC@CuS@CeO2 double p-n heterojunction hollow octahedrons for enhanced photocatalytic amine oxidation - Yaxin Ru; Yajie Chen; Xinyan Yu; Qiuyu Zhang; Yuejia Yin; Guohui Tian (Chemical Engineering Journal, 2023)

Cyclodextrin-based metal-organic framework materials: Classifications, synthesis strategies and applications in variegated delivery systems - Ru-nan Zhao; Bei-wei Zhu; Yu Xu; Song-feng Yu; Wen-jun Wang; Dong-hong Liu; Jiang-ning Hu (Carbohydrate Polymers, 2023)

Intermittent fasting and Alzheimer's disease—Targeting ketone bodies as a potential strategy for brain energy rescue - Yu- Cai Ye; Shi-Fan Chai; Xin-Ru Li; Mei-Na Wu; Hong-Yan Cai; Zhao-Jun Wang (Metabolic Brain Disease, 2023)

Maternal transfer of F-53B inhibited neurobehavior in zebrafish offspring larvae and potential mechanisms: Dopaminergic dysfunction, eye development defects and disrupted calcium homeostasis - Luyin Wu; Mohammed Zeeshan; Yao Dang; Yun-Ting Zhang; Li-Xia Liang; Jing-Wen Huang; Jia-Xin Zhou; Li-Hao Guo; Yuan-Yuan Fan; Ming-Kun Sun; Tao Yu; Yue Wen; et al. (Science of The Total Environment, 2023)

Reduction of pesticides and bacteria on Napa cabbage by ozone microbubble water - Hsiu-Ling Chen; Rachelle D. Arcega; Pei-Yu Liao; Chih-Yao Hou; Wen-Chun Liu; Yun-Ru Chen; Jong-Shinn Wu; Wan-Ru Wang; Chia-Min Lin (Postharvest Biology and Technology, 2023)

Efficient removal of impurities from phosphogypsum during preparation of α-hemihydrate gypsum - Qingjun Guan; Yulin Zhou; Weijian Yu; Ruihua Fan; Ying Sui; Yongjie Bu; Zhigang Yin; Ru-an Chi; Zhiyong Gao (Minerals Engineering, 2023)

Characterizing basin-scale subsurface hydraulic heterogeneity with multiscale geological and hydrological measurements - Hong-Ru Lin; Jet-Chau Wen; Zaiyong Zhang; Yu-Li Wang (Journal of Hydrology, 2023)

Boron nitride quantum dots-enhanced laser desorption/ionization mass spectrometry analysis and imaging of bisphenol A - Yanfang Zhao; Rabah Boukherroub; Lu Liu; Huizhi Li; Ru-Song Zhao; Qin Wei; Xiang Yu; Xiangfeng Chen (Journal of Hazardous Materials, 2023)

Ozone exposure associates with sperm quality indicators: Sperm telomere length as a potential mediating factor - Zhong-Hua Lu; Bin Sun; Yi-Xin Wang; Ya-Ru Wu; Yu-Jie Chen; Sheng-Zhi Sun; Shi-Jia Liang; Song Xu; Hao Chang; Heng-Gui Chen; Jie Zhang (Journal of Hazardous Materials, 2023)

Once-middle amount of straw interlayer enhances saline soil quality and sunflower yield in semi-arid regions of China: Evidence from a four-year experiment - Fangdi Chang; Hongyuan Zhang; Jiashen Song; Ru Yu; Xia Zhang; Haoruo Li; Jing Wang; Zhengrong Kan; Yuyi Li (Journal of Environmental Management, 2023)

Enhanced encapsulation of lutein using soy protein isolate nanoparticles prepared by pulsed electric field and pH shifting treatment - Rui Wang; Man-Qin Zeng; Yu-Wei Wu; Yong-Xin Teng; Lang-Hong Wang; Jian Li; Fei-Yue Xu; Bo-Ru Chen; Zhong Han; Xin-An Zeng (Food Chemistry, 2023)

Self-assembly and interaction mechanisms of edible dock protein and flavonoids regulated by the phenolic hydroxyl position - Qian Zhou; Xiao-Jie Wang; Jing Li; Yu-Ru Wu; Wei Wang; Zhen-Yu Yu; Ya-Qing Xiao; Ying-Nan Liu; Shi-Yi Li; Ming-Ming Zheng; Yi-Bin Zhou; Kang Liu (Food Chemistry, 2023)

Climate warming may accelerate apple phenology but lead to divergent dynamics in late-spring frost and poor pollination risks in main apple production regions of China - Xiaoya Ru; Jie Zhou; Kaiyuan Gong; Zhihao He; Zhanwu Dai; Meirong Li; Xinxin Feng; Qiang Yu; Hao Feng; Jianqiang He (European Journal of Agronomy, 2023)

Adult Kerion Celsi Caused by Trichophyton tonsurans Secondary to Black Dot Tinea Capitis - Qian-ru Ye; Yu-wu Luo; Xin Zhou; Qing-qing Li; Yu-mei Liu (Mycopathologia, 2023)
A 34-year-old female patient presented with hair loss due to black dot tinea capitis caused by Trichophyton tonsurans for 6 months. Hair loss progressed to painful swelling for 2 months due to kerion Celsi which may be associated with treatment like topical minoxidil, antibiotic and corticosteroid previously. The patient was treated with oral Itraconazole initially without success but cured by Terbinafine eventually. It’s very interesting that the patient caught kerion celsi secondary to a four-month history of hair loss due to black dot tinea capitis.

A life-threatening bleeding prediction model for immune thrombocytopenia based on personalized machine learning: a nationwide prospective cohort study - Zhuo-Yu An; Ye-Jun Wu; Yu Hou; Heng Mei; Wei-Xia Nong; Wen-Qian Li; Hu Zhou; Ru Feng; Jian-Ping Shen; Jun Peng; Hai Zhou; Yi Liu; et al. (Science Bulletin, 2023)

From arc accretion to within-plate extension: Geochronology and geochemistry of the Neoproterozoic magmatism on the northern margin of the Yangtze Block - Yu Huang; Xiao-Lei Wang; Jun-Yong Li; Ru-Cao Li; De-Hong Du; Chang-Hong Jiang; Lin-Sen Li; Ning Ding (Precambrian Research, 2023)

Metabolomic profiling of Panax ginseng in response to Fusarium solani infection - Guijia Zhao; Shuyang Xing; Yang Wang; Xu Yang; Ru Sun; Lin Feng; Jifeng Wang; Tianxia Sun; Wenhui Lian; Yu Zhao (Physiological and Molecular Plant Pathology, 2023)

CDN1163, a SERCA activator, causes intracellular Ca2+ leak, mitochondrial hyperpolarization and cell cycle arrest in mouse neuronal N2A cells - Yi-Ping Huang; Wen-Wei Huang; Kun-Feng Tsai; Lian-Ru Shiao; Zih-He Yang; Shao-Yun Tseng; Yu-Hsien Lin; Cing-Yu Chen; Paul Chan; Yuk-Man Leung (NeuroToxicology, 2023)

Effects of combined antibiotics on nitrification, bacteria and antibiotic resistance genes in activated sludge: Insights from legacy effect of antibiotics - Zhong-Xing Zhang; Xiao-Yan Fan; Xing Li; Yu-Xi Gao; Jun-Ru Zhao (Journal of Environmental Sciences, 2023)

Individual and joint associations of urinary phthalate metabolites with polycystic ovary and polycystic ovary syndrome: Results from the TREE cohort - Min Zhang; Chong Liu; Xiao-Qiong Yuan; Fei-Peng Cui; Yu Miao; Wen Yao; Dan-Yu Qin; Yan-Ling Deng; Pan-Pan Chen; Jia-Yue Zeng; Xiao-Ying Liu; Yang Wu; et al. (Environmental Toxicology and Pharmacology, 2023)

Impact of National Industrial Relocation Demonstration Zones (NIRDZs) policy on urban carbon emissions in China - Ke-Liang Wang; Ru-Yu Xu; Wei Jiang; Yuan Liu (Environmental Impact Assessment Review, 2023)

Partially miscible droplet microfluidics to enhance interfacial adsorption of hydrophilic nanoparticles for colloidosome synthesis - Wei-Yi Chu; Yi-Ru Chiou; Ren-Hao Luo; Tzu-Heng Chen; Cheng-Ju Yu; Yi-Ju Chou; Huan-Tsung Chang; Chien-Fu Chen (Chemical Engineering Journal, 2023)

Age- and gender-related dispersion of brain networks across the lifespan - Qing Wang; Lingyu Qi; Cancan He; Haixia Feng; Chunming Xie; Chao-Gan Yan; Xiao Chen; Le Li; Francisco Xavier Castellanos; Tong-Jian Bai; Ning-Xuan Chen; Wei Chen; et al. (GeroScience, 2023)

Strategy for cost-effective BMPs of non-point source pollution in the small agricultural watershed of Poyang Lake: A case study of the Zhuxi River - Wei Liu; Lei Zhang; Huoliang Wu; Yinfeng Wang; Yalan Zhang; Jinying Xu; Dongyang Wei; Ru Zhang; Ying Yu; Daishe Wu; Xianchuan Xie (Chemosphere, 2023)

Inhibition of ecdysone receptor (DcEcR) and ultraspiracle (DcUSP) expression in Diaphorina citri increased susceptibility to pesticides - Cong Zhang; Bin Wan; Meng-Ru Jin; Xi Wang; Yu-Jing Wei; Ling Zhong; Bin Xia (Pesticide Biochemistry and Physiology, 2023)

The sustainable treatment of chemical polishing wastewater under low-carbon economy: Pollutants removal, resource recovery and energy generation - Cong Ding; Meng-yu Liu; Si-zhuo Wan; Zhao-yang Cai; Lin-jiang Yuan; Ru Wang; Ping Zheng (Journal of Cleaner Production, 2023)

Au@BN-enhanced laser desorption/ionization mass spectrometry and imaging for determination of fipronil and its metabolites in food and biological samples - Yanfang Zhao; Rabah Boukherroub; Guiju Xu; Huijuan Li; Ru-Song Zhao; Qin Wei; Xiang Yu; Xiangfeng Chen (Food Chemistry, 2023)

Understanding the digestibility of wheat starch- caffeic acid complexes prepared by hot-extrusion 3D printing technology - Xin-Ru Cui; Yu-Sheng Wang; Yan Chen; Hong-Yan Mu; Hai-Hua Chen (Food Hydrocolloids, 2023)

Pollinium development and sporoderm structure of Dendrobium officinale - Yi Feng Cui; Ting Zhou; Ya Ru Wei; De Quan Wang; Wen Yu Liang; Shu Juan Yang (Flora, 2023)

Thymic tuft cells: potential “regulators” of non-mucosal tissue development and immune response - Jun Sun; Ming-xin Li; Yi-meng Xie; Ya-ru Zhang; Yu-rong Chai (Immunologic Research, 2023)

Effect of liver metastasis on the efficacy of immune checkpoint inhibitors in cancer patients: a systemic review and meta-analysis - Bao-Wen Tian; Cheng-Long Han; Han-Chao Wang; Lun-Jie Yan; Zi-Niu Ding; Hui Liu; Xin-Cheng Mao; Jin-Cheng Tian; Jun-Shuai Xue; Long-Shan Yang; Si-Yu Tan; Zhao-Ru Dong; et al. (Clinical & Experimental Metastasis, 2023)

Recent Progress in Atmospheric Chemistry Research in China: Establishing a Theoretical Framework for the “Air Pollution Complex” - Tong Zhu; Mingjin Tang; Meng Gao; Xinhui Bi; Junji Cao; Huizheng Che; Jianmin Chen; Aijun Ding; Pingqing Fu; Jian Gao; Yang Gao; Maofa Ge; et al. (Advances in Atmospheric Sciences, 2023)
Atmospheric chemistry research has been growing rapidly in China in the last 25 years since the concept of the “air pollution complex” was first proposed by Professor Xiaoyan TANG in 1997. For papers published in 2021 on air pollution (only papers included in the Web of Science Core Collection database were considered), more than 24 000 papers were authored or co-authored by scientists working in China. In this paper, we review a limited number of representative and significant studies on atmospheric chemistry in China in the last few years, including studies on (1) sources and emission inventories, (2) atmospheric chemical processes, (3) interactions of air pollution with meteorology, weather and climate, (4) interactions between the biosphere and atmosphere, and (5) data assimilation. The intention was not to provide a complete review of all progress made in the last few years, but rather to serve as a starting point for learning more about atmospheric chemistry research in China. The advances reviewed in this paper have enabled a theoretical framework for the air pollution complex to be established, provided robust scientific support to highly successful air pollution control policies in China, and created great opportunities in education, training, and career development for many graduate students and young scientists. This paper further highlights that developing and low-income countries that are heavily affected by air pollution can benefit from these research advances, whilst at the same time acknowledging that many challenges and opportunities still remain in atmospheric chemistry research in China, to hopefully be addressed over the next few decades.

CAT Interruption as a Protective Factor in Chinese Patients with Spinocerebellar Ataxia Type 1 - Ya-Ru Shao; Jin-Yang Yu; Yin Ma; Yi Dong; Zhi-Ying Wu (The Cerebellum, 2023)

Inhibitory effect of Portulaca oleracea L. aqueous extract and juice on NLRP3 inflammasome activation in an ulcerative colitis mouse model - Yi-meng Fan; Yuan-yuan Wei; Hui-ru Wang; Yu-Ga; Yan-nan Zhang; Zhihui Hao (Environmental Science and Pollution Research, 2023)

Role of phosphite in the environmental phosphorus cycle - Wei Liu; Yalan Zhang; Mengqin Yu; Jinying Xu; Hu Du; Ru Zhang; Daishe Wu; Xianchuan Xie (Science of The Total Environment, 2023)

Anti-inflammatory lanostane triterpenoids with rearranged spirobi[indene] scaffold and their biogenetically related analogues from Euphorbia maculata - Ru-Feng Xia; Jun-Cheng Su; Jun Yu; Hong-Jing Zha; Jia-Le Wu; Xiao-Na Fu; Qin Cai; Luo-Sheng Wan (Phytochemistry, 2023)

Rationally designing imidazole-based coordination polymers with high adsorption capacity for removing iodine - Xin Gao; Qing-Hua Hu; Yu-Zhen Shi; Ru-Ping Liang; Jian-Ding Qiu (Chemical Engineering Journal, 2023)

Genetic variation reveals the enhanced microbial hyaluronan biosynthesis via atmospheric and room temperature plasma - Zhi-Yuan Yao; Jin-Song Gong; Yu-Ru Liu; Jia-Yu Jiang; Yue-Sheng Zhang; Chang Su; Heng Li; Chuan-Li Kang; Lei Liu; Zheng-Hong Xu; Jin-Song Shi (Carbohydrate Polymers, 2023)

Effects of fungal agents and biochar on odor emissions and microbial community dynamics during in-situ treatment of food waste - Shu-Ping Zou; Ru-Sheng Liu; Yu Luo; Chun-Tao Bo; Su-Qin Tang; Ya-Ping Xue; Yu-Guo Zheng (Bioresource Technology, 2023)

Projections from the Prefrontal Cortex to Zona Incerta Mediate Fear Generalization - Kun Tong; Guang-Kai Bu; Si-Qi Jing; Tong Wu; Yu-Tong Song; Yue You; Le Liu; Yuan-Hao Chen; Jing-Ru Hao; Nan Sun; Can Gao (Neuroscience Bulletin, 2023)

Ganglioside-focused Glycan Array Reveals Abnormal Anti-GD1b Auto-antibody in Plasma of Preclinical Huntington’s Disease - Tien-Wei Lin; Jung-Kai Chang; Yih-Ru Wu; Tsung-Hsien Sun; Yang-Yu Cheng; Chien-Tai Ren; Mei-Hung Pan; Jin-Lin Wu; Kuo-Hsuan Chang; Hwai-I Yang; Chiung-Mei Chen; Chung-Yi Wu; et al. (Molecular Neurobiology, 2023)

Planning the temporary takeoff/landing site’s location for a pesticide spraying helicopter based on an intelligent fusion algorithm - Shuping Fang; Yu Ru; Chenming Hu; Fengbo Yang; Jiangkun Xue; Jie Zhou (Computers and Electronics in Agriculture, 2023)

Insights into differences between spore-assisted and pellet-assisted microalgae harvesting using a highly efficient fungus: Efficiency, high-value substances, and mechanisms - Qian-Ru Wang; Yu Hong; Li-Hua Li (Science of The Total Environment, 2023)

Soil erosion effectively alleviated by Miscanthus sacchariflorus, a potential candidate for land deterioration improvement - Chu Zhao; Yu-han Nie; Jian-pan Xin; Xiao-yu Zhu; Yan Li; Ru-nan Tian (Rhizosphere, 2023)

D-π-A array structure of Bi4Ti3O12-triazine-aldehyde group benzene skeleton for enhanced photocatalytic uranium (VI) reduction - Xin Liu; Rui-Xiang Bi; Feng-Tao Yu; Cheng-Rong Zhang; Qiu-Xia Luo; Ru-Ping Liang; Jian-Ding Qiu (Journal of Hazardous Materials, 2023)

An effective tool for tracking steroids and their metabolites at the watershed level: Combining fugacity modeling and a chemical indicator - Ru Xu; Shan Liu; Hui Chen; Qin-Wei Hao; Yong-Xia Hu; Heng-Xiang Li; Lang Lin; Rui Hou; Bing Hong; Shen Yu; Xiang-Rong Xu (Environmental Pollution, 2023)

Molybdenum carbide changes the abundance of antibiotic resistance genes and bacterial communities in bioelectrocatalytic systems treating wastewater contaminated by tetracycline - Yi Shao; Yu-Xiang Lu; Shi-Ru Gao; Bolun Xie; Xiao-Li Yang; Hai-Liang Song (Bioresource Technology Reports, 2023)

Ndufa4 Regulates the Proliferation and Apoptosis of Neurons via miR-145a-5p/Homer1/Ccnd2 - Fang Fu; Chen Chen; Kun Du; Lu-shan Li; Ru Li; Ting-ying Lei; Qiong Deng; Dan Wang; Qiu-xia Yu; Xin Yang; Jin Han; Min Pan; et al. (Molecular Neurobiology, 2023)
The Dandy–Walker malformation (DWM) is characterized by neuron dysregulation in embryonic development; however, the regulatory mechanisms associated with it are unclear. This study aimed to investigate the role of NADH dehydrogenase 1 alpha subcomplex 4 (NDUFA4) in regulating downstream signaling cascades and neuronal proliferation and apoptosis. Ndufa4 overexpression promoted the proliferation of neurons and inhibited their apoptosis in vitro, which underwent reverse regulation by the Ndufa4 short hairpin RNAs. Ndufa4 -knockout (KO) mice showed abnormal histological alterations in the brain tissue, in addition to impaired spatial learning capacity and exploratory activity. Ndufa4 depletion altered the microRNA expressional profiles of the cerebellum: Ndufa4 inhibited miR-145a-5p expression both in the cerebellum and neurons. miR-145a-5p inhibited the proliferation of neurons and promoted their apoptosis. Ndufa4 promoted and miR-145a-5p inhibited the expression of human homer protein homolog 1 and cyclin D2 in neurons. Thus, Ndufa4 promotes the proliferation of neurons and inhibits their apoptosis by inhibiting miR-145a-5p, which directly targets and inhibits the untranslated regions of Homer1 and Ccnd2 expression.

Molecular mechanism of Rhubarb in the treatment of non-small cell lung cancer based on network pharmacology and molecular docking technology - Ye-Ru Tan; Yu Lu (Molecular Diversity, 2023)

Prenatal diagnosis in the fetal hyperechogenic kidneys: assessment using chromosomal microarray analysis and exome sequencing - Ruibin Huang; Fang Fu; Hang Zhou; Lu Zhang; Tingying Lei; Ken Cheng; Shujuan Yan; Fei Guo; You Wang; Chunling Ma; Ru Li; Qiuxia Yu; et al. (Human Genetics, 2023)

The coupling of graphene, graphitic carbon nitride and cellulose to fabricate zinc oxide-based sensors and their enhanced activity towards air pollutant nitrogen dioxide - Hua-Min Xiao; Yu-Chang Hou; Yuan-Ru Guo; Qing-Jiang Pan (Chemosphere, 2023)

Dissolved biochar fractions and solid biochar particles inhibit soil acidification induced by nitrification through different mechanisms - Ren-Yong Shi; Ni Ni; Ru-Hai Wang; Jackson Nkoh Nkoh; Xiao-Ying Pan; Ge Dong; Ren-Kou Xu; Xiu-Min Cui; Jiu-Yu Li (Science of The Total Environment, 2023)

Renewable pickering emulsion system based on bifunctional materials for highly efficient fuel oil desulfurization without stirring - Shuai-Yong Dou; Jia-Yu An; Yan-Ru Feng; Kang Liu; Xuan Wang; Bo-Wen Zhang; Jing-Xuan Zhang; Er-Hong Duan; Ai-Bin Kang (Fuel, 2023)

The effects of pulsed electric fields treatment on the structure and physicochemical properties of dialdehyde starch - Ying Li; Jin-Hua Wang; Yu Han; Fu-Hao Yue; Xin-An Zeng; Bo-Ru Chen; Man-Qin Zeng; Meng-Wai Woo; Zhong Han (Food Chemistry, 2023)

Planning of takeoff/landing site location, dispatch route, and spraying route for a pesticide application helicopter - Fang Shuping; Ru Yu; Hu Chenming; Yang Fengbo (European Journal of Agronomy, 2023)

Electrochemical etching induced high-valence cobalt with defects site for boosting electrochemical water splitting - Hongmei Gao; Jiaqi Liu; Zijin Zhang; Yuxuan Lu; Ru Chen; Yu-Cheng Huang; Chao Xie; Mengyi Qiu; Tianyu Wu; Jinbo Wang; Yubin Jiang; Chung-Li Dong; et al. (Chemical Engineering Journal, 2023)

QTL-seq and transcriptomic integrative analyses reveal two positively regulated genes that control the low-temperature germination ability of MTP–maize introgression lines - Ru-Yu He; Jun-Jun Zheng; Yu Chen; Ze-Yang Pan; Tao Yang; Yang Zhou; Xiao-Feng Li; Xinyi Nan; Ying-Zheng Li; Ming-Jun Cheng; Yan Li; Yang Li; et al. (Theoretical and Applied Genetics, 2023)

A volatile producing Bacillus subtilis strain from the rhizosphere of Haloxylon ammodendron promotes plant root development - Ao-Lei He; Ling-Yu Zhao; Wei Ren; Hui-Ru Li; Paul W. Paré; Qi Zhao; Jin-Lin Zhang (Plant and Soil, 2023)

Methylated Chromenoquinoline as a Novel Nucleus Fluorescent Probe for Nucleic Acid Imaging - Zhi-Hao Zhang; Qing Yu; Gang Zhang; Hai-Yan Peng; Ru Sun; Yu-Jie Xu; Jian-Feng Ge (Journal of Fluorescence, 2023)

Circulating polyunsaturated fatty acids, fish oil supplementation, and risk of incident dementia: a prospective cohort study of 440,750 participants - Yu He; Shu-Yi Huang; Hui-Fu Wang; Wei Zhang; Yue-Ting Deng; Ya-Ru Zhang; Qiang Dong; Jian-Feng Feng; Wei Cheng; Jin-Tai Yu (GeroScience, 2023)

mRNA 3ʹ -UTR-mediate translational control through PAS and CPE in sheep oocyte - Chun-Ru Song; Ru-Jing Zhang; Fang-Rui Xue; Xiao-Jie Zhang; Xing-Yue Wang; Dui Sun; Kang Ding; Qi Yang; Xin-Yu Wang; Cheng-Guang Liang (Theriogenology, 2023)

Magnetic ternary layered double hydroxides for efficient removal of 1-naphthalene acetic acid from waters: Adsorption behavior and mechanism - Ti-Bo Fang; Hua Xiao; Ling-Xi Zhao; Na Li; Ling-Yu Luan; Zhao-Xing Yan; Jin-Ming Lin; Ru-Song Zhao (Journal of Environmental Chemical Engineering, 2023)

Effect of nanoclay supported nanosilver on the growth inhibition of aquatic pathogens and immunomodulatory effect in Penaeus vannamei - Zhen-Hao Liao; Huai-Ting Huang; Yu-Ru Lin; Chi-Yun Hu; Yu-Hsuan Kai; Jiang-Jen Lin; Fan-Hua Nan (Fish & Shellfish Immunology, 2023)

Mechanical properties of auxetic circular and square tubes filled with aluminum foam - Ru Yuan Huo; Dong Han; Yi Zhang; Wei Jiang; Le Yang Fan; Xin Wei Peng; Ge Chen Jie Shi; Ming Hao Chu; Xiang Yu Zhang; Yi Min Xie; Xin Ren (Engineering Structures, 2023)

A comprehensive understanding of adaptive thermal comfort in dynamic environments – An interaction matrix-based path analysis modeling framework - Ru Ming; Baizhan Li; Chenqiu Du; Wei Yu; Hong Liu; Risto Kosonen; Runming Yao (Energy and Buildings, 2023)

Application of microbial-induced carbonate precipitation (MICP) techniques to remove heavy metal in the natural environment: A critical review - Amit Kumar; He-Wei Song; Saurabh Mishra; Wei Zhang; Yu-Ling Zhang; Qian-Ru Zhang; Zhi-Guo Yu (Chemosphere, 2023)

Efficient coupling of sulfadiazine removal with microalgae lipid production in a membrane photobioreactor - Feng Gao; Jin-Long Zhou; Yu-Ru Zhang; Ashiwin Vadiveloo; Qing-Guo Chen; Jun-Zhi Liu; Qiao Yang; Ya-Ming Ge (Chemosphere, 2023)

Halogen microregulation in metal-organic frameworks for enhanced adsorption performance of ReO4-/TcO4- - Qing-Hua Hu; You-Gan Wang; Xin Gao; Yu-Zhen Shi; Sen Lin; Ru-Ping Liang; Jian-Ding Qiu (Journal of Hazardous Materials, 2023)

Self-oxidation cycle of oxidized red phosphorus for regeneration of binding sites enables efficient uranium extraction in tributylphosphate-kerosene system - Yingtong Lv; Ru Cheng; Guolin Yang; Wang Liu; Jingye Zhang; Xiaofang Yu; Wencai Bai; Rong He; Wenkun Zhu (Chemical Engineering Journal, 2023)

P2Y1R and P2Y2R: potential molecular triggers in muscle regeneration - Min-Jia Wang; Bi-Ru Yang; Xin-Yu Jing; Yao-Zheng Wang; Lu Kang; Kai Ren; Liang Kang (Purinergic Signalling, 2023)
Muscle regeneration is indispensable for skeletal muscle health and daily life when injury, muscular disease, and aging occur. Among the muscle regeneration, muscle stem cells’ (MuSCs) activation, proliferation, and differentiation play a key role in muscle regeneration. Purines bind to its specific receptors during muscle development, which transmit environmental stimuli and play a crucial role of modulator of muscle regeneration. Evidences proved P2R expression during development and regeneration of skeletal muscle, both in human and mouse. In contrast to P2XR, which have been extensively investigated in skeletal muscles, the knowledge of P2YR in this tissue is less comprehensive. This review summarized muscle regeneration via P2Y1R and P2Y2R and speculated that P2Y1R and P2Y2R might be potential molecular triggers for MuSCs’ activation and proliferation via the p-ERK1/2 and PLC pathways, explored their cascade effects on skeletal muscle, and proposed P2Y1/2 receptors as potential pharmacological targets in muscle regeneration, to advance the purinergic signaling within muscle and provide promising strategies for alleviating muscular disease.

Engelheptanoxides behave as liver X receptor α agonists - Yu-Hsuan Liang; Yu-Han Luo; Ih-Sheng Chen; Hsiang-Ru Lin (Medicinal Chemistry Research, 2023)

Whole exome sequencing improves genetic diagnosis of fetal clubfoot - Ruibin Huang; Hang Zhou; Chunling Ma; Fang Fu; Ken Cheng; You Wang; Ru Li; Tingying Lei; Qiuxia Yu; Dan Wang; Shujuan Yan; Xin Yang; et al. (Human Genetics, 2023)

Dynamic changes in cell wall-degrading enzymes and physio-biochemistry of ginseng in response to fusarium oxysporum infection - Lin Feng; Guijia Zhao; Ru Sun; Jifeng Wang; Tianxia Sun; Shuyang Xing; Wenhui Lian; Yu Zhao (European Journal of Plant Pathology, 2023)

Can technological finance cooperation pilot policy improve energy efficiency? Evidence from a quasi-experiment in China - Bin Zhao; Ru-Yu Xu (Environmental Science and Pollution Research, 2023)

Condition optimization of iron-air fuel cell to treat phosphate-containing wastewater regarding sustainable development - Ling-ling Lai; Chao Liu; Meng-yu Liu; Si-zhuo Wan; Zhi-guo Zhao; Ru Wang; Lin-jiang Yuan (Chemosphere, 2023)

Genomic analysis of Marinimicrobium sp. C6131 reveals its genetic potential involved in chitin metabolism - Yan-Ru Dang; Xiao-Yu Zhang; Sha-Sha Liu; Ping-Yi Li; Xue-Bing Ren; Qi-Long Qin (Marine Genomics, 2023)

Response of activated sludge to antibiotics stress: Neglected legacy effects - Zhong-Xing Zhang; Xiao-Yan Fan; Xing Li; Yu-Xi Gao; Jun-Ru Zhao (Journal of Water Process Engineering, 2023)

The preparation of Co/γ-Al2O3 and treatment of cartap pesticide wastewater by microwave catalytic oxidation - Jia Ru Dai; Kai Xuan Liu; Fang Lian; Xue Peng Tian; Yu Feng Zhang (Journal of Water Process Engineering, 2023)

Restrictions on Niobium enrichment by alteration of Niobium-rich biotite in pure water, acid, alkaline and fluoride-bearing solutions at 200 MPa and 300–600 °C - Zhao-Yu Yang; Ru-Cheng Wang; Xu-Dong Che; Daniel Harlov (Geochimica et Cosmochimica Acta, 2023)

COSEν: A collective oscillation simulation engine for neutrinos - Manu George; Chun-Yu Lin; Meng-Ru Wu; Tony G. Liu; Zewei Xiong (Computer Physics Communications, 2023)

Molecular characterization of humic-like substances (HULIS) in atmospheric particles (PM2.5) in offshore Eastern China Sea (OECS) using solid-phase extraction coupled with ESI FT-ICR MS - Hao Sun; Zilan Wu; Xinyuan Kang; Chao Zhu; Limin Yu; Ru Li; Zhongsheng Lin; Jianmin Chen (Atmospheric Environment, 2023)

Plant growth-promoting properties of the phosphate-solubilizing red yeast Rhodosporidium paludigenum - Yi-Ru Chen; Chih-Yen Kuo; Shih-Feng Fu; Jui-Yu Chou (World Journal of Microbiology and Biotechnology, 2023)
Phosphorus (P) is one of the essential elements that are necessary for plant development and growth. However, the availability of soluble forms of P for plants in the soils is limited, because a large proportion of it is bound to soil constituents. Thus, the concentration of P available to plants at any time is very low and, moreover, its availability depends on the soil pH. As a solution, phosphate-solubilizing microorganisms (PSMs) are employed that render inorganic P available to plants in soluble form. Thus far, research into PSMs has been insufficient, and only few such organisms have been considered for exploitation as microbial fertilizer strains. The characteristics of plant growth promotion with the plant-PSMs coculture system remain to be elucidated. In the current study, we report on the isolate Rhodosporidium paludigenum JYC100 that exhibits good performance for solubilizing calcium phosphate. We found that it can be regulated by the amount of soluble phosphate. Furthermore, R . paludigenum JYC100 promotes plant growth under specific conditions (P deficiency, but with insoluble phosphate) in different media and soil pots. In contrast, the yeast Aureobasidium pullulans JYC104 exhibited weak phosphate-solubilizing capacities and no plant growth-promoting ability. Compared to control plants, the biomass, shoot height, and cellular inorganic P content of plants increased in plants cocultivated with R . paludigenum JYC100. In addition, histochemical GUS and qRT-PCR assays of phosphate starvation-induced (PSI) genes showed that the transcript levels of these PSI genes are decreased in the plants cocultured with R . paludigenum JYC100. These findings reflect the unique ability of R . paludigenum JYC100 to convert insoluble P compounds to plant-available P, thereby leading to growth promotion. Our study results highlight the use of yeasts as potential substitutes for inorganic phosphate fertilizers to meet the P demands of plants, which may eventually improve yields in sustainable agricultures.

Analysis of Whole Blood and Urine Trace Elements in Children with Autism Spectrum Disorders and Autistic Behaviors - Gang Zhao; Si-jin Liu; Xin-yu Gan; Jun-ru Li; Xiao-xue Wu; Si-yan Liu; Yi-si Jin; Ke-rang Zhang; Hong-mei Wu (Biological Trace Element Research, 2023)
The relationship between trace elements and neurological development is an emerging research focus. We performed a case–control study to explore (1) the differences of 13 trace elements chromium (Cr), manganese (Mn), cobalt (Co), zinc (Zn), arsenic (As), selenium (Se), molybdenum (Mo), cadmium (Cd), stannum (Sn), stibium (Sb), mercury (Hg), titanium (TI), and plumbum (Pb) concentration in whole blood and urine between autism spectrum disorder (ASD) children and their typical development peers, and (2) the association between the 13 trace elements and core behaviors of ASD. Thirty ASD subjects (cases) and 30 age-sex-matched healthy subjects from Baise City, Guangxi Zhuang Autonomous Region, China, were recruited. Element analysis was carried out by inductively coupled plasma-optical emission spectrometry. Autistic behaviors were assessed using Autism Behavior Checklist (ABC), Childhood Autism Rating Scale (CARS), and Children Neuropsychological and Behavior Scale (CNBS). The whole blood concentrations of Mo ( p = 0.004), Cd (0.007), Sn ( p = 0.003), and Pb ( p = 0.037) were significantly higher in the ASD cases than in the controls. Moreover, Se (0.393), Hg (0.408), and Mn (− 0.373) concentrations were significantly correlated between whole blood and urine levels in ASD case subjects. There were significant correlations between whole blood Sb (0.406), Tl (0.365), Mo (− 0.4237), Mn (− 0.389), Zn (0.476), and Se (0.375) levels and core behaviors of ASD. Although the mechanism of trace element imbalance in ASD is unclear, these data demonstrate that core behaviors of ASD may be affected by certain trace elements. Further studies are recommended for exploring the mechanism of element imbalance and providing corresponding clinical treatment measures.

Combined effect of Cu- and ZnO- NPs on antibiotic resistance genes in an estuarine water - Yu-ru Chen; Rong-rong Sha; Xiao-li Sun; Xing-pan Guo; Yi Yang (Frontiers in Marine Science, 2023)
Most studies of whether and how nanoparticles (NPs) affect antibiotic resistance genes (ARGs) focus on testing single NPs type. In this study, we determined the combined effect of Cu- and ZnO- NPs in the water samples collected from the Yangtze River Estuary and found the effect differs greatly from that produced by individual NPs. The results showed that the Cu- and ZnO- NPs co-exposure resulted in an enrichment of ARGs, whereas individual Cu- and ZnO- NPs exposure decreased the abundance of ARGs. Furthermore, the co-exposure of Cu- and ZnO- NPs induced obvious changes in the microbial communities compared to the control communities. Redundancy analysis suggested that the microbial community contributed the most (43.5%) to the ARG profiles, followed by dissolved metal ions (25.7%), MRGs, (19.4%), and MGEs (4.4%). Network analysis found several potential hosts (such as Mycobacterium and Escherichia coli ) and implied the extent of the risk of ARG transmission into various environmental niches by these common microbes.

Fiscal decentralization, industrial structure upgrading, and carbon emissions: evidence from China - Bin Zhao; Ke-Liang Wang; Ru-Yu Xu (Environmental Science and Pollution Research, 2023)

Zero-valent iron boosts nitrate-to-ammonia bioconversion via extracellular electron donation and reduction pathway complementation - Xue Li; Jie Li; Xiao-Rong Yu; Yong-Kun Zhu; Hou-Qi Liu; Lin Chen; Jing Wu; Xian-Zhong Fu; Shuo Cui; Tian-Yin Huang; Ru-Quan Ye; Wen-Wei Li (Resources, Conservation and Recycling, 2023)

Comparison of biochemical composition, nutritional quality, and metals concentrations between males and females of three different Crassostrea sp. - Yanping Qin; Ru Li; Qingliang Liao; Gongpengyang Shi; Yinyin Zhou; Weitao Wan; Jun Li; Haitao Ma; Yuehuan Zhang; Ziniu Yu (Food Chemistry, 2023)

Luteolin ameliorates palmitate-induced lipotoxicity in hepatocytes by mediating endoplasmic reticulum stress and autophagy - Chun-Yin Huang; Haw-Wen Chen; Chia-Wen Lo; Yu-Ru Wang; Chien-Chun Li; Kai-Li Liu; Chong-Kuei Lii (Food and Chemical Toxicology, 2023)

The associations of particulate matter short-term exposure and serum lipids are modified by vitamin D status: A panel study of young healthy adults - Jia-Min Li; Han-Yu Yang; Si-Han Wu; Shyamali C. Dharmage; Bin Jalaludin; Luke D. Knibbs; Michael S. Bloom; Yuming Guo; Lidia Morawska; Joachim Heinrich; Yim Steve Hung Lam; Li-Zi Lin; et al. (Environmental Pollution, 2023)

Association between long-term ambient ozone exposure and attention-deficit/hyperactivity disorder symptoms among Chinese children - Peien Zhou; Wangjian Zhang; Yu-Jie Xu; Ru-Qing Liu; Zhengmin Qian; Stephen Edward McMillin; Elizabeth Bingheim; Li-Zi Lin; Xiao-Wen Zeng; Bo-Yi Yang; Li-Wen Hu; Wen Chen; et al. (Environmental Research, 2023)

Antimicrobial peptide hepcidin contributes to restoration of the intestinal flora after Aeromonas hydrophila infection in Acrossocheilus fasciatus - Qun-Yin Zhu; Ru-Yi Chen; Jing Yu; Guo-Hua Ding; Rachel Wan Xin Seah; Jie Chen (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2023)

Identifying the impact of Fe nanoparticles encapsulated by nitrogen-doped carbon to Fe single atom sites for boosting oxygen reduction reaction toward Zn-air batteries - Wen-Jun Niu; Ying-Yun Yan; Ru-Ji Li; Wei-Wei Zhao; Jiang-Lei Chen; Ming-Jin Liu; Bingni Gu; Wen-Wu Liu; Yu-Lun Chueh (Chemical Engineering Journal, 2023)

Realizing the bifunctional electrocatalysis via local charge rearrangement of α-CrOOH-modulated Co@CoMoOx for overall water splitting - Suh-Ciuan Lim; Chao-Lung Chiang; Chun-Kuo Peng; Wen-Bin Wu; Yu-Chang Lin; Yu-Ru Lin; Chi-Liang Chen; Yan-Gu Lin (Chemical Engineering Journal, 2023)

Recyclable nanocomposites for carbon dioxide fixation and membrane separation using waste polycarbonate - Ying-Chi Huang; Li-Fan Chen; Yu-Hsiang Huang; Chien-Chieh Hu; Chien-Hsin Wu; Ru-Jong Jeng (Chemical Engineering Journal, 2023)

Efficient microalgal lipid production driven by salt stress and phytohormones synergistically - Zi-Yan Yang; Kai-Xuan Huang; Yu-Ru Zhang; Lei Yang; Jin-Long Zhou; Qiao Yang; Feng Gao (Bioresource Technology, 2023)

Bisphenols induce cardiotoxicity in zebrafish embryos: Role of the thyroid hormone receptor pathway - Jing-Yu Qin; Wenyi Jia; Shaoguo Ru; Jiu-Qiang Xiong; Jun Wang; Weiwei Wang; Liping Hao; Xiaona Zhang (Aquatic Toxicology, 2023)

A Bounded Near-Bottom Cruise Trajectory Planning Algorithm for Underwater Vehicles - Jingyu Ru; Han Yu; Hao Liu; Jiayuan Liu; Xiangyue Zhang; Hongli Xu (Journal of Marine Science and Engineering, 2022)
The trajectory planning algorithm of underwater vehicle near-bottom cruise is important to scientific investigation, industrial inspection, and military affairs. An autonomous underwater vehicle (AUV) often faces the problems of complex underwater environment and large cruise area in a real environment, and some robots must hide themselves during the cruise. However, to the best of our knowledge, few studies have focused on trajectory planning algorithms for AUVs with multiple constraints on large-scale maps. The currently used algorithms are not effective at solving length-constraint problems, and the mainstream trajectory planning algorithms for robots cannot be directly applied to the needs of underwater vehicle sailing near the bottom. Therefore, we present a bounded ridge-based trajectory planning algorithm (RA*) for an AUV to go on a near-bottom cruise. In the algorithm, we design a safety map based on a spherical structure to ensure the safe operation of the robot. In addressing the length-constraint problem and large-scale map planning problem, this paper proposes a two-stage framework for RA*, which designs map compression and parallel computation using a coarse-fine planning framework to solve the large-scale trajectory planning problem and uses a bounded search method to meet the trajectory planning requirements of length constraint. In this study, experiments based on the virtual ocean ridge are conducted, and the results validate the effectiveness and efficiency of the proposed RA* with MCPC algorithm framework.

Cryo-EM structures reveal the dynamic transformation of human alpha-2-macroglobulin working as a protease inhibitor - Xiaoxing Huang; Youwang Wang; Cong Yu; Hui Zhang; Qiang Ru; Xinxin Li; Kai Song; Min Zhou; Ping Zhu (Science China Life Sciences, 2022)

An alkali-resistant metal–organic framework as halogen bond donor for efficient and selective removing of ReO4−/TcO4− - Qing-Hua Hu; Yu-Zhen Shi; Xin Gao; Li Zhang; Ru-Ping Liang; Jian-Ding Qiu (Environmental Science and Pollution Research, 2022)

Recent advances in biotechnological production of polyunsaturated fatty acids by Yarrowia lipolytica - Yu-Lei Jia; Ling-Ru Wang; Zi-Xu Zhang; Yang Gu; Xiao-Man Sun (Critical Reviews in Food Science and Nutrition, 2022)

The impact of low-carbon city pilot policy on green total-factor productivity in China’s cities - Ke-Liang Wang; Jin Li; Ru-Yu Xu; Su-Qin Pang; Zhuang Miao; Hua-Ping Sun (Environmental Science and Pollution Research, 2022)

Involvement of osmoregulation, glyoxalase, and non-glyoxalase systems in signaling molecule glutamic acid-boosted thermotolerance in maize seedlings - Xue-Mei Qiu; Yu-Ying Sun; Jia-Qi Wang; Ru-Hua Xiang; Zhong-Guang Li (Protoplasma, 2022)

The Key Role of Magnetic Resonance Imaging in the Detection of Neurodegenerative Diseases-Associated Biomarkers: A Review - Ke-Ru Li; An-Guo Wu; Yong Tang; Xiao-Peng He; Chong-Lin Yu; Jian-Ming Wu; Guang-Qiang Hu; Lu Yu (Molecular Neurobiology, 2022)

High- and low-temperature fracture behavior of pervious asphalt mixtures under different freeze–thaw cycles based on acoustic emission technique - Tianmin Wang; Yu Chen; Changqi Zhu; Haifeng Liu; Chenghao Ma; Xing Wang; Ru Qu (Arabian Journal of Geosciences, 2022)

Siccirubricoccus soli sp. nov., a novel bacterial species isolated from Jiaozi Mountain soil - Guo-Xing Zhu; Ya-Jie Wu; Yan-Ru Cao; Bing-Jun Fan; Yu Jiao; Xiu-Li Hou; Zi-Chao Liu; Yue Zhang; Jiang-Bo He; Lian-Ming Liang (Antonie van Leeuwenhoek, 2022)

Bragg-region recognition of high-frequency radar spectra based on deep learning and image fusion processing - Laurence Zsu-Hsin Chuang; Yu-Ru Chen; Yu-Jen Chung; Li-Chung Wu; Tsung-Mo Tien (International Journal of Remote Sensing, 2022)

Deletions in GSN gene associated with growth traits of four Chinese cattle breeds - Ao Qi; Wenxiu Ru; Yangkai Liu; Yu Yang; Jia Tang; Haiyan Yang; Shuling Yang; Kaixing Qu; Xianyong Lan; Chuzhao Lei; Bizhi Huang; Hong Chen (Molecular Genetics and Genomics, 2022)

The Effect of Co-Exposure to Glyphosate, Cadmium, and Arsenic on Chronic Kidney Disease - Junne-Ming Sung; Wei-Hsiang Chang; Kuan-Hung Liu; Chung Yu Chen; Trias Mahmudiono; Wan-Ru Wang; Ho-Chi Hsu; Zhen-Yi Li; Hsiu-Ling Chen (Exposure and Health, 2022)

Age, Growth and Population Structure Analyses of the Purpleback Flying Squid Sthenoteuthis oualaniensis in the Northwest Indian Ocean by Beak Microstructure - Hua-Jie Lu; Yu-Zhe Ou; Jing-Ru He; Mao-Lin Zhao; Zi-Yue Chen; Xin-Jun Chen (Journal of Marine Science and Engineering, 2022)
To explore the feasibility of using beak microstructure information to estimate the age of Sthenoteuthis oualaniensis, the microstructures of the upper beaks of individual squid were applied in this work to analyze the ages and growth patterns of squid caught from February–May 2019 and from October–December 2020 in the northwest Indian Ocean. The results indicated that the squid samples in the two years were no older than 9 months, and the samples in 2019 were autumn population and 2020 were spring population. The linear growth model of the autumn population (2019) was the best model for describing the relationship between age and ML, while the power model of the spring population (2020) was the best for describing the relationship between age and ML. The maximum instantaneous growth rate (IGR) and absolute daily growth rate (AGR) values of the spring population were 0.24%/d and 1.09 mm/d, respectively, occurring in squid between 200 and 220 days of age. The maximum IGR and AGR values of the autumn population were 0.69%/d and 1.73 mm/d, respectively, occurring in squid between 200 and 240 days of age. The period from 141–260 days (5–8 months) was considered to correspond to the subadult stage in the whole life history of S. oualaniensis in the Northwest Indian Ocean. The beak microstructure information can be effectively applied to estimate the age of S. oualaniensis individuals.

Deciphering the Heterogeneity of Mitochondrial Functions During Hematopoietic Lineage Differentiation - Haoyue Liang; Shuxu Dong; Weichao Fu; Sen Zhang; Wenying Yu; Fang Dong; Baolin He; Jinhong Wang; Yingdai Gao; Yuan Zhou; Yongxin Ru (Stem Cell Reviews and Reports, 2022)

Traffic noise and adiposity: a systematic review and meta-analysis of epidemiological studies - Si-Yu Gui; Ke-Jia Wu; Yue Sun; Yue-Nan Chen; Huan-Ru Liang; Wen Liu; Yao Lu; Cheng-Yang Hu (Environmental Science and Pollution Research, 2022)

Lelliottia steviae sp. nov. isolated from Stevia rebaudiana Bertoni - Jing Lin; Ke Huang; Jing-Yu Huang; Yuan-Ru Xiong; Meng-Meng Wei; Na Xiao; Jia Gao; Xuan-Kai Ding; Zi-Yang Ma; Jun-Hao Sang; Ling-Xian Kong; Zhi-Yun Hong; et al. (Archives of Microbiology, 2022)

Spatiotemporal variations of seasonal temperature at different percentiles in the three provinces of northeast China from 1961 to 2019 - Yaxue Yang; Huixiao Wang; Changming Liu; Ru Feng; Yu Wang; Hongfang Li (International Journal of Climatology, 2022)
The three provinces of northeast China (NEPs) were one of the major grain producing areas in China and has undergone significant climate warming during past decades. However, nowadays researches on climate warming mostly focused on variations of mean temperature or temperature extremes, which missed much information in the other parts of temperature. Therefore, taken NEPs as study area, variations of maximum temperature (Tmax), minimum temperature (Tmin) and diurnal temperature range (DTR) at every 10% percentile from 1961 to 2019 in NEPs were analysed at seasonal scale. The abrupt changes and decadal shifts of Tmax, Tmin and DTR at different percentiles were further highlighted. Results show that (a) for either regional average or station cases, fluctuations of daily Tmax and daily Tmin both decreased in spring and winter, but increased in autumn. In summer, fluctuations of daily Tmin decreased while those of daily Tmax increased. (b) Spatially, Tmax heated up more in south of NEPs at lower percentiles, and in northwest of NEPs at higher percentiles in spring, summer and winter. Tmin and DTR overall showed consistent spatial differences that changes in north and northwest of NEPs were with greater magnitudes. (c) In spring and winter, the higher Tmax/Tmin had earlier abrupt changes than lower Tmax/Tmin, while in summer and autumn, the abrupt changes occurred earlier for lower Tmax/Tmin. (d) In winter, overwhelming positive shifts were significant before 2000, but turned negative after 2000. In summer, Tmax heated up quickly since 1990s and Tmin since 1980s. Shifts in spring and autumn varied during different periods and generally presented alternative warming at higher and lower percentiles. The research can help better depict the warming patterns and figure out the detailed warming procedures in NEPs, which is a strong supplement for current climate change research.

Dataset-based assessment of heavy metal contamination in freshwater fishes and their health risks - Xiao-Bo Liu; Congtian Lin; Yang-Yu Wu; Hai-Ning Huang; Li-Ting Zhu; Ru Jiang; Qiansheng Huang (Environmental Science and Pollution Research, 2022)

Detection of bloom-forming dinoflagellates Karenia mikimotoi and Prorocentrum donghaiense using qPCR assays - Xiao-Kun Hu; Zhuo-Ru Lin; Qing-Chun Zhang; Fan-Zhou Kong; Jing-Yi Cen; Yu-Lan Zeng; Ren-Cheng Yu (Journal of Applied Phycology, 2022)

Natural Feed Supplements Improve Growth, Non-Specific Immune Responses and Resistance against Vibrio alginolyticus in Lates calcarifer - Zhen-Hao Liao; Huai-Ting Huang; Yu-Ru Lin; Bo-Ying Chen; Yi-Fan Lee; Yuan-Heng Lin; Chieh-Yuan Chuang; Fan-Hua Nan (Journal of Marine Science and Engineering, 2022)
This study aimed to investigate the effects of dietary natural feed supplement on the growth performance, non-specific responses, and disease resistance in Lates calcarifer. Three commercial products (A, B, and C) containing a basal probiotic mixture were tested. Product A contained a basal mixture of Paenibacillus sp., Bacillus subtilis, Bacillus amyloliquefaciens, and Lactobacillus rhamnosus (107 cfu/g for each probiotic); product B contained additional Lactobacillus plantarum (1010 cfu/g); and product C contained additional soybean peptides (500 g/kg) and garlic powder (1 g/kg). Each product was supplemented into subject diets at dosages of 1 or 2 g/kg (designated as the A1, A2, B1, B2, C1, and C2 groups, respectively). Following an eight-week trial, growth parameters (specific growth rate and feed conversion ratio), non-specific immune responses (O2− production, phagocytic rate, and phagocytic index), and the results of a challenge test against Vibrio alginolyticus were evaluated. The results show that all probiotic supplement groups exhibited an improvement in growth performance compared to the control group (non-probiotic diet). In terms of non-specific immunity parameters, a significant improvement in O2− production was found in the C2 group, whereas significant improvements in phagocytic activity were found in all the B and C groups. The C2 group displayed optimal O2− production, phagocytic rate, and phagocytic index results. For the challenge test, the C groups showed higher Vibrio resistance than the other experimental groups and the control group. These results suggest that product C, given at dosages of 2 g/kg, may serve as a growth-promoting and immunostimulatory additive for the cultivation of Asian seabass.

A new highly oxygenated germacranolide from Carpesium nepalense var. lanatum (C.B.Clarke) Kitam - Yi-Fan Yu; Yue-Qian Li; Ru-Yue Wang; Xu Liu; Wen-Bo Cui; Xiao-Han Chen; Cheng-Mu Zhao; Feng-Ming Qi; Zhan-Xin Zhang; Dong-Qing Fei (Natural Product Research, 2022)

Wind speed retrieval from Chinese Gaofen-3 synthetic aperture radar using an analytical approach in the nearshore waters of China’s seas - Ru Yao; Weizeng Shao; Xingwei Jiang; Tan Yu (International Journal of Remote Sensing, 2022)

Haloterrigena gelatinilytica sp. nov., a new extremely halophilic archaeon isolated from salt-lake - Bing-Bing Liu; Nimaichand Salam; Manik Prabhu Narsing Rao; Shuang Cheng; Yuan-Guo Xie; Lai-You Wang; Yuan-ru Zhang; Xin-Yuan Yu; Shu-xian Guo; Wen-Jun Li (Archives of Microbiology, 2022)

Shape stable poly(vinyl alcohol) hydrogels with immobilized metal hexacyanoferrates for cesium removal from waters - Po-Hsun Wang; Yin-Ru Chang; Man-Li Chen; Yu-Kuo Lo; Duu-Jong Lee (Environmental Science and Pollution Research, 2022)

Soil moisture response to land use and topography across a semi-arid watershed: Implications for vegetation restoration on the Chinese Loess Plateau - Lu Xia; Ru-tian Bi; Xiao-yu Song; Wei Hu; Chun-juan Lyu; Xu Xi; Huai-you Li (Journal of Mountain Science, 2022)

Household environmental microbiota influences early‐life eczema development - Le Duc Huy Ta; Carina Jing Xuan Tay; Christophe Lay; Paola Florez de Sessions; Cheryl Pei Ting Tan; Michelle Jia Yu Tay; Hui Xing Lau; Atiqa Binte Zulkifli; Gaik Chin Yap; Elizabeth Huiwen Tham; Eliza Xin Pei Ho; Anne Eng Neo Goh; et al. (Environmental Microbiology, 2021)
Summary Exposure to a diverse microbial environment during pregnancy and early postnatal period is important in determining predisposition towards allergy. However, the effect of environmental microbiota exposure during preconception, pregnancy and postnatal life on development of allergy in the child has not been investigated so far. In the S‐PRESTO (Singapore PREconception Study of long Term maternal and child Outcomes) cohort, we collected house dust during all three critical window periods and analysed microbial composition using 16S rRNA gene sequencing. At 6 and 18 months, the child was assessed for eczema by clinicians. In the eczema group, household environmental microbiota was characterized by presence of human‐associated bacteria Actinomyces , Anaerococcus, Finegoldia, Micrococcus, Prevotella and Propionibacterium at all time points, suggesting their possible contributions to regulating host immunity and increasing the susceptibility to eczema. In the home environment of the control group, putative protective effect of an environmental microbe Planomicrobium ( Planococcaceae family) was observed to be significantly higher than that in the eczema group. Network correlation analysis demonstrated inverse relationships between beneficial Planomicrobium and human‐associated bacteria ( Actinomyces , Anaerococcus, Finegoldia, Micrococcus, Prevotella and Propionibacterium ). Exposure to natural environmental microbiota may be beneficial to modulate shed human‐associated microbiota in an indoor environment.

Recent progress of oridonin and its derivatives for cancer therapy and drug resistance - Yong-Feng Guan; Xiu-Juan Liu; Xiao-Jing Pang; Wen-Bo Liu; Guang -Xi Yu; Yin -Ru Li; Yan-Bing Zhang; Jian Song; Sai-Yang Zhang (Medicinal Chemistry Research, 2021)

Anti-miR33 therapy improved hepatopancreatic lipid and immune metabolism disorders in grass carp, Ctenopharyngodon idella - Rong-Hua Lu; Meng-Jun Lin; Feng Yang; Shen-zong Jia; Yu-Ru Zhang; Chao-Bin Qin; Xiao-Lin Meng; Guo-Xing Nie (Fish Physiology and Biochemistry, 2021)

Interactive effects of nutrient availability, fluctuating supply, and plant parasitism on the post-invasion success of Bidens pilosa - Fang-Lei Gao; Qiao-Sheng He; Ru-Qian Xie; Jia-Hui Hou; Chen-Lu Shi; Jun-Min Li; Fei-Hai Yu (Biological Invasions, 2021)

The occurrence order and cross-talk of different tRNA modifications - Jing Li; Wen-Yu Zhu; Wen-Qing Yang; Cai-Tao Li; Ru-Juan Liu (Science China Life Sciences, 2021)

Transport patterns and numerical simulation of heavy metal pollutants in soils of lead-zinc ore mines - Jie Cao; Cheng-yu Xie; Zhi-ru Hou (Journal of Mountain Science, 2021)

LncRNA TUG1 exhibits pro-fibrosis activity in hypertrophic scar through TAK1/YAP/TAZ pathway via miR-27b-3p - Xian-Min Li; Wen-Yuan Yu; Qi Chen; Hui-Ru Zhuang; Su-Yue Gao; Tian-Lan Zhao (Molecular and Cellular Biochemistry, 2021)

A Multi-AUV Path Planning System Based on the Omni-Directional Sensing Ability - Jingyu Ru; Shuangjiang Yu; Hao Wu; Yuhan Li; Chengdong Wu; Zixi Jia; Hongli Xu (Journal of Marine Science and Engineering, 2021)
Following the development of autonomous underwater vehicles (AUVs), multiple trajectory-based submarine target information collection constitutes one of the key technologies that significantly influence underwater information collection ability and deployment efficiency. In this paper, we propose an underwater information collection AUV, O-AUV, that can perceive the omnidirectional area and could detect a larger area than the traditional AUV. A 3D sensing model for the O-AUV is proposed to describe the complex underwater information collection spaces. Thereafter, a cube-based environment model involving candidate observation point calculation methods are suggested to adapt the O-AUV model. A voyage cost map is also built according to the multi-AUV path planning for a common submarine mission that must traverse numerous mission targets in complex environments through the R-Dijkstra algorithm. Specifically, the voyage planning problem is solved through a critical algorithm called ANSGA (accelerated NSGA-II algorithm), which in turn, is developed by modifying the non-dominated sorting genetic algorithm (NSGA-II) to accelerate the optimization rate for the Pareto solution. Experiments are carried out in MATLAB, and the results verify the validity of the proposed O-AUV+ANSGA algorithm framework.

Numerical Study on Interaction between Submarine Landslides and a Monopile Using CFD Techniques - Ru-Yu Li; Jin-Jian Chen; Chen-Cong Liao (Journal of Marine Science and Engineering, 2021)
Offshore installations with pile foundations in shallow water are vulnerable to submarine landslides, which cause serious damage to engineering facilities, loss of life, and loss of money. Due to a shortage of real observation data and the difficulty of reproduction, we lack insight into the interaction behavior between submarine landslides and monopiles. This study capitalized on ANSYS Fluent 20.0 to develop a three-dimensional biphasic (water and slurry) numerical model. This CFD model was used to analyze the interaction between a monopile and submarine landslides at different flow heights. The velocities of submarine landslides were from low to high values. Two modes of interactional forces acting on the monopile are proposed, which are (i) interaction force with peak value and (ii) interaction force without peak value. The influence of flow height and velocity on interaction forces was investigated. Results show that the effect of the flow heights on the interaction force is significant at low velocity stage, while the peak force representing a hazard level of the pile was non-negligible under high flow velocity and low flow height conditions, which should be considered in a future study. The related mechanisms are revealed with a hybrid model considering different components of the force.

Genetic Analysis of ZNF Protein Family Members for Early-Onset Parkinson’s Disease in Chinese Population - Chun Yu Li; Ru Wei Ou; Yong Ping Chen; Xiao Jing Gu; Qian Qian Wei; Bei Cao; Ling Yu Zhang; Yan Bing Hou; Kun Cheng Liu; Xue Ping Chen; Wei Song; Bi Zhao; et al. (Molecular Neurobiology, 2021)

Marinifaba aquimaris gen. nov., sp. nov., a novel chitin‐degrading gammaproteobacterium in the family Alteromonadaceae isolated from seawater of the Mariana Trench - Xin Sui; Xiao-yan He; Ning-hua Liu; Yan-ru Dang; Qian-qian Cha; Mei-ling Sun; Chun-yang Li; Hui-hui Fu; Xiao-yan Song; Qi-long Qin; Xiu-lan Chen; Yu-zhong Zhang; et al. (Antonie van Leeuwenhoek, 2021)

The Knowledge and Attitude Towards Advance Care Planning Among Chinese Patients with Advanced Cancer - Xiao-Ting Hou; Yu-Han Lu; Hong Yang; Ren-Xiu Guo; Yun Wang; Li-Hong Wen; Ya-Ru Zhang; Hong-Yu Sun (Journal of Cancer Education, 2021)

Prediction of oral hepatotoxic dose of natural products derived from traditional Chinese medicines based on SVM classifier and PBPK modeling - Size Li; Yiqun Yu; Xiaolan Bian; Li Yao; Min Li; Yan-Ru Lou; Jing Yuan; Hai-shu Lin; Lucy Liu; Bing Han; Xiaoqiang Xiang (Archives of Toxicology, 2021)

Genome sequencing and functional annotation of Bacillus sp. strain BS-Z15 isolated from cotton rhizosphere soil having antagonistic activity against Verticillium dahliae - Zhong-Yi Chen; Xieerwanimu Abuduaini; Nuramina Mamat; Qi-Lin Yang; Meng-Jun Wu; Xin-Rui Lin; Ru Wang; Rong-Rong Lin; Wei-Jun Zeng; Huan-Chen Ning; He-Ping Zhao; Jin-Yu Li; et al. (Archives of Microbiology, 2021)

Selective Ferroptosis Inhibitor Liproxstatin-1 Attenuates Neurological Deficits and Neuroinflammation After Subarachnoid Hemorrhage - Yang Cao; Yin Li; Chao He; Feng Yan; Jian-Ru Li; Hang-Zhe Xu; Jian-Feng Zhuang; Hang Zhou; Yu-Cong Peng; Xiong-Jie Fu; Xiao-Yang Lu; Yuan Yao; et al. (Neuroscience Bulletin, 2021)

Genetic Analysis of Prosaposin, the Lysosomal Storage Disorder Gene in Parkinson’s Disease - Yong-Ping Chen; Xiao-Jing Gu; Ru-Wei Ou; Ling-Yu Zhang; Yan-Bing Hou; Kun-Cheng Liu; Bei Cao; Qian-Qian Wei; Wei Song; Bi Zhao; Ying Wu; Jing-Qiu Cheng; et al. (Molecular Neurobiology, 2021)

Tracing consumption patterns of stimulants, opioids, and ketamine in China by wastewater-based epidemiology - Si-Yu Liu; Wen-Jing Yu; Yi-Ru Wang; Xue-Ting Shao; De-Gao Wang (Environmental Science and Pollution Research, 2021)

Re-use of wasted sludge to treat industrial pollutants - Ru Wang; Li-ping Yu; Bibi Saima Zeb; Lin-jie Yuan; Meng-yu Liu; Lin-jiang Yuan (Water, Air, & Soil Pollution, 2021)

Brominated and phosphate flame retardants from interior and surface dust of personal computers: insights into sources for human dermal exposure - Lehuan Yu; Shuling Ru; Xiaobo Zheng; Shejun Chen; Huiying Guo; Guijuan Gao; Yuan Zeng; Yijie Tang; Bixian Mai (Environmental Science and Pollution Research, 2021)

MicroRNA‐144 promotes remote limb ischemic preconditioning-mediated neuroprotection against ischemic stroke via PTEN/Akt pathway - Si-Jin Zhong; Miao-Miao Cui; Yu-Ting Gao; Xue-Yan Cao; Bin Chen; Xian-Ru Wen (Acta Neurologica Belgica, 2021)

Experimental evidence for long‐term coexistence of copiotrophic and oligotrophic bacteria in pelagic surface seawater - Yi Li; Zhi‐Bin Wang; Xi‐Ying Zhang; Yan‐Ru Dang; Lin‐Lin Sun; Wei‐Peng Zhang; Hui‐Hui Fu; Gui‐Peng Yang; Min Wang; Andrew McMinn; Xiu‐Lan Chen; Yin Chen; et al. (Environmental Microbiology, 2021)
Summary Most marine copiotrophic bacteria can produce extracellular enzymes to degrade biopolymers into bio‐available smaller solutes, while oligotrophic bacteria usually cannot. Bacterial extracellular enzymes and enzymatic products can be a common resource that could be utilized by both copiotrophs and oligotrophs; when present, oligotrophs may outcompete the enzyme‐producing copiotrophs. However, copiotrophs and oligotrophs consistently coexist in the ocean. How they maintain coexistence has still not been experimentally studied. In this study, the interaction and coexistence of a copiotroph and an oligotroph, isolated from the same surface seawater sample and utilizing the same proteinaceous substrate, were experimentally investigated. The copiotroph could secrete extracellular proteases to degrade and then utilize the proteinaceous substrate. The oligotroph was unable to utilize the proteinaceous substrate by itself, but could grow by using the hydrolysate amino acids. The copiotroph outcompeted the oligotroph by adsorbing the amino acids quickly and having a higher growth rate in the rich medium. The oligotroph survived by adapting to low concentration of nutrients. The copiotroph and oligotroph were able to maintain long‐term (up to 142 days) coexistence in the laboratory. This study indicates that differences in the utilization of different concentrations of nutrients can drive the coexistence of marine copiotrophs and oligotrophs.

Correction to: Involvement of proBDNF in Monocytes/Macrophages with Gastrointestinal Disorders in Depressive Mice - Yun-Qing Yu; Yan-Ling Zhang; Zhe Wang; Yu Liu; Hui Li; Chang-Qi Li; Xin-Fu Zhou; Zhao-Lan Hu; Ru-Ping Dai (Neurotoxicity Research, 2020)

Involvement of proBDNF in Monocytes/Macrophages with Gastrointestinal Disorders in Depressive Mice - Yun-Qing Yu; Yan-Ling Zhang; Zhe Wang; Yu Liu; Hui Li; Xin-Fu Zhou; Zhao-Lan Hu; Ru-Ping Dai (Neurotoxicity Research, 2020)

Comparison of Plasma Concentrations of Mercury, Cadmium, and Arsenic among Women in 2005 and 2012 in a Historically Contaminated Area in China - Lei Jin; Jing-ru Yu; Le Zhang; Ai-guo Ren (Biological Trace Element Research, 2020)

Rapid identification of landslide, collapse and crack based on low-altitude remote sensing image of UAV - Xu-gang Lian; Zou-jun Li; Hong-yan Yuan; Ji-bo Liu; Yan-jun Zhang; Xiao-yu Liu; Yan-ru Wu (Journal of Mountain Science, 2020)

Elevated ROS depress mitochondrial oxygen utilization efficiency in cardiomyocytes during acute hypoxia - Ru-Zhou Zhao; Xiao-Bo Wang; Shuai Jiang; Ning-Yu Ru; Bo Jiao; Yun-Ying Wang; Zhi-Bin Yu (Pflügers Archiv - European Journal of Physiology, 2020)

Novel ACADVL variants resulting in mitochondrial defects in long-chain acyl-CoA dehydrogenase deficiency - Ting Chen; Fan Tong; Xiao-yu Wu; Ling Zhu; Qiu-zi Yi; Jing Zheng; Ru-lai Yang; Zheng-yan Zhao; Xiao-hui Cang; Qiang Shu; Ping-ping Jiang (Journal of Zhejiang University-SCIENCE B, 2020)

Content and health risk assessment of heavy metals and polybrominated diphenyl ethers in fish from Songhua Lake (Jilin City), China - Mengnan Shen; Chunyu Kang; Tiehong Song; Hai Lu; Yuehong Wang; Bowen Yu; Ru Wang; Jie Cheng (Environmental Science and Pollution Research, 2020)

Characteristics of methane emissions in the Living Water Garden in Chengdu City from 2012 to 2017 - Ru Xue; Xiaoling Liu; Xiaoying Fu; Hongbing Luo; Ke Zhang; Bruce C. Anderson; Mei Li; Bo Huang; Lijuan Yu; Xiaoting Li; Shuzhi Fu; Aiping Pu; et al. (Environmental Science and Pollution Research, 2020)

Liquiritin inhibits proliferation and induces apoptosis in HepG2 hepatocellular carcinoma cells via the ROS-mediated MAPK/AKT/NF-κB signaling pathway - Jia-Ru Wang; Tian-Zhu Li; Cheng Wang; Shu-Mei Li; Ying-Hua Luo; Xian-Ji Piao; Yu-Chao Feng; Yi Zhang; Wan-Ting Xu; Yu Zhang; Tong Zhang; Shi-Nong Wang; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2020)

Grape seed proanthocyanidin extract ameliorates hepatic lipid accumulation and inflammation in grass carp (Ctenopharyngodon idella) - Rong-Hua Lu; Chao-Bin Qin; Feng Yang; Wen-Ya Zhang; Yu-Ru Zhang; Guo-Kun Yang; Li-Ping Yang; Xiao-Lin Meng; Xiao Yan; Guo-Xing Nie (Fish Physiology and Biochemistry, 2020)

Comparative Variations of Extractive Nitrogenous Components and Quality in Fresh Muscle and Dried Product of Rabbitfish ( Siganus fuscescens ) in Taiwan - Yu-Ru Huang; Wan-Yi Huang; Hsiao-Chin Jen; Bi-Yu Liu; Ken-Meng Huang; Deng Fwu Hwang (Journal of Aquatic Food Product Technology, 2020)

A new phenanthropyran and a new biphenanthrene from the rhizomes of Dioscorea septemloba and their antioxidant activities - Tao He; Yi Liu; Rui-Feng Xiong; Xiao-Yu Li; Shou-Feng Wang; Chun-Ru Cheng (Natural Product Research, 2020)

Corticosterone Induced the Increase of proBDNF in Primary Hippocampal Neurons Via Endoplasmic Reticulum Stress - Yu Liu; Guang-Jing Zou; Bo-Xuan Tu; Zhao-Lan Hu; Cong Luo; Yan-Hui Cui; Yang Xu; Fang Li; Ru-Ping Dai; Fang-Fang Bi; Chang-Qi Li (Neurotoxicity Research, 2020)

Prenatal di-(2-ethylhexyl) phthalate maternal exposure impairs the spatial memory of adult mouse offspring in a phase- and gender-dependent manner - Ling-Li Zhao; Ru Shen; Cong-Cong Sun; Shan-Yu Zhang; Bo Wang; Mei-Fang Sun; De-Xiang Xu (Environmental Science and Pollution Research, 2020)

Reconnaissance and learning after the February 6, 2018, earthquake in Hualien, Taiwan - Jui-Liang Lin; Chun-Hsiang Kuo; Yu-Wen Chang; Shu-Hsien Chao; Yi-An Li; Wen-Cheng Shen; Chung-Han Yu; Cho-Yen Yang; Fan-Ru Lin; Hsiao-Hui Hung; Chun-Chung Chen; Chin-Kuo Su; et al. (Bulletin of Earthquake Engineering, 2020)

Effects of surface modification on heavy metal adsorption performance and stability of peanut shell and its extracts of cellulose, lignin, and hemicellulose - Hang Yu; Jing Wang; Jun-xia Yu; Yi Wang; Ru-an Chi (Environmental Science and Pollution Research, 2020)

Influence of Aphis gossypii feeding on defense strategy of native and introduced populations of Ageratina adenophora - Ying Lin; Shu-Qi He; Zhi-Hui Lu; Yu-Lin Gao; Yan-Ru Duan; Zheng-Yue Li; Bin Chen; Fu-Rong Gui (Arthropod-Plant Interactions, 2020)

Combined effect of polymorphisms of MTHFR and MTR and arsenic methylation capacity on developmental delay in preschool children in Taiwan - Yu-Mei Hsueh; Ying-Chin Lin; Chi-Jung Chung; Ya-Li Huang; Ru-Lan Hsieh; Pai-Tsang Huang; Mei-Yi Wu; Horng-Sheng Shiue; Ssu-Ning Chien; Chih-Ying Lee; Ming-I. Lin; Shu-Chi Mu; et al. (Archives of Toxicology, 2020)

Pasture degradation impact on soil carbon and nitrogen fractions of alpine meadow in a Tibetan permafrost region - Zi-Qiang Yuan; Qing-Bai Wu; Xin Song; Xiao-Jin Jiang; Si-Ru Gao; Qing-Feng Wang; Guo-Yu Li (Journal of Soils and Sediments, 2020)

Thioredoxin-Interacting Protein (TXNIP) Regulates Parkin/PINK1-mediated Mitophagy in Dopaminergic Neurons Under High-glucose Conditions: Implications for Molecular Links Between Parkinson’s Disease and Diabetes - Cun-Jin Su; Zhu Shen; Ru-Xiao Cui; Ya Huang; De-Lai Xu; Feng-Lun Zhao; Jie Pan; Ai-Ming Shi; Tong Liu; Yun-Li Yu (Neuroscience Bulletin, 2020)

Endometrial autophagy is essential for embryo implantation during early pregnancy - Yan Su; Juan-Juan Zhang; Jun-Lin He; Xue-Qing Liu; Xue-Mei Chen; Yu-Bin Ding; Chao Tong; Chuan Peng; Yan-Qing Geng; Ying-Xiong Wang; Ru-Fei Gao (Journal of Molecular Medicine, 2020)

Effects of small nucleolar RNA SNORD44 on the proliferation, apoptosis and invasion of glioma cells - Xian-Ru Xia; Wen-Cui Li; Zong-Tao Yu; Jie Li; Chun-Yan Peng; Li Jin; Guo-Lin Yuan (Histochemistry and Cell Biology, 2020)

The enhanced SO3 formation by alkali-metal sulfates from ash in the post-flame region during the combustion of high-alkali coal - Haiping Xiao; Qiyong Cheng; Hao Shi; Jian Li; Yu Ru (Environmental Science and Pollution Research, 2020)

Modified stepwise mini-incision microdissection testicular sperm extraction: a useful technique for patients with a history of orchidopexy affected by non-obstructive azoospermia - Peng Li; Chen-cheng Yao; Er-lei Zhi; Yuan Xu; Zhong Wan; Ying-chuan Jiang; Yu-hua Huang; Yue-hua Gong; Hui-xing Chen; Ru-hui Tian; Chao Yang; Liang-yu Zhao; et al. (Journal of Zhejiang University-SCIENCE B, 2020)

Development of Human in vitro Brain-blood Barrier Model from Induced Pluripotent Stem Cell-derived Endothelial Cells to Predict the in vivo Permeability of Drugs - Yuan Li; Xueying Sun; Houfu Liu; Liang Huang; Guofeng Meng; Yu Ding; Wenji Su; Jiaqi Lu; Sophie Gong; Georg C. Terstappen; Ru Zhang; Wandong Zhang (Neuroscience Bulletin, 2019)

Climatology and change of extreme precipitation events in Taiwan based on weather types - Yi‐chao Wu; S.‐Y. Simon Wang; Yi‐Chiang Yu; Chu‐Ying Kung; An‐Hsiang Wang; Sebastian A. Los; Wan‐Ru Huang (International Journal of Climatology, 2019)
Taiwan's most significant natural hazards are caused by hydrological extremes resulting from excessive precipitation. The threat of extreme precipitation is posed by several different types of weather patterns that affect Taiwan. This study examined the bi‐decadal changes in rainfall by defining an extreme precipitation occurrence (EPO) for a range of event durations from 1 to 24 hr. Three major weather types affecting EPO in Taiwan were identified from 1993 to 2015: the front type consisting of either a frontal zone or convective systems developing with an apparent Meiyu cloudband, diurnal rainfall events when no apparent synoptic features are present, and a tropical cyclone (TC) type according to the maximum sustained wind radius of a TC. Results show that TC‐type events have the greatest overall contribution to EPO at longer (>6 hr) durations. Diurnal/afternoon convection events contribute most to the shorter ( 6 hr) EPO associated with the TC‐type events in summer. The distinction between EPO trends for the entire island of Taiwan and for the Taipei metropolitan area alone (northern Taiwan, population of 7 million) were compared, and an intriguing interannual variation is reported in the TC‐type EPO associated with the TC season 1 year to a year and half just before an El Niño–Southern Oscillation event. The analysis here provides refined statistical distributions of extreme rainfall, and these can contribute to the revision of governmental definitions for weather disasters that are used in mitigation and response strategies.

Upregulation of proBDNF in the Mesenteric Lymph Nodes in Septic Mice - Zhe Wang; Jia-Li Wu; Feng Zhong; Yu Liu; Yun-Qing Yu; Jing-Jing Sun; Shuang Wang; Hui Li; Xin-Fu Zhou; Zhao-Lan Hu; Ru-Ping Dai (Neurotoxicity Research, 2019)

The effects of negative air ions on cognitive function: an event-related potential (ERP) study - Chien-Heng Chu; Su-Ru Chen; Chih-Han Wu; Yung-Chao Cheng; Yu-Min Cho; Yu-Kai Chang (International Journal of Biometeorology, 2019)

Mixed phase nano–CdS supported on activated biomass carbon as efficient visible light–driven photocatalysts - Feng-Ying Cai; Yu-Qing Zhang; Jun-Tao Wang; Jun-Ru Zhou; Hai-Lei Cao; Jian Lü (Environmental Science and Pollution Research, 2019)

Cytoplasmic SIRT1 inhibits cell migration and invasion by impeding epithelial–mesenchymal transition in ovarian carcinoma - Tong Yang; Ru Zhou; Shentong Yu; Shuhong Yu; Zhuqing Cui; Peizhen Hu; Jinsong Liu; Qing Qiao; Jing Zhang (Molecular and Cellular Biochemistry, 2019)

Association of plasma folate, vitamin B12 levels, and arsenic methylation capacity with developmental delay in preschool children in Taiwan - Ying-Chin Lin; Chi-Jung Chung; Ya-Li Huang; Ru-Lan Hsieh; Pai-Tsang Huang; Mei-Yi Wu; Pui-Lam Ao; Horng-Sheng Shiue; Shiau-Rung Huang; Chien-Tien Su; Ming-I Lin; Shu-Chi Mu; et al. (Archives of Toxicology, 2019)

Antagonism of Ca2+-sensing receptors by NPS 2143 is transiently masked by p38 activation in mouse brain bEND.3 endothelial cells - Cing-Yu Chen; Mann-Jen Hour; Wen-Chuan Lin; Kar-Lok Wong; Lian-Ru Shiao; Ka-Shun Cheng; Paul Chan; Yuk-Man Leung (Naunyn-Schmiedeberg's Archives of Pharmacology, 2019)

Correction to: Genetic variant predictors of gene expression provide new insight into risk of colorectal cancer - Stephanie A. Bien; Yu-Ru Su; David V. Conti; Tabitha A. Harrison; Conghui Qu; Xingyi Guo; Yingchang Lu; Demetrius Albanes; Paul L. Auer; Barbara L. Banbury; Sonja I. Berndt; Stéphane Bézieau; et al. (Human Genetics, 2019)

Identification and characterisation of a glycine-rich RNA-binding protein as an endogenous suppressor of RNA silencing from Nicotiana glutinosa - Xu Huang; Ru Yu; Wenjing Li; Liwei Geng; Xiuli Jing; Changxiang Zhu; Hongmei Liu (Planta, 2019)

Genetic variant predictors of gene expression provide new insight into risk of colorectal cancer - Stephanie A. Bien; Yu-Ru Su; David V. Conti; Tabitha A. Harrison; Conghui Qu; Xingyi Guo; Yingchang Lu; Demetrius Albanes; Paul L. Auer; Barbara L. Banbury; Sonja I. Berndt; Stéphane Bézieau; et al. (Human Genetics, 2019)

Andrographolide impairs alpha-naphthylisothiocyanate-induced cholestatic liver injury in vivo - Lei Wang; Fei Cao; Li-li Zhu; Peng Liu; Yu-ru Shang; Wen-hui Liu; Xin Dong; Hai-dong Bao; Peng Gong; Zhong-yu Wang (Journal of Natural Medicines, 2019)

Detecting and attributing vegetation changes in Taihang Mountain, China - Shi Hu; Fei-yu Wang; Che-sheng Zhan; Ru-xin Zhao; Xiong-guo Mo; Liang-mei-zi Liu (Journal of Mountain Science, 2019)

Geomorphic features of Quaternary glaciation in the Taniantaweng Mountain, on the southeastern Qinghai-Tibet Plateau - Wei Zhang; Le Chai; Ian S Evans; Liang Liu; Ya-peng Li; Jing-ru Qiao; Qian-yu Tang; Bo Sun (Journal of Mountain Science, 2019)

Reduced hsa-miR-124-3p levels are associated with the poor survival of patients with hepatocellular carcinoma - Hui-Deng Long; Yu-Shui Ma; Hui-Qiong Yang; Shao-Bo Xue; Ji-Bin Liu; Fei Yu; Zhong-Wei Lv; Ji-Yu Li; Ru-Ting Xie; Zheng-Yan Chang; Gai-Xia Lu; Wen-Ting Xie; et al. (Molecular Biology Reports, 2018)

Efficient generation of functional cardiomyocytes from human umbilical cord-derived virus-free induced pluripotent stem cells - Kai Hong Wu; Su Yun Wang; Qian Ru Xiao; Yu Yang; Ning Ping Huang; Xu Ming Mo; Jian Sun (Cell and Tissue Research, 2018)

High-degree and broad-spectrum resistance mediated by a combination of NIb siRNA and miRNA suppresses replication of necrotic and common strains of potato virus Y - Ru Yu; Caixia Chen; Weilin Cao; Hongmei Liu; Shumei Zhou; Yunzhi Song; Changxiang Zhu (Archives of Virology, 2018)

Physiological Concentration of Prostaglandin E2 Exerts Anti-inflammatory Effects by Inhibiting Microglial Production of Superoxide Through a Novel Pathway - Shih-Heng Chen; Yueh-Feng Sung; Esteban A. Oyarzabal; Yu-Mei Tan; Jeremy Leonard; Mingri Guo; Shuo Li; Qingshan Wang; Chun-Hsien Chu; Shiou-Lan Chen; Ru-Band Lu; Jau-Shyong Hong (Molecular Neurobiology, 2018)

Novel combined method of biosorption and chemical precipitation for recovery of Pb2+ from wastewater - Jia-qi Tang; Jiang-bo Xi; Jun-xia Yu; Ru-an Chi; Jia-dong Chen (Environmental Science and Pollution Research, 2018)

Alternations of Metabolic Profile and Kynurenine Metabolism in the Plasma of Parkinson’s Disease - Kuo-Hsuan Chang; Mei-Ling Cheng; Hsiang-Yu Tang; Cheng-Yu Huang; Yih-Ru Wu; Chiung-Mei Chen (Molecular Neurobiology, 2018)

Enriched Expression of Neutral Sphingomyelinase 2 in the Striatum is Essential for Regulation of Lipid Raft Content and Motor Coordination - Laura Hui-Ru Tan; Angela Jin-Rong Tan; Yu-Ying Ng; John Jia-En Chua; Wee-Siong Chew; Sneha Muralidharan; Federico Torta; Bamaprasad Dutta; Siu Kwan Sze; Deron R. Herr; Wei-Yi Ong (Molecular Neurobiology, 2018)

Hyperelastic Mechanical Properties of Ex Vivo Normal and Intrauterine Growth Restricted Placenta - Shier Nee Saw; Jess Yi Ru Low; May Han Huang Ong; Yu Wei Poh; Citra Nurfarah Zaini Mattar; Arijit Biswas; Choon Hwai Yap (Annals of Biomedical Engineering, 2018)

An integrated assessment of INDCs under Shared Socioeconomic Pathways: an implementation of C3IAM - Yi-Ming Wei; Rong Han; Qiao-Mei Liang; Bi-Ying Yu; Yun-Fei Yao; Mei-Mei Xue; Kun Zhang; Li-Jing Liu; Juan Peng; Pu Yang; Zhi-Fu Mi; Yun-Fei Du; et al. (Natural Hazards, 2018)

Anti-amyloidgenic and neurotrophic effects of tetrahydroxystilbene glucoside on a chronic mitochondrial dysfunction rat model induced by sodium azide - Ru-yi Zhang; Lan Zhang; Li Zhang; Yu-lan Wang; Lin Li (Journal of Natural Medicines, 2018)

Changes of functional connectivity of the anterior cingulate cortex in women with primary dysmenorrhea - Peng Liu; Yanfei Liu; Geliang Wang; Ru Li; Ying Wei; Yingying Fan; Yang Yu; Demao Deng; Wei Qin (Brain Imaging and Behavior, 2018)

Non-structural protein 1 from avian influenza virus H9N2 is an efficient RNA silencing suppressor with characteristics that differ from those of Tomato bushy stunt virus p19 - Ru Yu; Xiuli Jing; Wenjing Li; Jie Xu; Yang Xu; Liwei Geng; Changxiang Zhu; Hongmei Liu (Virus Genes, 2018)

Ectopic expression of sorbitol-6-phosphate 2-dehydrogenase gene from Haloarcula marismortui enhances salt tolerance in transgenic Arabidopsis thaliana - Jian-jie Gao; Yu-ru Sun; Bo Zhu; Ri-He Peng; Bo Wang; Li-Juan Wang; Zhen-Jun Li; Lei Chen; Quan-Hong Yao (Acta Physiologiae Plantarum, 2018)

Brain MRI findings in acute hepatic encephalopathy in liver transplant recipients - Ruo-Mi Guo; Qing-Ling Li; Li-Ru Zhong; Yu Guo; Ju Jiao; Shao-Qiong Chen; Jin Wang; Yong Zhang (Acta Neurologica Belgica, 2018)

Soil physicochemical properties and vegetation structure along an elevation gradient and implications for the response of alpine plant development to climate change on the northern slopes of the Qilian Mountains - Yong-sheng Yang; Li Zhang; Hong-qin Li; Hui-dan He; Ya-xi Wei; Jin Luo; Guang-ru Zhang; Yu-ru Huang; Ying-nian Li; Hua-kun Zhou (Journal of Mountain Science, 2018)

Spatial and temporal variations in extreme temperature in Central Asia - Ru Feng; Ruide Yu; Hongwei Zheng; Miao Gan (International Journal of Climatology, 2018)
Central Asia, a typical arid and semi‐arid area, is very sensitive to climate change and is projected to undergo vigorous warming trend in future. However, it is still unclear how extreme temperatures have changed. Therefore, using the daily maximum and minimum temperatures collected from 108 stations in the study area from 1981 to 2015, the spatial–temporal variations in extreme temperature in Central Asia were analysed on both annual and seasonal scales based on 11 indices from The Expert Team on Climate Change Detection and Indices. Results show that: (1) from 1981 to 2015, all extreme temperature values exhibited increasing trends on an annual scale, but maximum temperature (TMAX) increased faster than the minimum temperature (TMIN), leading to an overall increase in the diurnal temperature range (DTR). Most of the stations in Central Asia, except for those in Xinjiang (China), exhibited an increasing trend in DTR, while most of the stations in Xinjiang (China) exhibited reversely significant decreasing trends. (2) TMAX, TMIN and DTR increased significantly, mainly during spring and summer. The trends of most warm extreme indices (warm days, warm nights and warmest days) indicate that the warming mainly occurred in spring, while most cold extreme indices (cool days, cool nights and coldest nights) exhibited significant warming trends in autumn. Dominant warming during spring and autumn can lead to longer summers, which may further accelerate the frequencies and magnitudes of temperature extremes. (3) Additionally, TMAX, TMIN and the percentile‐based warm indices all exhibited significant increasing trends from southwestern Central Asia (Turkmenistan) to eastern Central Asia (Xinjiang (China)) via the Tianshan Mountains. Although the percentile‐based cold indices showed decreasing trends in this region, they were too minor to offset the overall warming trend. With longer summers, stronger and more prolonged melting seasons were detected in the mountains of Central Asia.

Comparative chemical, taste, and functional components in different tissues of giant grouper ( Epinephelus lanceolatus ) - Chyuan-Yuan Shiau; Min-Hsien Hsu; Ann-Chang Cheng; Yu-Ru Huang (Journal of Aquatic Food Product Technology, 2018)

Investigating the composition characteristics of dissolved and particulate/colloidal organic matter in effluent-dominated stream using fluorescence spectroscopy combined with multivariable analysis - Min-Da Yu; Xiao-Song He; Bei-Dou Xi; Ru-Tai Gao; Xian-Wei Zhao; Hui Zhang; Cai-Hong Huang; Wenbing Tan (Environmental Science and Pollution Research, 2018)

Genetic analysis of three porcine bocaparvoviruses and identification of a natural recombinant breakpoint in NS1 - Yu Zhou; Jia Xu; Shi-Kang Zhu; Qing-Feng Meng; Zhi-Xiong Lin; Ru Chen; Ai-Dong Qian (Archives of Virology, 2018)

Chemical Characteristics of Different Tissues of Spectacled Caiman ( Caiman crocodilus ) - Yu-Ru Huang; Yung-Hsiang Tsai; Ching-Lu Liu; Wei-Zong Syue; Yi-Cheng Su (Journal of Aquatic Food Product Technology, 2018)

A two-step leaching method designed based on chemical fraction distribution of the heavy metals for selective leaching of Cd, Zn, Cu, and Pb from metallurgical sludge - Fen Wang; Junxia Yu; Wanli Xiong; Yuanlai Xu; Ru-an Chi (Environmental Science and Pollution Research, 2018)

Pentapeptide-insertion scanning mutational analysis of turkey herpesvirus HVT063 reveals residues important for its RNA silencing suppression activity - Gang Jia; Wenjing Li; Meina Fan; Ru Yu; Yang Xu; Liwei Geng; Jiedao Zhang; Changxiang Zhu; Hongmei Liu (Archives of Virology, 2018)

New phenolic acids from Salvia yunnanensis C.H.Wright - Yun Yu; Yin-ru Wang; Zhen-huan Dong; Wei Li; Shu-Ming Li; Xue-feng Huang (Natural Product Research, 2017)

Role of early environmental enrichment on the social dominance tube test at adulthood in the rat - Wen-Yu Cao; Zhao-Lan Hu; Yang Xu; Wen-Juan Zhang; Fu-Lian Huang; Xiao-Qing Qiao; Yan-Hui Cui; Wei Wan; Xue-qin Wang; Dan Liu; Ru-Ping Dai; Fang Li; et al. (Psychopharmacology, 2017)

Metabolic benefits of rivaroxaban in non-valvular atrial fibrillation patients after radiofrequency catheter ablation - Jun Zhu; Rong-jun Gao; Qiang Liu; Ru-hong Jiang; Lu Yu; Ya-xun Sun; Pei Zhang; Jian-wei Lin; Yang Ye; Zu-wen Zhang; Shi-quan Chen; Hui Cheng; et al. (Journal of Zhejiang University-SCIENCE B, 2017)

An overlooked nitrogen loss linked to anaerobic ammonium oxidation in estuarine sediments in China - Xiao-Ru Yang; Bo-Sen Weng; Hu Li; Christopher W. Marshall; Hong Li; Yong-Shan Chen; Shen Yu; Gui-Bing Zhu; Yong-Guan Zhu (Journal of Soils and Sediments, 2017)

Statistical features of eddies approaching the Kuroshio east of Taiwan Island and Luzon Island - Yu-Hsin Cheng; Chung-Ru Ho; Quanan Zheng; Bo Qiu; Jianyu Hu; Nan-Jung Kuo (Journal of Oceanography, 2017)

Evaluation on subcellular partitioning and biodynamics of pulse copper toxicity in tilapia reveals impacts of a major environmental disturbance - Yun-Ru Ju; Ying-Fei Yang; Jeng-Wei Tsai; Yi-Hsien Cheng; Wei-Yu Chen; Chung-Min Liao (Environmental Science and Pollution Research, 2017)

Groundwater origins and recharge in a well field near Chien-Shih, Shinchu, Taiwan - Pei-Ying Lin; Louis Loung-Yie Tsai; Chung-Ho Wang; Kuei-Wen Chang; Yu-Yen Sheng; I-Tzu Chu; Wang-Ru Lee (Sustainable Water Resources Management, 2017)

Retraction Note To: VEGF Silencing Inhibits Human Osteosarcoma Angiogenesis and Promotes Cell Apoptosis via PI3K/AKT Signaling Pathway - Jian Zhao; Zi-Ru Zhang; Na Zhao; Bao-An Ma; Qing-Yu Fan (Cell Biochemistry and Biophysics, 2017)

Propofol attenuates H2O2-induced oxidative stress and apoptosis via the mitochondria- and ER-medicated pathways in neonatal rat cardiomyocytes - Xue-Ru Liu; Lu Cao; Tao Li; Lin-Lin Chen; Yi-Yan Yu; Wen-Jun Huang; Li Liu; Xiao-Qiu Tan (Apoptosis, 2017)

Selective adsorption and recycle of Cu2+ from aqueous solution by modified sugarcane bagasse under dynamic condition - Jia-dong Chen; Jun-xia Yu; Fen Wang; Jia-qi Tang; Yue-fei Zhang; Yuan-lai Xu; Ru-an Chi (Environmental Science and Pollution Research, 2017)

Life cycle toxicity assessment of earthworms exposed to cadmium-contaminated soils - Wei-Yu Chen; Wen-Hsuan Li; Yun-Ru Ju; Chung-Min Liao; Vivian Hsiu-Chuan Liao (Ecotoxicology, 2017)

Removal of Congo red from aqueous solution by adsorption onto different amine compounds modified sugarcane bagasse - Jun-xia Yu; Wan-li Xiong; Jing Zhu; Jia-dong Chen; Ru-an Chi (Clean Technologies and Environmental Policy, 2017)

Overexpression of the ascorbate peroxidase gene from eggplant and sponge gourd enhances flood tolerance in transgenic Arabidopsis - Chih-Ming Chiang; Chiu-Chen Chen; Shi-Peng Chen; Kuan-Hung Lin; Li-Ru Chen; Yu-Huei Su; His-Cheng Yen (Journal of Plant Research, 2017)

Genomewide association study for seeding emergence and tiller number using SNP markers in an elite winter wheat population - GUANG FENG CHEN; RU GANG WU; DONG MEI LI; HAI XIA YU; ZHIYING DENG; JI CHUN TIAN (Journal of Genetics, 2017)

Arabidopsis heat stress transcription factors A2 (HSFA2) and A3 (HSFA3) function in the same heat regulation pathway - Xiao-dong Li; Xiao-li Wang; Yi-Ming Cai; Jia-hai Wu; Ben-tian Mo; Er-ru Yu (Acta Physiologiae Plantarum, 2017)

Applying the strategy of light environment control to improve the biomass and polysaccharide production of Nostoc flagelliforme - Pei-pei Han; Shi-gang Shen; Hui-Yan Wang; Shun-yu Yao; Zhi-lei Tan; Cheng Zhong; Shi-ru Jia (Journal of Applied Phycology, 2017)

Inhibition of the Receptor for Advanced Glycation End-Products (RAGE) Attenuates Neuroinflammation While Sensitizing Cortical Neurons Towards Death in Experimental Subarachnoid Hemorrhage - Hua Li; Jia-Sheng Yu; Ding-Ding Zhang; Yi-Qing Yang; Li-Tian Huang; Zhuang Yu; Ru-Dong Chen; Hong-Kuan Yang; Chun-Hua Hang (Molecular Neurobiology, 2017)

An integrated earthquake early warning system and its performance at schools in Taiwan - Bing-Ru Wu; Nai-Chi Hsiao; Pei-Yang Lin; Ting-Yu Hsu; Chiou-Yun Chen; Shieh-Kung Huang; Hung-Wei Chiang (Journal of Seismology, 2017)

Dynamic quantitative proteomics characterization of TNF-α-induced necroptosis - Yang Wang; Zhi-Hao Huang; Yang-Jia Li; Gui-Wei He; Ru-Yuan Yu; Jie Yang; Wan-Ting Liu; Bin Li; Qing-Yu He (Apoptosis, 2016)

Reactive Oxygen Species-mediated Loss of Phenotype of Parvalbumin Interneurons Contributes to Long-term Cognitive Impairments After Repeated Neonatal Ketamine Exposures - Hui Zhang; Xiao-ru Sun; Jing Wang; Zhen-zhen Zhang; Hong-ting Zhao; Hui-hui Li; Mu-huo Ji; Kuan-yu Li; Jian-jun Yang (Neurotoxicity Research, 2016)

RhoB/ROCK mediates oxygen–glucose deprivation-stimulated syncytiotrophoblast microparticle shedding in preeclampsia - Jian Han; Bo-ping Yang; Yi-lin Li; Hong-mei Li; Xiu-hui Zheng; Li-li Yu; Qiong Zhang; Ying-ru Zheng; Ping Yi; Li Li; Jian-xin Guo; Yuan-guo Zhou (Cell and Tissue Research, 2016)

Salicylic acid-induced antioxidant protection against low temperature in cold-hardy winter wheat - Jing Yu; Jing Cang; Yanping Li; Ru Huang; Qiuwei Lu; Xiutian Wang; Lijie Liu; Qinghua Xu; Kejian Zhang (Acta Physiologiae Plantarum, 2016)

Trans-cinnamaldehyde protected PC12 cells against oxygen and glucose deprivation/reperfusion (OGD/R)-induced injury via anti-apoptosis and anti-oxidative stress - Xue Qi; Ru Zhou; Yue Liu; Jing Wang; Wan-Nian Zhang; Huan-Ran Tan; Yang Niu; Tao Sun; Yu-Xiang Li; Jian-Qiang Yu (Molecular and Cellular Biochemistry, 2016)

Flood damage assessment of an urban area in Taiwan - Yi-Ru Chen; Chao-Hsien Yeh; Bofu Yu (Natural Hazards, 2016)

Molecular Design, Structural Analysis and Antifungal Activity of Derivatives of Peptide CGA-N46 - Rui-Fang Li; Zhi-Fang Lu; Ya-Nan Sun; Shi-Hua Chen; Yan-Jie Yi; Hui-Ru Zhang; Shuo-Ye Yang; Guang-Hai Yu; Liang Huang; Chao-Nan Li (Interdisciplinary Sciences: Computational Life Sciences, 2016)

A Waterborne Gastroenteritis Outbreak Caused by Norovirus GII.17 in a Hotel, Hebei, China, December 2014 - Meng Qin; Xiao-Gen Dong; Yan-Yan Jing; Xiu-xia Wei; Zhao-E Wang; Hui-Ru Feng; Hong Yu; Jin-Song Li; Jie Li (Food and Environmental Virology, 2016)

Adsorption of Cd(II) by two variable-charge soils in the presence of pectin - Ru-hai Wang; Xiao-fang Zhu; Wei Qian; Min-hua Zhao; Ren-kou Xu; Yuan-chun Yu (Environmental Science and Pollution Research, 2016)

Influence of Soluplus on Solid-State Properties and Physical Stability of Indomethacin-Saccharin Co-crystal Formation Prepared by Air-Drying Process - Shan-Yang Lin; Hong-Liang Lin; Ying-Ting Chi; Ru-Ying Hung; Yu-Ting Huang; Wei-Hsien Hsieh; Chi-Yu Kao (Journal of Pharmaceutical Innovation, 2016)

Pertrogenesis and tectonic implications of the late Jurassic basic rocks from the northern Shi‐Hang zone, Southeast China - Qing Zhou; Yao–hui Jiang; Shi–yong Liao; Peng Zhao; Ru–ya Jia; Zheng Liu; Guo–chang Wang; Chun–yu Ni (Island Arc, 2016)
The tectonic setting of the late mesozoic of South China is in a debate between two schools of thought: an intra‐continental rift zone along a passive continental margin or active rifting associated with subduction of the paleo‐Pacific Plate. In this study, we present new sensitive high‐resolution ion microprobe (SHRIMP) U‐Pb zircon ages, along with geochemical data of three basic dikes that cross‐cut the Dexing porphyry copper deposit. The deposit is the largest of its kind in eastern China and part of large scale mineralization associated with Mesozoic magmatic activity in the area. Our results indicate that the dikes were emplaced in the Late Jurassic with an average U‐Pb age of 153.5 ± 2.4 Ma. The intrusions have bulk ε Nd (t) of ca +0.7 and zircon ε Hf (t) value of +1.54 to +6.92. Based on relatively enriched light rare earth elements (LREE) and depleted high‐field‐strength elements (HFSE) abundances with pronounced negative Ta–Nb, Hf–Zr and Ti anomalies in multi‐element diagrams, we propose that these dikes were derived from a subduction‐modified lithospheric mantle source. The variability in Hf isotopes identifies some degree of crustal contaminations. Our data support a scenario with a back‐arc extensional setting or an intra‐arc rift environment associated with the westward subduction of the paleo‐Pacific Plate at or prior to the late Jurassic as the most likely cause for these subduction signatures.

Erratum to: An Up-regulation of IRF-1 After a Spinal Cord Injury: Implications for Neuronal Apoptosis - Jian Zhao; Chen Chen; Jian-Ru Xiao; Hai-Feng Wei; Xu-hui Zhou; Xing-Xing Mao; Wei-dong Zhang; Rong Qian; Xin-lei Chen; Ming-qing He; Xiao-Wei Yu; Jian Zhao (Journal of Molecular Neuroscience, 2016)

In vivo comparison of biomineralized scaffold-directed osteogenic differentiation of human embryonic and mesenchymal stem cells - Cai Wen; Heemin Kang; Yu-Ru V. Shih; YongSung Hwang; Shyni Varghese (Drug Delivery and Translational Research, 2016)

Evaluating the impacts of cumulus, land surface and ocean surface schemes on summertime rainfall simulations over East-to-southeast Asia and the western north Pacific by RegCM4 - Yu-Bin Li; Chi-Yung Tam; Wan-Ru Huang; Kevin K. W. Cheung; Zhiqiu Gao (Climate Dynamics, 2016)

Differential expression of ATP-gated P2X receptors in DRG between chronic neuropathic pain and visceralgia rat models - Lin Chen; Yu-wei Liu; Kai Yue; Qin Ru; Qi Xiong; Bao-miao Ma; Xiang Tian; Chao-ying Li (Purinergic Signalling, 2016)

Isolation and characterization of collagens from the skin of giant grouper ( Epinephelus lanceolatus ) - Cheng-Hong Hsieh; Chyuan-Yuan Shiau; Yi-Cheng Su; Yi-Han Liu; Yu-Ru Huang (Journal of Aquatic Food Product Technology, 2016)

Changes in Biochemical Compositions and Quality of White Shrimp ( Litopenaeus vannamei ) During Storage - Yu-Ru Huang; Mirtala Francisca Guevara Zelaya; Chyuan-Yuan Shiau (Journal of Aquatic Food Product Technology, 2016)

Gomisin A is a Novel Isoform-Specific Probe for the Selective Sensing of Human Cytochrome P450 3A4 in Liver Microsomes and Living Cells - Jing-Jing Wu; Guang-Bo Ge; Yu-Qi He; Ping Wang; Zi-Ru Dai; Jing Ning; Liang-Hai Hu; Ling Yang (The AAPS Journal, 2016)

Di-(2-ethylhexyl) phthalate accelerates atherosclerosis in apolipoprotein E-deficient mice - Jin-Feng Zhao; Sheng-Huang Hsiao; Ming-Hua Hsu; Kuan-Chuan Pao; Yu Ru Kou; Song-Kun Shyue; Tzong-Shyuan Lee (Archives of Toxicology, 2016)

Identification of geranylgeranyl diphosphate synthase genes from Tripterygium wilfordii - Meng Zhang; Ping Su; Yong-Jin Zhou; Xiu-Juan Wang; Yu-Jun Zhao; Yu-Jia Liu; Yu-Ru Tong; Tian-Yuan Hu; Lu-Qi Huang; Wei Gao (Plant Cell Reports, 2015)

An Up-regulation of IRF-1 After a Spinal Cord Injury: Implications for Neuronal Apoptosis - Jian Zhao; Chen Chen; Jian-Ru Xiao; Hai-Feng Wei; Xu-hui Zhou; Xing-Xing Mao; Wei-dong Zhang; Rong Qian; Xin-lei Chen; Ming-qing He; Xiao-Wei Yu; Jian Zhao (Journal of Molecular Neuroscience, 2015)
IRF-1, a kind of transcription factor, is expressed in many cell types, except in early embryonal cells. IRF-1 has played an essential role in various physiological and pathological processes, including tumor immune surveillance, viral infection, development of immunity system and pro-inflammatory injury. However, the expression and function of IRF-1 in spinal cord injury (SCI) are still unknown. In this study, we have performed an acute SCI model in adult rats and investigated the dynamic changes of IRF-1 expression in the spinal cord. Western blot have shown that IRF-1 protein levels gradually increased, reaching a peak at day 3 and then gradually declined to a normal level at day 14 after SCI. Double immunofluorescence staining showed that IRF-1 immunoreactivity was found in neurons, but not in astrocytes and microglia. Additionally, colocalization of IRF-1/active caspase-3 was detected in neurons. In vitro, IRF-1 depletion, by short interfering RNA, obviously decreases neuronal apoptosis. In conclusion, this is the first description of IRF-1 expression in spinal cord injury. Our results suggested that IRF-1 might play crucial roles in CNS pathophysiology after SCI.

Effect of pectin on adsorption of Cu(II) by two variable-charge soils from southern China - Ru-hai Wang; Xiao-fang Zhu; Wei Qian; Yuan-chun Yu; Ren-kou Xu (Environmental Science and Pollution Research, 2015)

RETRACTED ARTICLE: VEGF Silencing Inhibits Human Osteosarcoma Angiogenesis and Promotes Cell Apoptosis via PI3K/AKT Signaling Pathway - Jian Zhao; Zi-Ru Zhang; Na Zhao; Bao-An Ma; Qing-Yu Fan (Cell Biochemistry and Biophysics, 2015)

Impact assessment of climatic and land-use changes on flood runoff in southeast Queensland - Yi-Ru Chen; Bofu Yu (Hydrological Sciences Journal, 2015)

Protective effects of aloperine on neonatal rat primary cultured hippocampal neurons injured by oxygen–glucose deprivation and reperfusion - Ning-Tian Ma; Ru Zhou; Ren-Yuan Chang; Yin-Ju Hao; Lin Ma; Shao-Ju Jin; Juan Du; Jie Zheng; Cheng-Jun Zhao; Yang Niu; Tao Sun; Wei Li; et al. (Journal of Natural Medicines, 2015)

Model-based meta-analysis of the effects of non-selective and α1-selective GABAA receptor agonists in healthy volunteers - Yu-Peng Ren; Ru-Jia Xie; Scott Marshall; Liang Li; Tian-Yan Zhou; Wei Lu (European Journal of Clinical Pharmacology, 2015)

Environmental stochasticity promotes copper bioaccumulation and bioenergetic response in tilapia - Wei-Yu Chen; Yun-Ru Ju; Chia-Jung Lin; Jeng-Wei Tsai; Szu-Cheih Chen; Chung-Min Liao (Stochastic Environmental Research and Risk Assessment, 2015)

Interaction of DRD2TaqI, COMT, and ALDH2 genes associated with bipolar II disorder comorbid with anxiety disorders in Han Chinese in Taiwan - Ming-Chuan Hu; Sheng-Yu Lee; Tzu-Yun Wang; Yun-Hsuan Chang; Shiou-Lan Chen; Shih-Heng Chen; Chun-Hsien Chu; Chen-Lin Wang; I Hui Lee; Po See Chen; Yen Kuang Yang; Ru-Band Lu (Metabolic Brain Disease, 2015)

Comparative pharmacokinetics of oxytetracycline in blunt-snout bream (Megalobrama amblycephala) with single and multiple-dose oral administration - Ru-Qin Li; Yu-Wei Ren; Jing Li; Can Huang; Jun-hui Shao; Xiao-Xuan Chen; Zhi-Xin Wu (Fish Physiology and Biochemistry, 2015)

Efficient secretory production of CotA-laccase and its application in the decolorization and detoxification of industrial textile wastewater - Zheng-Bing Guan; Yan Shui; Chen-Meng Song; Ning Zhang; Yu-Jie Cai; Xiang-Ru Liao (Environmental Science and Pollution Research, 2015)

Using fluorescence spectroscopy coupled with chemometric analysis to investigate the origin, composition, and dynamics of dissolved organic matter in leachate-polluted groundwater - Xiao-Song He; Bei-Dou Xi; Ru-Tai Gao; Lei Wang; Yan Ma; Dong-Yu Cui; Wen-Bing Tan (Environmental Science and Pollution Research, 2015)

Biotransformation of rutin to isoquercitrin using recombinant α-l-rhamnosidase from Bifidobacterium breve - Ru Zhang; Bian-Ling Zhang; Tao Xie; Gu-Cai Li; Yi Tuo; Yu-Ting Xiang (Biotechnology Letters, 2015)

Augmenter of liver regeneration plays a protective role against hydrogen peroxide-induced oxidative stress in renal proximal tubule cells - Ning Xia; Ru-yu Yan; Qi Liu; Xiao-hui Liao; Hang Sun; Hui Guo; Ling Zhang (Apoptosis, 2015)

The relationship between the plant-encoded RNA-dependent RNA polymerase 1 and alternative oxidase in tomato basal defense against Tobacco mosaic virus - Yang-Wen-Ke Liao; Ya-Ru Liu; Jia-Yang Liang; Wen-Ping Wang; Jie Zhou; Xiao-Jian Xia; Yan-Hong Zhou; Jing-Quan Yu; Kai Shi (Planta, 2015)

Is abnormal non-high-density lipoprotein cholesterol a gender-specific predictor for metabolic syndrome in patients with schizophrenia taking second-generation antipsychotics? - Esther Ching-Lan Lin; Wen-Chuan Shao; Hsin-Ju Yang; Miaofen Yen; Sheng-Yu Lee; Pei-Chun Wu; Ru-Band Lu (Metabolic Brain Disease, 2015)

Genetic analysis and chromosome mapping of a thermo-sensitive genic male sterile gene in wheat - Zhen-Gang Ru; Li-Ping Zhang; Tie-Zhu Hu; Hong-Yu Liu; Qing-Kai Yang; Man-Li Weng; Bin Wang; Chang-Ping Zhao (Euphytica, 2015)

Efficacy of a high-growth reassortant H1N1 influenza virus vaccine against the classical swine H1N1 subtype influenza virus in mice and pigs - Feng Wen; Hai Yu; Fu-ru Yang; Meng Huang; Sheng Yang; Yan-Jun Zhou; Ze-Jun Li; Guang-Zhi Tong (Archives of Virology, 2014)

Impact of land–sea breezes at different scales on the diurnal rainfall in Taiwan - Wan-Ru Huang; Shih-Yu Wang (Climate Dynamics, 2014)

Metabolomic approach to optimizing and evaluating antibiotic treatment in the axenic culture of cyanobacterium Nostoc flagelliforme - Pei-pei Han; Shi-ru Jia; Ying Sun; Zhi-lei Tan; Cheng Zhong; Yu-jie Dai; Ning Tan; Shi-gang Shen (World Journal of Microbiology and Biotechnology, 2014)

Rapid development of tissue bank achieved by International Atomic Energy Agency (IAEA) Tissue Banking Programme in China - Yu-Min Zhang; Jian-Ru Wang; Nai-Li Zhang; Xiao-Ming Liu; Mo Zhou; Shao-Ying Ma; Ting Yang; Bao-Xing Li (Cell and Tissue Banking, 2014)

Establishment of a Spinal Cord Injury Model in Adult Rats by an Electrocircuit-Controlled Impacting Device and its Pathological Observations - Yun Wang; Chun-feng Liu; Qi-ping Wang; Heng Gao; Han-rong Na; Ru-tong Yu (Cell Biochemistry and Biophysics, 2014)

SNP and haplotype analysis reveal IGF2 variants associated with growth traits in Chinese Qinchuan cattle - Yong-Zhen Huang; Zhao-Yang Zhan; Xin-Yi Li; Sheng-Ru Wu; Yu-Jia Sun; Jing Xue; Xian-Yong Lan; Chu-Zhao Lei; Chun-Lei Zhang; Yu-Tang Jia; Hong Chen (Molecular Biology Reports, 2014)

Origin of Middle Cambrian and Late Silurian potassic granitoids from the western Kunlun orogen, northwest China: a magmatic response to the Proto-Tethys evolution - Zheng Liu; Yao-Hui Jiang; Ru-Ya Jia; Peng Zhao; Qing Zhou; Guo-Chang Wang; Chun-Yu Ni (Mineralogy and Petrology, 2014)

The functions and regulations of DAPK in cancer metastasis - Hsin-Yi Chen; Yu-Ru Lee; Ruey-Hwa Chen (Apoptosis, 2014)

Changes in Transcriptional Factor Binding Capacity Resulting from Promoter Region Methylation Induce Aberrantly High GDNF Expression in Human Glioma - Zheng-Quan Yu; Bao-Le Zhang; Qing-Xian Ren; Jian-Cun Wang; Ru-Tong Yu; De-Wei Qu; Ze-Hao Liu; Ye Xiong; Dian-Shuai Gao (Molecular Neurobiology, 2013)

Ecological Risks Assessment and Pollution Source Identification of Trace Elements in Contaminated Sediments from the Pearl River Delta, China - Feng Li; Xiang-yun Zeng; Chang-hua Wu; Zhi-peng Duan; Yan-mao Wen; Guo-ru Huang; Xiao-lin Long; Min-Jian Li; Man-Jie Li; Jiang-Yu Xu (Biological Trace Element Research, 2013)

QTL mapping and correlation analysis for 1000-grain weight and percentage of grains with chalkiness in rice - JIAN-MIN BIAN; HUAN SHI; CUI-JUAN LI; CHANG-LAN ZHU; QIU-YING YU; XIAO-SONG PENG; JUN-RU FU; XIAO-PENG HE; XIAO-RONG CHEN; LI-FANG HU; LIN-JUAN OUYANG; HAO-HUA HE (Journal of Genetics, 2013)

Toxicokinetics of tilapia following high exposure to waterborne and dietary copper and implications for coping mechanisms - Jeng-Wei Tsai; Yun-Ru Ju; Ying-Hsuan Huang; Yue-Sun Deng; Wei-Yu Chen; Chin-Ching Wu; Chung-Min Liao (Environmental Science and Pollution Research, 2013)

Down-regulation of the ErbB3 binding protein 1 in human bladder cancer promotes tumor progression and cell proliferation - Hui-chan He; Xiao-hui Ling; Jian-guo Zhu; Xin Fu; Zhao-dong Han; Yu-xian Liang; Ye-han Deng; Zhuo-yuan Lin; Guo Chen; Yan-fei Chen; Ru-jun Mo; Wei-de Zhong (Molecular Biology Reports, 2013)

SIRT1 interacts with metabolic transcriptional factors in the pancreas of insulin-resistant and calorie-restricted rats - Yong-Ru Chen; Yu-lin Lai; Shao-da Lin; Xi-tao Li; Yu-Cai Fu; Wen-Can Xu (Molecular Biology Reports, 2013)

Molecular cloning, expression profiles and subcellular localization of cyclin B in ovary of the mud crab, Scylla paramamosain - Wen-Xing Li; Hui-Yang Huang; Jing-Ru Huang; Jin-Jin Yu; Jun Ma; Hai-Hui Ye (Genes & Genomics, 2013)

Construction of multiple shRNAs expression vector that inhibits FUT1 gene expression and production of the transgenic SCNT embryos in vitro - Jian-wen Chen; Yu Zhang; Yuan-liang Zhang; Chao Wei; Xing Liu; Na-ru Zhou; Qing Jia; Yun-sheng Li; Xiao-rong Zhang; Yun-hai Zhang (Molecular Biology Reports, 2013)

Molecular characterization of a gene POLR2H encoded an essential subunit for RNA polymerase II from the Giant Panda (Ailuropoda Melanoleuca) - Yu-jie Du; Yi-ling Hou; Wan-ru Hou (Molecular Biology Reports, 2013)

β2-Glycoprotein I inhibits VEGF-induced endothelial cell growth and migration via suppressing phosphorylation of VEGFR2, ERK1/2, and Akt - Wen-Chin Chiu; Jan-Yu Lin; Tzong-Shyuan Lee; Li-Ru You; An-Na Chiang (Molecular and Cellular Biochemistry, 2013)

A simple method to prepare magnetic modified beer yeast and its application for cationic dye adsorption - Jun-Xia Yu; Li-Yan Wang; Ru-An Chi; Yue-Fei Zhang; Zhi-Gao Xu; Jia Guo (Environmental Science and Pollution Research, 2013)

A Mucormycosis Case in a Cirrhotic Patient Successfully Treated with Posaconazole and Review of Published Literature - Shang-Yi Lin; Po-Liang Lu; Kun-Bow Tsai; Chun-Yu Lin; Wei-Ru Lin; Tun-Chieh Chen; Ya-Ting Chang; Chung-Hao Huang; Chi-Yu Chen; Chung-Chih Lai; Yen-Hsu Chen (Mycopathologia, 2012)

Dextromethorphan Attenuated Inflammation and Combined Opioid Use in Humans Undergoing Methadone Maintenance Treatment - Shiou-Lan Chen; Sheng-Yu Lee; Pao-Luh Tao; Yun-Hsuan Chang; Shih-Heng Chen; Chun-Hsien Chu; Po See Chen; I Hui Lee; Tzung Lieh Yeh; Yen Kuang Yang; Jau-Shyong Hong; Ru-Band Lu (Journal of Neuroimmune Pharmacology, 2012)

Erratum to: Inflammation in Patients with Schizophrenia: The Therapeutic Benefits of Risperidone Plus Add-On Dextromethorphan - Shiou-Lan Chen; Sheng-Yu Lee; Yun-Hsuan Chang; Shih-Heng Chen; Chun-Hsieh Chu; Nian-Sheng Tzeng; I-Hui Lee; Po-See Chen; Tzung Lieh Yeh; San-Yuan Huang; Yen-Kuang Yang; Ru-Band Lu; et al. (Journal of Neuroimmune Pharmacology, 2012)

Coupled dynamics of energy budget and population growth of tilapia in response to pulsed waterborne copper - Wei-Yu Chen; Chia-Jung Lin; Yun-Ru Ju; Jeng-Wei Tsai; Chung-Min Liao (Ecotoxicology, 2012)

Co-variability of poleward propagating atmospheric energy with tropical and higher-latitude climate oscillations - Wan-Ru Huang; Tsing-Chang Chen; Shih-Yu Wang (Climate Dynamics, 2012)

Inflammation in Patients with Schizophrenia: The Therapeutic Benefits of Risperidone Plus Add-On Dextromethorphan - Shiou-Lan Chen; Sheng-Yu Lee; Yun-Hsuan Chang; Shih-Heng Chen; Chun-Hsieh Chu; Nian-Sheng Tzeng; I-Hui Lee; Po-See Chen; Tzung Lieh Yeh; San-Yuan Huang; Yen-Kuang Yang; Ru-Band Lu (Journal of Neuroimmune Pharmacology, 2012)

The prevalence of CD33 and MS4A6A variant in Chinese Han population with Alzheimer’s disease - Yu-Lei Deng; Li-Hua Liu; Ying Wang; Hui-Dong Tang; Ru-Jing Ren; Wei Xu; Jian-Fang Ma; Li-Ling Wang; Jun-Peng Zhuang; Gang Wang; Sheng-Di Chen (Human Genetics, 2012)

Cloning and overexpression of an important functional gene ATP6V1F encoding a component of vacuolar ATPase from the Giant Panda (Ailuropoda melanoleuca) - Yu-jie Du; Yi-ling Hou; Wan-ru Hou (Molecular Biology Reports, 2012)

Cassiterite exsolution with ilmenite lamellae in magnetite from the Huashan metaluminous tin granite in southern China - Ru Cheng Wang; A-Peng Yu; Jun Chen; Lei Xie; Jian-Jun Lu; Jin-Chu Zhu (Mineralogy and Petrology, 2012)

Construction of a eukaryotic expression vector pEGFP-C1-BMP-2 and its effect on cell migration - Xiao-ying Wang; Zhong-hua Chen; Ru-yi Zhang; Sen-quan Liu; Zhu Mei; Ying-ying Yu; Xiong Zhang; Qiang Xia; Yue-min Ding (Journal of Zhejiang University-SCIENCE B, 2012)

Lead and cadmium-induced oxidative stress impacting mycelial growth of Oudemansiella radicata in liquid medium alleviated by microbial siderophores - Yan-ru Cao; Xi-yu Zhang; Jia-yu Deng; Qi-qi Zhao; Heng Xu (World Journal of Microbiology and Biotechnology, 2012)

Observational and supportive modelling analyses of winter precipitation change in China over the last half century - Robert R. Gillies; Shih‐Yu Wang; Wan‐Ru Huang (International Journal of Climatology, 2012)
Overall increasing trends in annual precipitation and widespread warming over China have been documented. During the winter months in southeast China, where snow is commonplace but rarely accumulates, the climatological 0 °C surface isotherm generally defines the southern boundary of the snowfield. Therefore, a warming climate will: (a) modify the southern boundary of the snowfield; and (b) potentially alter the snow‐rain ratio. Using recently released daily precipitation from the Asian Precipitation‐Highly Resolved Observational Data Integration Towards Evaluation (APHRODITE) and temperature observations from the ERA‐40/Interim Reanalyses, this study investigated historical winter precipitation changes in China. Since snowfall observations were largely unavailable for southeast China, snowfall amounts were estimated using a rain‐snow threshold temperature (RST) method which was subsequently verified by in situ and satellite observations of snow depth, snow cover, and snow water equivalent (SWE). The composite analysis reveals a decrease in snowfall totals which are accompanied by an increase in rainfall; this change corresponds with the northward retreat of the 0 °C surface isotherm and the snow‐rain ratio. Atmospheric circulation analysis indicated lower tropospheric warming with increased moisture over southeast China, consistent with previous studies. Moreover, we observed an increase in the convergence of water vapour flux which sustains the increase in precipitation; this is accompanied by the suppression of snowfall due to the lower tropospheric warming. An additional analysis employed to further substantiate the RST method was undertaken by modelling the snow‐rain ratio with the Weather Research and Forecasting (WRF) Model. The results were in agreement with those estimated from the observations. Copyright © 2011 Royal Meteorological Society

Availability of dopamine and serotonin transporters in opioid-dependent users—a two-isotope SPECT study - Tzung Lieh Yeh; Kao Chin Chen; Shih-Hsien Lin; I. Hui Lee; Po See Chen; Wei Jen Yao; Sheng-Yu Lee; Yen Kuang Yang; Ru-Band Lu; Mei-Hsiu Liao; Nan-Tsing Chiu (Psychopharmacology, 2012)

Toxicokinetics/toxicodynamics with damage feedback improves risk assessment for tilapia and freshwater clam exposed to arsenic - Wei-Yu Chen; Chung-Min Liao; Yun-Ru Ju; Sher Singh; Li-John Jou; Bo-Ching Chen; Jeng-Wei Tsai (Ecotoxicology, 2012)

Effect of heavy metal-solubilizing microorganisms on zinc and cadmium extractions from heavy metal contaminated soil with Tricholoma lobynsis - Ling-yun Ji; Wei-wei Zhang; Dong Yu; Yan-ru Cao; Heng Xu (World Journal of Microbiology and Biotechnology, 2012)

An upstream regulatory element confers orientation-independent enhancement of the TSG101 promoter activity in transformed cells - Shih-Fang Hsu; Yih-Gang Goan; Hsien-Yu Tsai; Yi-Ru Lin; Rue-Tsuan Liu; Jiin-Tsuey Cheng (Molecular Biology Reports, 2012)

Integrated application of the analytic hierarchy process and the geographic information system for flood risk assessment and flood plain management in Taiwan - Yi-Ru Chen; Chao-Hsien Yeh; Bofu Yu (Natural Hazards, 2011)

QTL mapping of bio-energy related traits in Sorghum - Yan-an Guan; Hai-lian Wang; Ling Qin; Hua-wen Zhang; Yan-bing Yang; Feng-ju Gao; Ru-yu Li; Hong-gang Wang (Euphytica, 2011)

Infrasound Exposure Induces Apoptosis of Rat Cardiac Myocytes by Regulating the Expression of Apoptosis-Related Proteins - Zhao-Hui Pei; Bao-Ying Chen; Ru Tie; Hai-Feng Zhang; Ge Zhao; Ping Qu; Xiao-Xing Zhu; Miao-Zhang Zhu; Jun Yu (Cardiovascular Toxicology, 2011)

Discrepancies between global reanalyses and observations in the interdecadal variations of Southeast Asian cold surge - Wan‐Ru Huang; Shih‐Yu Wang; Johnny C. L. Chan (International Journal of Climatology, 2011)
The Siberian High (SH) is an important part of the East Asian winter monsoon (EAWM) and is closely linked to cold surges. Previous studies revealed a pronounced decline in the strength of the SH during the late 20th century accompanied with a coherent decrease in the frequency of cold surges. However, studies using different data sets yielded different behaviour of the trends. Here we examine the interdecadal variations of the SH and cold surges deduced from six modern global reanalysis data sets. Discrepancies in such variations are found between the reanalysis data sets and observations as well as among different reanalysis data sets. Such discrepancies contribute to inconsistent interdecadal variations of the cold surge frequency in different reanalysis data sets. Potential causes of this situation are discussed. Copyright © 2010 Royal Meteorological Society

Impacts of erucic acid and glucosinolate content on genetic relationships between protein content and fatty acids of rape seed across environments - Chun-Hai Shi; Wei-Dong Xu; Qian-Ru Yu; Hai-Zhen Zhang; Zhong-Wei Yang; Jian-Guo Wu (Euphytica, 2011)

Estimation of nested spatial patterns and seasonal variation in the longitudinal distribution of Sicyopterus japonicus in the Datuan Stream, Taiwan by using geostatistical methods - Yu-Pin Lin; Cheng-Long Wang; Chi-Ru Chang; Hsiao-Hsuan Yu (Environmental Monitoring and Assessment, 2011)

Effects of SKF-96365, a TRPC inhibitor, on melittin-induced inward current and intracellular Ca2+ rise in primary sensory cells - Jing Ding; Yong Xiao; Dan Lu; Yi-Ru Du; Xiu-Yu Cui; Jun Chen (Neuroscience Bulletin, 2011)

Effect of neuronal excitotoxicity on Munc18-1 distribution in nuclei of rat hippocampal neuron and primary cultured neuron - Yan-Ping Zhang; Ping Wan; Hong-Quan Wang; Hong Zhao; Yu-Xia Xu; Ru Yang; Cui-Qing Zhu (Neuroscience Bulletin, 2011)

Assessing abalone growth inhibition risk to cadmium and silver by linking toxicokinetics/toxicodynamics and subcellular partitioning - Wei-Yu Chen; Yun-Ru Ju; Bo-Ching Chen; Jeng-Wei Tsai; Chia-Jung Lin; Chung-Min Liao (Ecotoxicology, 2011)

Lipopolysaccharide-stimulated activation of murine DC2.4 cells is attenuated by n-butylidenephthalide through suppression of the NF-κB pathway - Ru-Huei Fu; Horng-Jyh Hran; Ching-Liang Chu; Chin-Mao Huang; Shih-Ping Liu; Yu-Chi Wang; Ya-Hsien Lin; Woei-Cherng Shyu; Shinn-Zong Lin (Biotechnology Letters, 2011)

Molecular characterization and expression analysis of elongation factors 1A and 2 from the Pacific white shrimp, Litopenaeus vannamei - Lei Wang; Yuan Liu; Wei-Na Wang; Wei-Jun Mai; Yu Xin; Jun Zhou; Wen-Yin He; An-Li Wang; Ru-Yong Sun (Molecular Biology Reports, 2011)

Comparison of Non-covalent Interactions Between a Series of N-Phosphoryl Dipeptide or Methyl Esters and Protein by Electrospray Ionization Mass Spectrometry - Li-ming Qiang; Ming-xiu Lü; Xu-ru Dong; Shu-xia Cao; Kui Lu; Yu-fen Zhao (International Journal of Peptide Research and Therapeutics, 2011)

A phylogeny of Photinia sensu lato (Rosaceae) and related genera based on nrITS and cpDNA analysis - Wei Guo; Yi Yu; Ru-jiang Shen; Wen-bo Liao; Siew-wai Chin; Daniel Potter (Plant Systematics and Evolution, 2011)

Field evaluation of an innovative stormwater treatment device—the StormvaultTM system - Ru Zhang; Wen Bin Zhou; Jing Li; Shaw L. Yu (Environmental Monitoring and Assessment, 2010)

Simulation of organic carbon dynamics at regional scale for paddy soils in China - Xue-Zheng Shi; Ru-Wei Yang; David C. Weindorf; Hong-Jie Wang; Dong-Sheng Yu; Yao Huang; Xian-Zhang Pan; Wei-Xia Sun; Li-Ming Zhang (Climatic Change, 2010)

Glutamate enhances the surface distribution and release of Munc18 in cerebral cortical neurons - Ping Wan; Yan-Ping Zhang; Jie Yan; Yu-Xia Xu; Hong-Quan Wang; Ru Yang; Cui-Qing Zhu (Neuroscience Bulletin, 2010)

Differentiation of cryopreserved human umbilical cord blood-derived stromal cells into cells with an oligodendrocyte phenotype - Yong-Chun Luo; Hong-Tian Zhang; Hao-Yu Cheng; Zhi-Jun Yang; Yi-Wu Dai; Ru-Xiang Xu (In Vitro Cellular & Developmental Biology - Animal, 2010)

A Series of Novel Rare Earth Molybdotungstosilicate Heteropolyoxometalates Binding to Bovine Serum Albumin: Spectroscopic Approach - Yan-Jun Hu; Yu Ou-Yang; Ai-Min Bai; Ru-Ming Zhao; Yi Liu (Biological Trace Element Research, 2010)

Ectopic Expression of the Tomato Mi-1 Gene Confers Resistance to Root Knot Nematodes in Lettuce (Lactuca sativa) - Li-Ying Zhang; Yu-Yang Zhang; Ru-Gang Chen; Jun-Hong Zhang; Tao-Tao Wang; Han-Xia Li; Zhi-Biao Ye (Plant Molecular Biology Reporter, 2010)

Livin abrogates apoptosis of SPC-A1 cell by regulating JNKI signaling pathway - Yu-Sheng Chen; Hong-Ru Li; Ming Lin; Gang Chen; Bao-Song Xie; Neng-Luan Xu; Li-Fang Lin (Molecular Biology Reports, 2010)

Biological Activation of Heteropoly Complex of Molybdotungstosilicate Containing Lanthanum K10H3La(SiMo6W5O39)2⋅26H2O: Spectroscopic Approach and Microcalorimetry - Yan-Jun Hu; Yu Ou-Yang; Ru-Ming Zhao; Yi Liu (Biological Trace Element Research, 2010)

cDNA, genomic sequence cloning and overexpression of ribosomal protein S25 gene (RPS25) from the Giant Panda - Yan-zhe Hao; Wan-ru Hou; Yi-ling Hou; Yu-jie Du; Tian Zhang; Zheng-song Peng (Molecular Biology Reports, 2009)

Studying the Interaction of Pirarubicin with DNA and Determining Pirarubicin in Human Urine Samples: Combining Excitation -Emission Fluorescence Matrices with Second-order Calibration Methods - Hong-Yan Zou; Hai-Long Wu; Yan Zhang; Shu-Fang Li; Jin-Fang Nie; Hai-Yan Fu; Ru-Qin Yu (Journal of Fluorescence, 2009)

Human mesenchymal stem cells-like cells as cellular vehicles for delivery of immunotoxin in vitro - Chang-chen Hu; Yi-quan Ke; Xin-lin Sun; Xiao-dan Jiang; Ru-xiang Xu; Jun Lv; Yu-sheng Wang; Ying-qian Cai; Ling-sha Qin; Yu-xi Zou (Biotechnology Letters, 2009)

Synergistic up-regulation of muscle LIM protein expression in C2C12 and NIH3T3 cells by myogenin and MEF2C - Zhen-Xing Ji; Chao Du; Guo-Sheng Wu; Shu-Yan Li; Guo-Shun An; Yu-Xi Yang; Ru Jia; Hong-Ti Jia; Ju-Hua Ni (Molecular Genetics and Genomics, 2009)

Effects of ginkgolide B on neuronal discharges in paraventricular nucleus of rat hypothalamic slices - Yue Lin; Ru Wang; Xin Wang; Rui-Rong He; Yu-Ming Wu (Neuroscience Bulletin, 2008)

The Influence of Center of Rotation on the Assessment of Trabecular Bone Densitometric and Structural Properties - Zhi-Feng Sheng; Ru-Chun Dai; Xian-Ping Wu; Yu-Lin Ma; Kang Xu; Yu-Hai Zhang; Ye-Bin Jiang; Er-Yuan Liao (Annals of Biomedical Engineering, 2008)

Juvenile Tilapia (Oreochromis mossambicus) Strive to Maintain Physiological Functions After Waterborne Copper Exposure - Su Mei Wu; Hui Ru Ding; Li-Yih Lin; Yu-Siang Lin (Archives of Environmental Contamination and Toxicology, 2008)

Protolith natures and U‐Pb sensitive high mass‐resolution ion microprobe (SHRIMP) zircon ages of the metabasites in Hainan Island, South China: Implications for geodynamic evolution since the late Precambrian - De‐Ru Xu; Bin Xia; Peng‐Chun Li; Guang‐Hao Chen; Ci Ma; Yu‐Quan Zhang (Island Arc, 2007)
Metabasites within the Paleozoic volcanic‐clastic sedimentary sequences in Hainan Island, South China, show large differences not only in the nature of protoliths, but also in zircon U‐Pb sensitive high mass‐resolution ion microprobe (SHRIMP) ages. The protoliths for the Tunchang area metabasites have intraoceanic arc geochemical affinities. In the east‐central island gabbroic to diabasic rocks and pillow lavas are also present, while the Bangxi area metabasites with back‐arc geochemical affinities in the northwest island consist of basaltic, gabbroic and/or picritic rocks. Three types of zircon domains/crystals in the Tunchang area metabasites are defined. Type 1 is comagmatic and yields concordant to approximately concordant 206 Pb/238 U ages ranging from 442.1 ± 13.7 Ma to 514.3 ± 30.2 Ma with a weighted U‐Pb mean age of 445 ± 10 Ma. Type 2 is inherited and yields a weighted 207 Pb/206 Pb mean age of 2488.1 ± 8.3 Ma. Type 3 is magmatic with a 207 Pb/206 Pb age of ca 1450 Ma. Magmatic zircons in the Bangxi area metabasites yield a weighted U‐Pb mean age of 269 ± 4 Ma. We suggest 450 Ma is the minimum age for crystallization of protoliths of the Tunchang area metabasites, because the age range of ca 440–514 Ma probably corresponds to both the time of igneous crystallization and the high‐temperature overprint. The presence of abundant inherited zircons strongly favors derivation of these rocks from a NMORB‐like mantle proximal to continental crust. A protolith age of ca 270 Ma for the Bangxi area metabasites probably records expansion of an epircontinental back‐arc basin and subsequent generation of a small oceanic basin. The presence of ophiolitic rocks with an age of ca 450 Ma, not only in Hainan Island, but also in the Yangtze block, highlights the fact that the South China Caledonian Orogeny was not intracontinental in nature, but characterized by an ocean‐related event.

Long-term aerobic exercise protects the heart against ischemia/reperfusion injury via PI3 kinase-dependent and Akt-mediated mechanism - Kun-Ru Zhang; Hai-Tao Liu; Hai-Feng Zhang; Quan-Jiang Zhang; Qiu-Xia Li; Qiu-Jun Yu; Wen-Yi Guo; Hai-Chang Wang; Feng Gao (Apoptosis, 2007)

Therapeutic effect of microencapsulated porcine retinal pigmented epithelial cells transplantation on rat model of Parkinson’s disease - Hou-Liang Zhang; Jian-Jun Wu; Hui-Min Ren; Jian Wang; Ya-Ru Su; Yu-Ping Jiang (Neuroscience Bulletin, 2007)

Overexpression of lentivirus-mediated glial cell line-derived neurotrophic factor in bone marrow stromal cells and its neuroprotection for the PC12 cells damaged by lactacystin - Ya-Ru Su; Jian Wang; Jian-Jun Wu; Yan Chen; Yu-Ping Jiang (Neuroscience Bulletin, 2007)

Transcriptomic adaptations in rice suspension cells under sucrose starvation - Huei-Jing Wang; Ai-Ru Wan; Chia-Mei Hsu; Kuo-Wei Lee; Su-May Yu; Guang-Yuh Jauh (Plant Molecular Biology, 2007)

Occurrence of foliar rot of pak choy and Chinese mustard caused by Rhizoctonia solani AG1-IB in China - Gen-Hua Yang; Hai-Ru Chen; Shigeo Naito; Jian-Yu Wu; Xia-Hong He; Chun-Fang Duan (Journal of General Plant Pathology, 2005)

Expression of an antibody-targeted plasminogen activator in Escherichia coli using chemically induced stress responses - Ming Yu; Meimin Yu; Binggen Ru (Biotechnology Letters, 2004)

Enhanced expression of an antibody-targeted plasminogen activator in Escherichia coli by fusion to decorsin - Ming Yu; Meimin Yu; Binggen Ru (Biotechnology Letters, 2004)

Cytoplasmic composition in Pinus densata and population establishment of the diploid hybrid pine - Bao‐Hua Song; Xiao‐Quan Wang; Xiao‐Ru Wang; Kai‐Yu Ding; De‐Yuan Hong (Molecular Ecology, 2003)
Sequence and restriction site analyses of the paternally inherited chloroplast rbc L gene and maternally inherited mitochondrial nad 1 fragments from the same set of populations and individuals were used to investigate cytoplasmic composition and population establishment of Pinus densata , a diploid pine that originated through hybridization between P . tabuliformis and P . yunnanensis . Two variable sites and three chlorotypes (TT, TC and GC) were detected on the rbc L gene of the three pines. P . densata harboured the three chlorotypes, two of which (TT, GC) were characteristic of the parental species, respectively. The third chlorotype (TC) was distributed extensively in seven of the 10 P . densata populations analysed, and might represent a mutation type or have been derived from an extinct parent. The distribution of chlorotypes, together with that of mitotypes, indicated that significant founder effect and backcross happened during the population establishment of the hybrid pine. P . tabuliformis and P . yunnanensis had acted as both mother and father donors, i.e. bi‐directional gene flow existed between the two parental species in the past. Population differentiation of P . densata is high, as detected from the cytoplasmic genomes: G ST = 0.533 for cpDNA and G ST = 0.905 for mtDNA. The differences in cytoplasmic composition among the hybrid populations suggest that the local populations have undergone different evolutionary histories.

A cDNA encoding vacuolar type β-d-fructofuranosidase (Osβfruct3) of rice and its expression in Pichia pastoris - Ru-Huei Fu; Ai-Yu Wang; Yu-Chi Wang; Hsien-Yi Sung (Biotechnology Letters, 2003)

Estimation of atmospheric input of mercury to South Lake and Jingyue Pool - Feng-man Fang; Qi-chao Wang; Zhuang-wei Ma; Ru-hai Liu; Yu-hong Cao (Chinese Geographical Science, 2002)

CO2-Enrichment and photosynthetic photon flux affect the growth of in vitro-cultured apple plantlets - Ru Yu Li; Hosakatte Niranjana Murthy; Seon Kyu Kim; Kee Yeoup Paek (Journal of Plant Biology, 2001)

Differential expression of RAB5A in human lung adenocarcinoma cells with different metastasis potential - Li Yu; Feng Hui-chen; Yu Chen; Rong Zou; Song Yan; Liu Chun-xiang; Wang Wu-ru; Pu Li (Clinical & Experimental Metastasis, 1999)

Alkaline Serine Protease Is an Exotoxin of Vibrio alginolyticus in Kuruma Prawn, Penaeus japonicus - Kuo-Kau Lee; Shu-Ru Yu; Ping-Chung Liu (Current Microbiology, 1997)